PEGylated Lipidic Nanocapsules Encapsulating Olaparib for Breast Cancer Therapy: In Vitro and In Vivo Evaluation - Sourabh Tapekar; Anish Dhuri; Priti Paul; Tanmoy Kanp; Rahul Nair; Neeraj Kumar Ravi; Hira Yadav; Bharath M; Khushi Rode; Pankaj Kumar Singh (Journal of Pharmaceutical Innovation, 2027)

Frequency-content dependent seismic assessment of low-, intermediate-, and high-rise base-isolated shear buildings considering soil-structure interaction - Rahul Kumar; Raushan Kumar; Sidhartha Sankar Roy; Kishore Chandra Biswal (Soil Dynamics and Earthquake Engineering, 2027)

Upcycling biomass and bio-based waste into functional carbon for supercapacitors with an insight into prospective life cycle assessment - Unnikrishna Menon; Satvik Anshu; Rahul R; Amreesh Chandra; Amit Kumar; Brajesh Kumar Dubey (Biomass and Bioenergy, 2026)

Identification and validation of HaGNA gene as potential RNAi target for management of Old-World bollworm Helicoverpa armigera (Hübner) - A. Boopathi Kumar; Vivek Shah; Joy Das; Rakesh Kumar; K. V. Anu; Pooja Verma; Neelakanth Hiremani; Shivaji Thube; Rahul M. Phuke; G. T. Behere; V. N. Waghmare (Molecular Biology Reports, 2026)

Identification of condition-specific optimal reference genes for qPCR data normalisation in pink bollworm Pectinophora gossypiella (Saunders) - Joy Das; Rakesh Kumar; K. P. Raghavendra; Suhas G. Karkute; Vivek Shah; Kishor U. Tribhuvan; Rahul M. Phuke; G. T. Behere; Vinita Gotmare; V. N. Waghmare (Molecular Biology Reports, 2026)

From bench to bedside: stem cell therapy as a transformative approach against HIV - Ankit Kumar Bharti S; Anirban Goutam Mukherjee; Abilash Valsala Gopalakrishnan; Babu Gajendran; Rahul Vashishth; Sabina Evan Prince (Molecular Biology Reports, 2026)

Phenotypic diversity and molecular characterization of male sterility based on cytotype and Ms locus variation in Indian onion germplasm - S. Santhiya; Nirmal Kumar Hedau; Anamika Thakur; Anu Singh; Rahul Dev; Lakshmi Kant (Molecular Biology Reports, 2026)

Multi-model GWAS reveals genetic determinants of grain hardness, size and weight in bread wheat (Triticum aestivum L.) - Deepa Bhadana; Jitendra Kumar; Shoeb Ahmed; Anita Kumari; Monika Garg; Joy Roy; Rahul Kumar (Molecular Genetics and Genomics, 2026)

Antimicrobial susceptibility, molecular characterization and multilocus sequence typing of Staphylococcus aureus isolates associated with subclinical mastitis in buffaloes (Bubalus bubalis) in Haryana, India - Ojasvita; Vandna Bhanot; Renu Gupta; Jasleen Kaur; Mahavir Singh; Jinu Manoj; Rahul Yadav; Pankaj Kumar; Parveen Kumar; Satbir Sharma; Rajesh Chhabra (Brazilian Journal of Microbiology, 2026)

Enterotoxin and biofilm producing Staphylococcus aureus and MRSA isolates from animal source foods sold in Assam - Vishnu Raghavendran AV; Zunjar Baburao Dubal; Vinodh Kumar O.R; Rahul Kolhe; Himani Dhanze; Shriya Rawat; Rajiv Ranjan Kumar; KN Viswas (Brazilian Journal of Microbiology, 2026)

Comparative analysis of the emission reduction potential of algal biofuel blends and pure Jet A-1 fuel - Geena Prasad; G. Sujesh; N. Nirmala; Pranav Prasannakumar; Sreejitha Raj; Rahul Kumar (Fuel, 2026)

Assessment and prediction of snow cover dynamics over Siachen using advanced statistics and Hybrid Seasonal-Trend Fourier Regression model - Aditya Kumar Thakur; Harshita Tiwari; Rahul Dev Garg; Kamal Jain (Cold Regions Science and Technology, 2026)

Adapting tulip cultivation to the western Himalayas: A study of growth, flowering, and bulb development in varying agroclimatic conditions - Aparna Misra; Kamlesh Verma; Shagun Rana; Gulshan Birsanta; Anjali Chandel; Rahul Bodh; Rajesh Kumar Singh; Bhavya Bhargava (South African Journal of Botany, 2026)

A comprehensive review on lead removal strategies from industrial wastewater: analysis using carbon quantum dots - D. Prabu; K. Shalini; R. Jayasurya; S. Sathish; M. Karthikeyan; Michael Rahul Soosai; D. Venkatesan; J. Barnabas Paul Glady; J. Aravind Kumar; M. Kavisri; Meivelu Moovendhan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Microplastics as emerging contaminants: Ecotoxicological disruption and human health risks from soil–water–sediment systems to nutrition - Pooja; Gagan Matta; Rama Pal; Gaurav Pant; Shivangi Tyagi; Rahul Saini; Laura Gjyli; Amit Kumar; Rupesh Kumar; Ujjwal Gulaiya (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Dynamics of air quality and meteorological interactions in four high-polluted cities in the Indo-Gangetic Basin, India - Ramesh Kumar; Prity S. Pippal; Suhas Ballal; Michael Rahul Soosai; Rishiv Kalia; Atar Singh; Alok Raj; Payal Sharma; Rajesh Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhanced precipitation estimation in a Himalayan river basin through the fusion of multi-source datasets using various machine learning techniques - Harshita Tiwari; Aditya Kumar Thakur; Rahul Dev Garg (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Efficient analysis of wake dynamics for self-propulsion characteristics of a marine ship hull: A segmented domain approach using partially averaged Navier-Stokes turbulence model - Sonu Kumar; Sawan S. Sinha; Rahul Goyal (Ocean Engineering, 2026)

Magnesium as a structural switch in Fe-AIPA framework: Unlocking ultrafast antibiotic degradation in complex matrices - Smriti Rana; Yogesh Kumar; Rahul Kaushik; Bhaskar Kumar Brahma; Pallav Mondal; Lalita S. Kumar (Journal of Water Process Engineering, 2026)

Biomass-derived aerogels for solar-driven atmospheric water harvesting with enhanced recyclability - Rahul Ranjan; Manraj Kaur; Himanshu Modi; Saurav Kumar; Prodyut Dhar (Journal of Environmental Chemical Engineering, 2026)

Bioplastics derived from microalgae: A new perspective on biorefinery development, challenges, opportunities, and sustainability assessment for a circular bioeconomy approach - Rahul Kumar Goswami; Sandeep Singh Shekhawat; Ismail Rawat; Pradeep Verma; Faizal Bux (Journal of Environmental Chemical Engineering, 2026)

Correction to: Quality by Design (QbD) Assisted HPLC Method for Concurrent Estimation of Aloe-Emodin and Adapalene - Shashi Kant; Raj Kamal; Pankaj Popli; Rahul Kumar Patel; Rohit Bhatia; Rajan Swami (Journal of Pharmaceutical Innovation, 2026)

Exploring Neuroprotective Activity of a Piperine Liposomal Thermogel in 3-nitropropionic Acid-Induced Huntington’s Disease Models - Ayush Kumar; Ashish Dilip Sutar; Khushboo Kumari; Rahul Shukla (Journal of Pharmaceutical Innovation, 2026)

Pathogen recovery, disease severity and agro-climatic associations of wheat spot blotch in selected districts of Eastern Uttar Pradesh, India - Pankaj Tiwari; Rahul Kumar Sharma; Rohit Tiwari; D. N. Shukla; Sunil Kumar Vishwakarma; Sushree Suparna Mahapatra; Swagatika Mohanty (Indian Phytopathology, 2026)

Enhanced extraction of caffeine from tea using natural eutectic deep solvents: Comparative evaluation of choline chloride-based NADES systems - Saurav Kumar; Rahul Sahu; Supriya Chaudhary; Neha Upadhyay; Ritika Karanwal; Anupma Sharma (Next Research, 2026)

Deep-water nutrients mediated glacial-interglacial diatom productivity in the Indian Polar Front Zone of the Southern Ocean - Aditi Nautiyal; Sunil Kumar Shukla; Rahul Mohan (Marine Micropaleontology, 2026)

Musculoskeletal degeneration in space: translational parallels with spaceflight-associated ocular pathology and surgical implications - Rohan Phadke; Samer Salman; Ananya Bansal; Rahul Kumar; Phani Paladugu; Joshua Ong; Ethan Waisberg; Andrew G. Lee (Life Sciences in Space Research, 2026)

Next generation risk assessment and new approach methodologies for sustainable management of heavy metal contaminated environments: A critical review - Prince Kumar Singh; Indrajeet Kumar; Umesh Kumar; Rahul Prasad Singh; Ram Sharan Singh; Rajesh Kumar Sharma (Environmental Pollution, 2026)

Multidimensional genetic analysis of bread wheat (Triticum aestivum L.) germplasm for precision breeding - Ritu Rani; Pradeep Kumar Sharma; Jitendra Kumar; Pushpendra; Rahul Kumar; Sushil Kumar; Priyanka Veerala; Prashant Kaushik (Ecological Genetics and Genomics, 2026)

Waste-to-energy conversion of fruit waste in soil microbial fuel cells using an indigenous electroactive Stutzerimonas stutzeri - Abhinav Kumar Singh; Rahul Gautam; Gaurav Manik (Bioresource Technology Reports, 2026)

Life cycle energy, environment, and economic audit of BEV, HEV & ICEV powertrains in India - Rahul Kumar Singh; Srijit Biswas; Avinash Kumar Agarwal (The International Journal of Life Cycle Assessment, 2026)

Trait-mediated regeneration dynamics and climatic influence on tree size class distribution in central Indian tropical forests - Anil Kumar Kewat; Sanjay Singh; Parmanand Kumar; Arti Khanduri; Abhishek Kumar; Rahul Kumar; Harish Bahadur Chand (Regional Environmental Change, 2026)

Evolving Hazards, Infrastructure Development, and Population Dynamics in Uttarakhand, NW Himalaya - Neha Chauhan; Vipin Kumar; Avijit Sahay; Abhisek K. Srivastav; Rahul Ranjan; Yaspal Sundriyal; Rajiv Sinha; Hugh Sinclair; Gargi Dangwal; Neeharika Chauhan (Regional Environmental Change, 2026)

Machine Learning Based Location Estimation for Analysing GPS Accuracy - Pankaj P. Tasgaonkar; Rahul Dev Garg; Pradeep Kumar Garg; Poonam Bhosale (Journal of the Indian Society of Remote Sensing, 2026)

Extricating the allelic variation, population structure and genetic potential in buckwheat genotypes and substantiation of high yielding and stable genotypes with superior biochemical quality - Sunandan Swain; Bingiala Laloo; Partha Protim Dutta; Simardeep Kaur; Letngam Touthang; Veerendra Kumar Verma; Rahul Chandora; Satish Kumar Yadav; Amit Kumar (Journal of Applied Genetics, 2026)

Assessing the cross transferability of finger millet SSR markers and genetic diversity analysis in browntop millet (Urochloa ramosa L.) based on microsatellite data and morphological traits - G. K. Rahul; P. Bhavani; C. Nandini; R. L. Ravi Kumar (Cereal Research Communications, 2026)

Pilot-scale outdoor raceway pond cultivation of Chlorella minutissima with poultry litter integration for biodiesel production - Sagar Devadiga; Rahul Tiwari; Vinay Bansal; Sashi Sonkar; Sonu Kumar Patidar; Hifjur Raheman; Nirupama Mallick (Algal Research, 2026)

Temperature and Light Interplay Modulate In Vitro Morphogenesis and Steroidal Alkaloid Biosynthesis in Fritillaria roylei Hook. - High Value Critically Endangered Himalayan Herb - Shagun Sharma; Pankaj Kumar; Ashish R. Warghat; Rahul Chandora; Vinay Kumar; Rajnish Sharma; Amisha Rani; Rohit Sharma (Journal of Plant Growth Regulation, 2026)

Advancing oceanographic forecasts in the Bay of Bengal: an AI-based spatiotemporal prediction for SST and MLD - Bipin Kumar; Rahul Kumar; Bishakhdatta Gayen; Sourav Kumar Khan; Bajrang Chidhambaranathan; S V S S N V G Krishna Murthy; Ravi S Nanjundiah; M Ravichandran (Journal of Earth System Science, 2026)

Counting of rice panicles using drone mounted RGB sensor and deep learning approaches - Rahul Tripathi; Ashish Kumar Gouda; Shiv Sundar Jena; Smruti Ranjan Sahu; Sushanta Kumar Dash; Milan Kumar Lal; Rabi Narayan Sahoo (Journal of Crop Science and Biotechnology, 2026)

Doronicum sanctum (Asteraceae): a new species of sunflower family discovered from the Indian Himalaya - Rahul Kumar; Vikas Kumar (Biologia, 2026)

Chronic Fluoride Exposure Disrupts Calcium-Dependent Neurodevelopmental Signalling and Brain Proteomic Architecture: Multi-Target Modulation by Naringin - Ravindra Shantakumar Swamy; Shalini Choudhary; Abhishek Ambawatiya; Vishal Chhabra; Mayank Mishra; Md Abubakar; Smita Shenoy; Naveen Kumar; Rahul L. Gajbhiye; Amita Rai; Velayutham Ravichandiran; Nitesh Kumar (Biological Trace Element Research, 2026)

Advances in spectroscopic and machine learning approaches for estimating soil organic carbon and nitrogen: a comprehensive review - Swagata Ghosh; Sangita Mohanty; Rahul Tripathi; Bijan Kumar Mondal (International Journal of Remote Sensing, 2026)

Escalating heat waves and human thermal stress over semi-arid Bundelkhand region, India - Yogeshwar Singh; Rahul Kumar; Soumyajeet Sahu; Shobhit Pipil; Shiv Vendra Singh; Pavan Kumar; Manish Srivastav; A.K. Singh (Urban Climate, 2026)

Distributions of membrane lipids (3-hydroxy fatty acids and brGDGTs) in the Eastern Himalayan soil and their global context: insights into temperature and pH variations - Uday Narayan Guria; Santrupta Samantaray; Rahul Sen; Vishal Kumar; Bibhasvata Dasgupta; Mahesh Ghosh; Prasanta Sanyal (Organic Geochemistry, 2026)

Stable carbon isotopic tracing of organic matter transformation and soil CO2 sources across tropical sub-humid to semi-arid climates - Amzad Hussain Laskar; Ranjan Kumar Mohanty; Rahul Kumar Agrawal; Ankur Kumar Dabhi; Sanjeev Kumar (Organic Geochemistry, 2026)

Investigating the seasonal habitat use and key factors shaping the distribution of Asian elephant in the Melagiris - Rahul Gour; Robert S. Davis; S.R. Sanjeev Kumar (Journal for Nature Conservation, 2026)

Ethnopharmacological exploration of Indian medicinal plants: from traditional knowledge to modern medicine - Indrajeet Kumar; Sachin Kumar Vishwakarma; Prince Kumar Singh; Umesh Kumar; Rahul Prasad Singh; Parvati Madheshiya; Akanksha Dwivedi; Priyanka Singh; Rajesh Kumar Sharma (Phytochemistry Reviews, 2026)

Debris flow events on 5th August 2025 in Dharali region, Uttarakhand Himalaya, India: insights from remote sensing data - Ravi Kumar Umrao; Rahul Kumar Verma; Rajesh Singh (Natural Hazards, 2026)

Integrated Modeling of Water Availability in a Changing Climate for the Teesta Basin in the Eastern Himalayan State of Sikkim, India - Swapnali Barman; Waikhom Rahul Singh; Biman Kalita; Manmohan Kumar Goel; Deepti Rani (International Journal of Environmental Research, 2026)

Shaping SHAPE - A spectro-polarimeter onboard Chandrayaan-3 to observe Earth as an Exoplanet - Anuj Nandi; Swapnil Singh; Bhavesh Jaiswal; Anand Jain; Smrati Verma; Reenu Palawat; B.T. Ravishankar; Brajpal Singh; Priyanka Das; Supratik Bose; Supriya Verma; Waghmare Rahul Gautam; et al. (Advances in Space Research, 2026)

Graph Neural Networks in Neuroimaging: Current Status and Biostatistical Considerations for Clinical Deployment - Rahul Kumar; Kyle Sporn; Ethan Waisberg; Joshua Ong; Phani Paladugu; Tejas Sekhar; Tamer Hage; Swapna Vaja; Nicolas Nelson; Mouayad Masalkhi; Ryung Lee; Dylan Amiri; et al. (Annals of Biomedical Engineering, 2026)

Suitability analysis of agroforestry in Himachal Pradesh by using a multi-criteria GIS–AHP approach - Saakshi; D. R. Bhardwaj; Prem Prakash Sharma; Dushyant Sharma; Rahul Bodh; Avinash Kumar Bhatia (Agroforestry Systems, 2026)

Dietary phytoestrogen ameliorates ovarian toxicant–induced neurotoxicity: mechanistic and metabolic insights - Ambika Shandilya; Suhas Hajare; Dube Aakash Arwind; Chander Kant Giri; Rahul Gajbhiye; V. Ravichandiran; Vipan Kumar Parihar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Advances in Biological Control of Fungal Phytopathogens: Toward Achieving Sustainable Development Goals (SDGs) in Agriculture - Sanjay Kumar Goswami; Ranjit Singh Gujjar; Rajeev Kumar; Rahul Kumar Tiwari; Abhijeet S. Kashyap; Nazia Manzar; Iram Saifi; Anamika Singh; Vibha Kumari Dewangan (Journal of Crop Health, 2026)

Archaeobotanical data from a Baran settlement (4,300–3,400 yrs bp) in the Ghaggar basin (northwestern India) reveals continuity of the Indus crop package after the Meghalayan stage drought - Mansi Swaroop; Shalini Sharma; Ruchita Yadav; Xiaoyan Yang; Guanghui Dong; Akinori Uesugi; Srinivas Bikkina; Alka Srivastava; Rahul Kumar; Anil K. Pokharia (Vegetation History and Archaeobotany, 2026)

Raman spectroscopic signatures of prostate cancer progression: correlation with gleason score - Samaneh Ghazanfarpour; Rahul Kumar Das; Satish Sharma; Stanley A. Schwartz; Kent Chevli; Wilfrido Mojica; Anna Sharikova; Supriya D. Mahajan; Alexander Khmaladze; Ravikumar Aalinkeel (Molecular and Cellular Biochemistry, 2026)
Prostate cancer (CaP) is a heterogeneous malignancy, and its grading via Gleason scoring is essential for prognosis and therapeutic decision‑making. However, traditional histopathological methods are limited in detecting subtle biochemical variations. This study applies Raman spectroscopy (RS) to formalin‑fixed paraffin‑embedded (FFPE) CaP tissues of varying Gleason scores to uncover biochemical signatures associated with tumor aggressiveness. Raman spectral analysis reveals distinct molecular alterations particularly in lipid, protein, and nucleic acid content that differ across Gleason patterns reflecting grade‑associated biochemical differences rather than any biological progression between patterns. Singular Value Decomposition (SVD) of Raman data enables discrimination between benign prostate tissue and higher‑grade cancer (Gleason ≥ 7) included in this study and stratifies the analyzed Gleason patterns. Our goal in this initial study was not to define definitive Raman biomarkers but to evaluate whether consistent biochemical differences across Gleason grades could be detected in FFPE tissue. Our findings support the potential of Raman spectroscopy as a label‑free, non‑destructive adjunct to conventional histopathology for improved CaP stratification.

Precision repurposing of clinically characterized molecules targeting dengue virus RNA-dependent RNA polymerase: an in silico identification and in vitro validation - Hrithika Panday; Babita Bohra; Rahul Shukla; Vivek Dhar Dwivedi; Abhimanyu Kumar Jha (Folia Microbiologica, 2026)

Poly (lactic-co-glycolic acid) nanoplatforms for triple-negative breast cancer: current progress, advances, and future outlook - Aakash Sharma; Ashwini Kumar Mishra; Pooja Mathur; Rahul Pratap Singh; Laxmi Rani (DARU Journal of Pharmaceutical Sciences, 2026)

Genome-wide Analysis of Laccase Gene Family in Tomato Highlights the Role of SlLAC16 in Lignin Biosynthesis - Gyanesh Shukla; Vishal; Akash; Abhishek Roychowdhury; Rahul Kumar (Journal of Plant Growth Regulation, 2026)

Double-edged sword of fungicides: non-target and harmful effects and their management for eco-friendly agriculture - Sanjay Kumar Goswami; Ranjit Singh Gujjar; Rajeev Kumar; Rahul Kumar Tiwari; Hillol Chakdar; Prassan Choudhary; Saket Kumar; Sumit Kumar; Mala Kumari (Indian Phytopathology, 2026)

Role of Elicitors on the Growth Parameters, Essential Oil Composition, and Antioxidant Capacity of Matricaria chamomilla - Shagun Thakur; Amisha Rani; Palak Thakur; Yash Pal Sharma; Ashun Chaudhary; Vishav Prakash Rahul; Rohit Sharma; Pankaj Kumar; Bhupender Dutt (Agricultural Research, 2026)

Calcium Dynamics in Sugar Crops: From Root Uptake to Stress Adaptation - Varucha Misra; A. K. Mall; S. Solomon; Rahul Tiwari; Dheeraj Kumar Tiwari (Sugar Tech, 2026)

Population structure and genetic diversity of Elwendia persica in the Western Himalayan region of India - Sangita Bansal; Parampara Joshi; Sabina Rana; Amit Kumar; Era V. Malhotra; Ajaz A. Lone; Narender Negi; Rahul Chandora; Sandeep Kumar; Rakesh Singh; G.P. Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Prediction of rigid rockfall barrier settlement under dynamic impact using numerical modelling and machine learning methodologies - Rahul Kumar; Virat Singh Chauhan; M.R. Sadique; Mohd.Masroor Alam (Computers and Geotechnics, 2026)

A Scalable Functional Nanogel of Polyacrylamide-Piperazine-Copper Oxide Nanoparticles for Enhanced Biogas Purification - Bibhuti Bhusan Sahoo; Mohd. Usama; Rahul Vyas; Dharmendra Kumar Bal (Bioresource Technology, 2026)

Recent Developments Regarding the Causes, Effects, and Methods of Bioremediation of Microplastics - Nidhi Kumari; Rahul Kumar; Debasis Mitra; Anuprita Ray (Water, Air, & Soil Pollution, 2026)

A new estimation strategy for the population mean under stratified double sampling: an empirical study based on production and productivity data - Mukesh Kumar Verma; Rahul Varshney; Subhash Kumar Yadav; Sarthak Sachdeva (Stochastic Environmental Research and Risk Assessment, 2026)

Optimization of parameters influencing the properties of foamed bitumen stabilized materials using response surface methodology - Rahul Kumar; Siksha S. Kar; U. C. Sahoo (Innovative Infrastructure Solutions, 2026)

Tinosporide promotes melanogenesis via activation of cAMP/PKA/CREB–MITF signaling in B16F10 and SK-MEL-2 cells - Sukhamoy Dhabal; Anirban Kr Chakrabarty; Rajiva Kumar Rai; Satyabrata Mohapatra; Rahul Singh; Chandra Kant Katiyar; Sunil Kumar Dubey (Journal of Natural Medicines, 2026)

Association of Serum Lithium Levels with Insulin Resistance in Type-2 Diabetes Patients - Pramod Kumar; Rasna Gupta; Manoj Yadav; Rahul Patel; Mahendra Kumar Meena; Ankit Gupta (Biological Trace Element Research, 2026)

Fuzzy-Clustering Driven Soil Nutrients Management Zone Delineation in Mandarin (Citrus reticulata Blanco) Growing Areas of Malwa Plateau Region of India - Seema Bhardwaj; Sanjib Kumar Behera; Rahul Mishra; Sanjay Kumar Sharma; Sudhir Kumar Trivedi; Vimal Shukla; Akanksha Sikarwar; Arvind Kumar Shukla (Journal of Soil Science and Plant Nutrition, 2026)

Assessing Mining-Induced Groundwater Level Decline Using Integrated Spatial and Statistical Techniques in the Moher Sub-basin, Singrauli Coalfield, India - Rahul Karki; Abul Amir Khan; S. K. Gara; Prem Kumar; Sahil Wadhwa (Mine Water and the Environment, 2026)

Genetic characteristics and connectivity of the southernmost snow leopard populations in the Indian Himalayan Region: Conservation implications - Sujeet Kumar Singh; Bheem Dutt Joshi; Reeta Sharma; Rahul De; Jouni Aspi; Laura Kvist; Aishwarya Maheshwari; Tawqir Bashir; Diwakar Sharma; Mukesh Thakur; Manoj Kumar; Indranil Mondal; et al. (Mammalian Biology, 2026)

Association of Haematological and Biochemical Inflammatory Indices with Angiographic Severity of Coronary Artery Disease in Chronic Stable Angina - Kuldeep Kumar Gaur; Ankit Kumar Yadav; Sojit Tomo; Mayank Yadav; Atul Kaushik; Rahul Choudhary; Surender Deora (Indian Journal of Clinical Biochemistry, 2026)

Inadequate immunorecognition and ineffective paraspecific neutralisation of lethality and toxicity of Trimeresurus erythrurus venom by Indian polyvalent antivenom compared to Trimeresurus popeiorum venom - Rahul Kumar; Rosy Mahato; Bhargab Kalita; Ashis K. Mukherjee (Toxicon, 2026)

Synthesis, crystal structure, and DFT study of a novel quinoline-based schiff base with nonlinear optical and biological potential - Asif Jamal; Md. Serajul Haque Faizi; Ansu Kumar Roy; Rafat Hajra; Rahul Kumar Gupta; Vaishali Anand; Khushbu Singh; Navedul Haque (Next Research, 2026)

Spatio-temporal assessment of soil biogeochemical properties and CO2 efflux in a dry tropical watershed of India - Roja Eliza; Rahul Kumar Pandey; Anshumali (Geoderma Regional, 2026)

Trade-offs and synergies of conservation agriculture practices in the maize–wheat system: Improving yield, profitability, and soil resilience in a changing climate - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; R.K. Singh; Kapila Shekhawat; B.S. Dwivedi; P.K. Upadhyay; Sunita Kumari Meena; Amit Kumar; Adarsh Kumar; Gaurav Verma; et al. (Field Crops Research, 2026)

Characterization of two different Coastally-Attached Lagrangian Coherent Structures and their applications for horizontal transport and mixing in the nearshore regions - Rahul Deogharia; Hitesh Gupta; Prasenjit Dey; Rajesh Sikhakolli; Sourav Sil; Avijit Gangopadhyay; Basanta Kumar Jena (Estuarine, Coastal and Shelf Science, 2026)

Abiotic stress-driven multivariate statistical optimization for enhanced α-tocopherol and lutein production in Tetraselmis indica BDUG001 - Udaypal Udaypal; Rahul Kumar Goswami; Pradeep Verma (Biocatalysis and Agricultural Biotechnology, 2026)

Genetic mapping and candidate gene analysis of flag leaf and yield traits using a MAGIC population under heat stress in wheat (Triticum aestivum L.) - Ananta Bag; Hari Krishna; P. . Vinodh Kumar; Narayana Bhat Devate; Rahul Meena; Sudhir Kumar; Ravindra Patil; Uday Govinda Reddy; Jang Bahadur Singh; Neelu Jain; Pradeep Kumar Singh; Gyanendra Pratap Singh (Plant Physiology Reports, 2026)

Delineation of Soil Nutrient Management Zone for Site-Specific Sulphur and Micronutrient Management: A Case Study of Jhansi Bundelkhand Region of India - Rahul Mishra; Sanjib Kumar Behera; Arvind Kumar Shukla; Vimal Shukla (Agricultural Research, 2026)

Labeo kaage sp. nov., a new species of cyprinid fish ( T eleostei: C yprinidae) from the C auvery R iver basin, India - Rahul G. Kumar; Charan Ravi; Nadumury Pradeep Krishnaprasoon; Valaparambil Saidumohmed Basheer (Journal of Fish Biology, 2026)
A new species of Labeo , Labeo kaage , is described from the Cauvery River, India. This distinctive black‐coloured species closely resembles Labeo nigrescens , Labeo filiferus , Labeo chekida and Labeo calbasu but is distinguished by unique morphological and genetic traits. It differs from L. nigrescens in the pectoral fin not reaching the pelvic fin, the presence of ½8–½9 + 1 + 6 scales in transverse series, 16½ branched dorsal‐fin rays, 37–38 vertebrae and absence of the lateral‐line kink near the 17th pored scale. Unlike L. filiferus , the anterior dorsal‐fin rays are not filamentous, and prominent acanthoid tubercles are present in the preorbital field. Compared to L. calbasu, L. kaage has a shallower body depth [27.4%–31.8% standard length (SL)], a dorsal‐fin base that is longer than its height and the adpressed pelvic fin reaching the anal‐fin origin. Mitochondrial cytochrome c oxidase subunit I (COI) gene analysis confirms that L. kaage is genetically distinct, with uncorrected p ‐distances of 5.4%–6.2% from L. calbasu and 5.2%–5.4% from L. nigrescens . Additionally, L. kaage is distinguished from congeners by its uniformly dark green to black body and fins, the presence of two pairs of barbels longer than the eye diameter, acanthoid tubercles with 3–5 spines in the preorbital, ethmoid, rhinal and rostral fields, a greatest body depth not exceeding one‐third of the SL, non‐extended anterior dorsal‐fin rays, adpressed pectoral fins not reaching the pelvic fins and a lateral line with 38 + 2–3 scales. This discovery underscores the importance of continued exploration to reveal the rich fish diversity of the Cauvery River basin.

Linear and Nonlinear Spectroscopic Insights Into the Synergistic Solvation of Rhodamine-6G in Methanol-Dichloromethane Binary Solvent Mixture - Rahul Kumar Gupta; Surya Kant; Debabrata Goswami (Journal of Fluorescence, 2026)

Radical Quenching and LOX Inhibiting Properties of Indole Derivatives: A Plausible Mechanism of Action Through HAT, SET-PT and SPLET Pathway - Km Srishti; Oseen Negi; Anamika Gusain; Naresh Kumar; Rahul Kumar Vishwakarma; Prasanta Kumar Hota (Journal of Fluorescence, 2026)

Alcohol-diesel blends fueled off-road compression ignition engine development: part 2 − Influence of ethanol-diesel blends on engine performance, combustion, and emissions - Hardikk Valera; Shanti Mehra; Rahul Kumar Singh; Jakub Čedík; Martin Pexa; Avinash Kumar Agarwal (Fuel, 2026)

Molecular evidence of Japanese encephalitis virus in poultry: Need to further elucidate JEV epidemiology - Ishita Gupta; Himani Dhanze; Suman Kumar M; Asok Kumar M; Rahul Singh; Vineetha S; Bablu Kumar; Premanshu Dandapat (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Machine Learning Based MODIS Day-Night Land Surface Temperature Downscaling Over India - Rahul Harod; Eswar Rajasekaran; Rahul Nigam; Bimal Kumar Bhattacharya (Journal of the Indian Society of Remote Sensing, 2026)

Evolutionary Dynamics and Abiotic Stress Responses of 20S Proteasome Gene Family in Maize (Zea mays L.) - Hemant Sharma; Shoeb Ahmed; Rahul Kumar (Journal of Plant Growth Regulation, 2026)

Plant Resilience to Abiotic Stress: Enhancing Mechanisms, Strategies, and Innovations - Vasudha Maurya; Rahul Kumar (Journal of Plant Growth Regulation, 2026)

Assessing energy fluxes of lowland rice fields using four-year eddy covariance data - Dibyendu Chatterjee; Abhijit Pradhan; Chinmaya Kumar Swain; Rounak Alam; Rahul Tripathi; Pratap Bhattacharyya (International Journal of Biometeorology, 2026)

Exploring Kolmogorov–Arnold networks for hyperspectral crop classification – an evaluative study - Shruti Gupta; Ashish Kumar; Rahul Dev Garg; Neeraj Jain (Advances in Space Research, 2026)

Autophagy-lysosomal dependency defines a vulnerable physiological state in drug-tolerant persister cells of triple-negative breast cancer - Essha Chatterjee; Biswajit Dey; Anamika Sharma; Anil Dharavath; Aliva Naik; Hoshiyar Singh; Santanu Basak; Bhavna Pratyusha; Vigneshwar Reddy Ashireddygari; Prasad Tammineni; Harikrishna Adicherla; Ira Bhatnagar; et al. (Apoptosis, 2026)

Synergistic effect of indigenous endophytes to boost nutritional content, quality traits and yield in tomato - K. R. Nayana; Sumit Deswal; Satish Kumar; Rahul Kumar Dhaka; Arvind Pratap Singh; Anuj Rana (Antonie van Leeuwenhoek, 2026)

Association of Low-Density Lipoprotein Receptor-Related Protein 5 Haplotypes with Depression Risk in Type 2 Diabetes Mellitus: A Linkage Disequilibrium Approach - Jiya Singh; Praveen Kumar Singh; Rahul Amoli; Anindya Das; Ravi Kant; Anissa Atif Mirza; Sarama Saha (Indian Journal of Clinical Biochemistry, 2026)

Human reproductive exposure to microplastics: A multi-technique analytical study of menstrual and amniotic fluids - Girish Chandra Sharma; Neeraj Kumar; Damini Devrukhkar; Rahul Mulchandji Joshi; Sourav Debnath; Bhumi Chaturvedi; Sumit Rajotiya; Shivang Mishra; Anupama Sharma; Mahaveer Singh; Deepak Nathiya; Balvir Singh Tomar (NanoImpact, 2026)

Exploring the potential of tyre derived graphene for supercapacitor applications: A DFT approach - Rahul Kumar Jha; Anurag Srivastava; Nand Gopal Sahoo; Suman Mahendia; Sravendra Rana (Journal of Environmental Chemical Engineering, 2026)

Integrated multi-analytical framework for comprehensive characterization of lignocellulosic hydrolysates for biorefinary applications - Sarvesh Kumar; Paula Nousiainen; Donya Kamravamanesh; Rahul Mangayil (Biomass and Bioenergy, 2026)

Smart farming approaches in medicinal plant cultivation: a review of techniques, benefits, and sustainability - Sanjeev Khan; Nutan Pathania; Pawan Kumar; Rahul Kumar; Jitender Kumar; Nitesh Kumar; Arti Sharma (Planta, 2026)

Role of endophytes in management of horticultural crops - Sucharita Mohapatra; Mehjebin Rahman; Lellapalli Rithesh; Anwesha Sharma; Shenaz Sultana Ahmed; Trishna Taye; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (Planta, 2026)

Comprehensive Assessment of Ground Deformation Dynamics and Displacement Patterns in Jeenagora Opencast Coal Mining Region of Jharia Coalfield Using PS-InSAR and Advanced Statistical Analysis - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Natural Resources Research, 2026)

Hybrid Ensemble Framework for Enhanced Crop Classification Using Hyperspectral Remote Sensing - Ashish Kumar; Rahul Dev Garg (Journal of the Indian Society of Remote Sensing, 2026)

GIS-Based Multi-criteria Flood Risk Assessment Using AHP in the Arpa River Basin, Chhattisgarh - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of the Indian Society of Remote Sensing, 2026)

Prediction of Tropospheric Nitrogen Dioxide in Kolkata Using Sentinel-5p and Sentinel-2 Multispectral Data and Machine Learning Algorithm - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Journal of the Indian Society of Remote Sensing, 2026)

Mucuna pruriens extract as prebiotic and Lactobacillus rhamnosus as probiotic intervention mitigated histological changes in DNCB-induced colitis via GLP-1/Nrf2/NF-κB axis regulation - Lokesh Nama; Md. Abubakar; Rajni Daksh; Gunjan Goel; Rahul Laxman Gajbhiye; Prabhat Kumar; Amita Rai; Krishna Murti; Velayutham Ravichandiran; Nitesh Kumar (Journal of Molecular Histology, 2026)

Environmental radioactivity and radiological hazard assessment of soil samples from Rajasthan, India - Mahesh Tiwari; Amar Dutt Pant; Tejas Rathod; Sanjay Kumar Sahu; Rahul Bhangare; Amit Kumar Verma; Anilkumar Pillai; Vandana Pulhani (Environmental Geochemistry and Health, 2026)

Macrophage-targeted Hyaluronic-acid Coated Liposomes Bearing Ursolic Acid for Visceral Leishmaniasis: In Vitro Characterisation and Pharmacokinetic Analysis - Spandana Gollapalli; Soyal Sayyed; Pawan Devangan; Dinesh Kumar Chandanpalli; Nandkumar Doijad; Rahul Kumar; Jitender Madan (Current Microbiology, 2026)

Correlation of enhanced antioxidant enzyme activity and phenolic content with downy mildew resistance in cucumber (Cucumis sativus L.) - Rahul Kumar; Vidya Sagar; Dharm Pal Singh; Pragya; Sudhakar Pandey; Rajeev Kumar; Jyoti Devi; Nakul Gupta; Shailesh Kumar Tiwari; Nagendra Rai; Rajesh Kumar (Journal of Plant Pathology, 2026)

Changing Northeast India Summer Monsoon Onset Dynamics in a Warming World - Simanta Das; Rahul Mahanta; Bijit Kumar Banerjee; B. N. Goswami (International Journal of Climatology, 2026)
The Indian Summer Monsoon typically begins over Northeast India (NEI) about 2 weeks earlier than monsoon onset over Kerala, extending the rainy season in NEI to around 150 days. This early onset is strongly linked to planetary‐scale processes, particularly interactions with extratropical Rossby waves. These waves facilitate the downward and southward intrusion of potential vorticity, which triggers low‐level cyclonic vorticity and initiates monsoon onset. The quasi‐biweekly oscillation further facilitates this process. While climate change is associated with a weakening of the seasonal mean monsoon over NEI, its impact on extratropical influences and the trend of earlier onset remains uncertain. This study examines changes in tropical circulation and extratropical influences by comparing two periods: 1940–1960 and 2002–2023. Results reveal a marked increase in extratropical influence in recent decades. In 2002–2023, clear signs of downward PV intrusion and enhanced low‐level cyclonic vorticity are observed, in contrast to the earlier period where such features are largely absent. Lead–lag composites of PV anomalies at 200 hPa show prominent eastward‐propagating signals during onset in the recent period. In 1940–1960, monsoon onset was primarily driven by local mesoscale convection and self‐organisation, with cyclonic vorticity strengthening 2 days post‐onset. During the earlier period, heat sources were more likely driven by local convective instability, as indicated by higher convective available potential energy, which was approximately 500 J/kg greater at the time of monsoon onset. Additionally, air‐sea interactions have become more influential in recent decades. While stronger Sea surface temperatures (SSTs) over the Bay of Bengal (BOB) during pre‐onset facilitates the onset through enhanced moisture flux, SSTs over BOB tend to cool once the onset process begins. These findings highlight a significant shift in monsoon onset mechanisms over NEI, with increasing extratropical control and evolving ocean–atmosphere interactions likely shaped by climate change.

Sustained cadmium exposure and hyperglycemia additively drives mitochondrial dysfunction in hepatic cells: Implications for MASLD etiopathogenesis - Rahul Kumar; Ashwin Chinala; Sharina Palencia Desai; Li Chen; Marcus A. Garcia; Sarah J. Blossom; Matthew J. Campen; Rama R. Gullapalli (Toxicology and Applied Pharmacology, 2026)

Cellulose nanocrystals from forest residues: An integrated techno-economic analysis and life cycle assessment - Rahul Prasad Bangalore Ashok; Richard Bergman; Md Shahadat Hossain; Deepak Kumar; Prakash Nepal; Troy Runge (Resources, Conservation and Recycling, 2026)

Root-microbiome signaling networks under climate stress: Mechanistic insights and rhizosphere engineering opportunities - Sipra Mohapatra; Vishal Johar; Hina Upadhyay; Anand Kumar; Premdeep; Prayasi Nayak; Mouli Paul; Swagatika Babu; Rahul Pradhan; Pragnyashree Mishra; Himanshu Saini (Rhizosphere, 2026)

In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

Understanding molecular mechanisms driving cadmium-induced mitochondrial dysfunction in human metabolic liver disease - Rahul Kumar; Ashwin Chinala; Rama R. Gullapalli (Environmental Toxicology and Pharmacology, 2026)

Exploration of genetic diversity and population structure in North Indian Aegle marmelos accessions using ISSR markers - Prince Minhas; Rajvinder Minhas; Atul Chamyal; Rakesh Kumar; Kanika Aggarwal; Rahul Kumar; Maneet Rana; Vikas Sharma (Ecological Genetics and Genomics, 2026)

Process optimization of bioleaching for sustainable recovery of metals from waste lithium-ion batteries - Rahul Rautela; Bholu Ram Yadav; Sunil Kumar (Bioresource Technology, 2026)

A Comprehensive Assessment of Spatiotemporal Dynamics of Urban NO2 using Sentinel-5P with Evaluation of the Predictive Capability of Sentinel-2 for Pollution Estimation - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Water, Air, & Soil Pollution, 2026)

Microbial Fuel Cells as a Sustainable and Eco-Friendly Technology for Microplastic Degradation in Wastewater: A Future Perspective - Tukendra Kumar; Rahul Baghel; Satya Eswari Jujjavarapu (Water, Air, & Soil Pollution, 2026)

Mapping agricultural vulnerability to climate-driven drought using the TOPSIS model - Kiran Kumar Mohapatra; Amaresh Kumar Nayak; Ranjan Kumar Patra; Rahul Tripathi; Chinmaya Kumar Swain; Rasu Eeswaran; Saheed Garnaik (Theoretical and Applied Climatology, 2026)

Genome-wide association analysis using multi model approach identified novel associations for plant architectural traits in chickpea germplasm collection - Rahul Raiya; Hemant Kumar Yadav; Kuldeep Kumar; Nitish Ranjan Prakash; Swarup Kumar Parida; Chellapilla Bharadwaj; Venkatraman Hegde; Shailesh Tripathi (The Nucleus, 2026)

Multivariate and nonlinear analyses to characterize phenotypic variability in landraces and cultivars of rice (Oryza sativa L.) - Soham Hazra; Debarpita Datta Ray; Abhisek Hazra; Avishek Chatterjee; Ankur Mukhopadhyay; Subhadwip Ghorai; Pabitra Kumar Ghosh; Suvojit Bose; Sourav Roy; Tina Nath; Sabuj Ghosh; Deep Pal; et al. (Plant Physiology Reports, 2026)

Exploring the feasibility and challenges of AI-based rainfall-induced landslides prediction - Dibyajyoti Chutia; Ranjan Kumar Deka; Rahul Kumar; Praveen Kumar; Avinash Chauhan; Puyam S. Singh; Nilay Nishant; Prakash Biswakarma; K. K. Sarma; S. P. Aggarwal (Natural Hazards, 2026)

Crop Suitability Analysis for Cereal Production in Bilaspur, Chhattisgarh, Using the Analytical Hierarchy Process and GIS Techniques - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of the Indian Society of Remote Sensing, 2026)

A Coumarin Derived 2-Methylthio-4-Hydroxypyrimidine[3,4-b]coumarin Fluorescent Chemosensor for Detection of Hypochlorite Ions in Aqueous Medium - Aruna; Kanchan; Arunava Agarwala; Gulshan Kumar; Rahul Shrivastava (Journal of Fluorescence, 2026)

Agronomic performance, grain quality and water productivity of basmati rice (Oryza sativa L.) under sixteen years long-term organic production system - Anita Kumawat; Dinesh Kumar; Y. S. Shivay; Devideen Yadav; M. Madhu; Shakir Ali; Sandeep Gawdiya; Ashok Kumar; Rahul Sadhukhan; R. A. Jat (Paddy and Water Environment, 2026)

Diversity and ecological assessment of aquatic algal species of river Varuna in Varanasi - Abhinav Sharma; Akash Thakur; Priya Yadav; Rahul Prasad Singh; Himani Sharma; Ashutosh Tyagi; Mukul Chaudhari; Rajan Kumar Gupta (Vegetos, 2026)

First record of Myzus persicae (Hemiptera: Aphididae) infesting heeng, Ferula assa-foetida L - Rahul Kumar; Rupinder Kaur; Aditya Singh Ranout; Satbeer Singh; Ramesh Chauhan; Sanatsujat Singh; Gireesh Nadda (International Journal of Tropical Insect Science, 2026)

Chlorine-UV hybrid disinfection: a review on mechanisms and efficiency towards emerging pollutants - Sandeep Singh Shekhawat; Rahul Kumar Goswami; Akhilendra Bhushan Gupta; Faizal Bux (Environmental Science and Pollution Research, 2026)
This review comprehensively evaluates the direct and indirect disinfection mechanisms and performance of chlorine-UV hybrid disinfection (CUV-HD) for the removal of microbial and emerging contaminants, including post-disinfection regrowth and formation potential of disinfection byproducts (DBPs), to ensure safe reuse of treated effluents. Direct disinfection reactions are mediated by HOCl and OCl⁻, as well as UV-induced photolytic damage. In contrast, indirect inactivation is driven by reactive oxygen species (ROS), particularly ∙OH, and reactive chlorine species (RCS) such as Cl∙, ClO∙, and Cl₂∙⁻. The order of reactive species generation indicates UV/chlorine > chlorine–UV > UV–chlorine, which is supported by the effective reduction potential and, consequently, the disinfection efficacy against microbial pollutants in treated wastewater. However, the water matrix, including pH, temperature, organic matter, and total suspended solids (TSS), significantly influences both the disinfection efficiency of these hybrid strategies and the potential formation of disinfection byproducts (DBPs). The formation potential of DBPs follows the order: UV/chlorine > UV–chlorine > chlorine–UV. Further studies quantifying reactive chlorine species (RCS) and elucidating their roles in CUV-HD are needed to fully understand the underlying indirect disinfection mechanisms.

Classification of Wheat (Triticum aestivum) Cultivars for Iron Efficiency Under Western India Conditions - Dileep Kumar; Khushvadan C. Patel; Arvind Kumar Shukla; Sanjib Kumar Behera; Salwinder Singh Dhaliwal; Pradeep Kumar; Ravi A. Patel; Rahul Mishra; Ajay S. Bhanvadia (Agricultural Research, 2026)

Material characterisation and simulation-based remediation of a failed earthen canal for enhanced hydraulic and structural performance - Omkar Prakash Navagire; Rahul Shende; Rakesh Kumar Verma; V. Srinivasan; Ashwini Mirajkar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Microbial metabolites–-a sustainable solution for agricultural challenges: A review - Rajat SINGH; Priyanka SONI; Rajul JAIN; Akash CHAUHAN; Rahul KUMAR; Divya GUNSOLA; Sourav CHATTARAJ; Sergio DE LOS SANTOS-VILLALOBOS; Debasis MITRA; Ashish GAUR (Pedosphere, 2026)

The skin lightening properties of mushrooms: A comprehensive review of mechanisms and applications - Reetu; Rahul Jaiswal; Sageer Ahmad; Vijayshwari Mishra; Supriya Pandey; Ashutosh Kumar Yadav; Asad Ali; Rupali Jaiswal; Reema Yadav; Rabiya Ahsan; Tapasya Dwivedi; Sonali; et al. (Next Research, 2026)

Genome wide responses of the water flea, Daphnia carinata, to 6PPD and its oxidation product 6PPD-quinone - Anupama Kumar; Khandaker Asif Ahmed; Thao V. Nguyen; Leon Court; Tom Walsh; Rahul Rane; Gunjan Pandey (Journal of Hazardous Materials, 2026)

Alcohol-Diesel blends fueled Off-Road CI engine Development: Part 3 − Evaluating the influence of Butanol-Diesel blends on Performance, Combustion, and emissions - Hardikk Valera; Rahul Kumar Singh; Shanti Mehra; Jakub Čedík; Martin Pexa; Avinash Kumar Agarwal (Fuel, 2026)

Unlocking the impact of fusarium isolates in infected potato tubers by biochemical profiling, volatile emissions and elemental shifts - Pooja; Prashant Chauhan; Rahul Kumar Tiwari; Anil Kumar Saini; Sushil Ahlawat; Ankit Kumar; Selva Kumar Ramasamy; Abhishek Kumar (Food Chemistry, 2026)

Sustainable Management of Distillery Effluent: Environmental Impacts, Treatment Approaches, and Resource Recovery - Himani Chandel; Himanshu Srivastava; Sibiraj Murugesan; Gaurav Saxena; Geetansh Sharma; Rahul Yadav; Navneet Kumar (Water, Air, & Soil Pollution, 2026)

Spatio - temporal changes in vegetation dynamics under climate variability and water structures in the Arpa river Basin, Central India - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Theoretical and Applied Climatology, 2026)

Insights on Epidemiology, Pathogenomics, and Pathophysiology of Sugarcane Smut Disease Caused by Sporisorium Scitamineum - Kirtika Swaraj; Sayanti Guha Majumdar; Sanjay Kumar Goswami; Ranjit Singh Gujjar; Rajeev Kumar; Dinesh Singh; Aalok Shiv; Anamika Singh; Ashutosh Kumar Mall; Dinesh Singh; Rahul Kumar Tiwari (Sugar Tech, 2026)

A comprehensive review on recent advances in nanomaterial facilitated phytoremediation - Nitesh Kumar; Ruchika Devi; Sushila Devi; Somvir Singh; Anand Singh Bisht; Jitender Kumar; Alka Kumari; Neha Neha; Sanya Chauhan; Arti Sharma; Rahul Kumar (Physiology and Molecular Biology of Plants, 2026)

A Systematic Hybrid Parameterization of SWAT Using SUFI-2 and PSO Algorithms for Historical Flow Simulation of the Brahmaputra River at Majuli: The World’s Largest Inhabited River Island - Biman Kalita; Swapnali Barman; Waikhom Rahul Singh; Rajib Kumar Bhattacharjya (Journal of the Indian Society of Remote Sensing, 2026)

Heavy Metal Accumulation on the Roadside Plant Species with Ethnobotanical Significance and Human Health Risk Assessment: A Case Study of a Major Highway Near the Coal Capital of India - Jitin Rahul; Manish Kumar Jain; Beenu Raj; Mansi Sharma; Shiv Shankar; Aliya Naz; Abhiroop Chowdhury (International Journal of Environmental Research, 2026)

Bioprocess for the Sustainable Production of Prebiotic Mannooligosaccharides Using a Bacterial Mannanase - Monika Rana; Aditya Kumar; Rahul Warmoota; Richa Yadav; Sunena Jassal; Koushik Mazumder; Naveen Gupta (Indian Journal of Microbiology, 2026)

Knowledge‐Guided Machine Learning for Global Change Ecology Research - Zhenong Jin; Licheng Liu; Qi Yang; Xiaowei Jia; Shengli Tao; Yinkun Guo; Rahul Ghosh; Sheng Wang; Qing Zhu; Martin Jung; Kaiyu Guan; Vipin Kumar; et al. (Global Change Biology, 2026)
Global change ecology demands predictive models that reconcile data‐driven learning with mechanistic theory to address complex, interconnected ecosystem challenges. Traditional process‐based approaches struggle with spatiotemporal parameterization, while purely data‐driven machine learning approaches suffer from extrapolation, interpretability, and physical consistency. Knowledge‐guided machine learning (KGML) bridges this divide by systematically integrating ecological principles (e.g., physical first principles, stoichiometry, process understanding, disturbance regimes) into how models are designed, trained, and adjusted to generalize across different ecosystems. The emerging KGML paradigm offers tremendous opportunities to advance the research of global change ecology. This review synthesizes KGML's transformative potential, showcasing its capacity to enhance the prediction of carbon‐water‐nutrient cycles and other ecological processes and lay groundwork for ecological foundation models. Emerging applications in decision support and symbolic regression further illustrate its role in deriving actionable insights and novel theoretical hypotheses. Future directions emphasize adaptive integration of data and knowledge, uncertainty quantification, causal embedding in foundation models, and interdisciplinary collaboration to align KGML innovations with sustainability goals. By uniting ecological theory with AI advances, KGML offers a robust pathway to encompass ecosystem responses to global change, fostering scientific discovery and actionable solutions.

A Validated Transcriptomic NMJ Remodeling Score Reveals Synaptic Dysfunction Independent of Muscle Atrophy after Immobilization in a Microgravity Analog - Rahul Kumar; Andrew Bouras; Karmen Gill; Kyle Sporn; Rohan Phadke; Harlene Kaur; Phani Paladugu; Joshua Ong; Ethan Waisberg; Andrew G. Lee (Neuroinformatics, 2026)

From dimensions to decisions: A Siamese Neural Network for comprehensive analysis of intrinsic dimensionality estimation and dimensionality reduction in hyperspectral imaging - Ashish Kumar; Rahul Dev Garg (Journal of Earth System Science, 2026)

Stability of Organic Carbon in Soil Under Rice and Non-Rice-Based Cropping Systems in Indo-Gangetic Plains of India - Ruma Das; Ankita Trivedi; Rahul Kumar; Shrila Das; Debarup Das; Renu Singh; Kader Ali Sarkar (Agricultural Research, 2026)

Antimicrobial peptide resistance in Salmonella AMR: the role of surface binding and lipopolysaccharide remodelling: one health implications - Rahul Kumar; Akriti Choubey (World Journal of Microbiology and Biotechnology, 2026)

Morphological and molecular identification of pod borer complex infesting chickpea and their associated natural enemies - Doddachowdappa Sagar; Suresh Mahadev Nebapure; Ramya Ramesan Syamala; Rahul Kumar Chandel; Pathour Rajendra Shashank (International Journal of Tropical Insect Science, 2026)

A comprehensive assessment of vegetation and water resource dynamics in Bihar using Sentinel-2 derived NDVI and NDWI indices - Aditya Kumar Thakur; Aman Srivastava; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2026)

A geo-spatial assessment of desert locust risk over India during summer 2020 using GEO-LEO satellite observations and weather forecast - Rahul Nigam; Bimal K. Bhattacharya; Ayan Das; Mukesh Kumar; Prashant Kumar (Remote Sensing Applications: Society and Environment, 2026)

The dual role of ethylene in plant growth and abiotic stress: Mechanisms, regulation, and mitigation through ACC deaminase - Omar A. Hewedy; Mostafa G. Ali; Rasha M. El-Meihy; Islam I. Teiba; Sergio de los Santos-Villalobos; Anshu Rastogi; Honghong Wu; Ahmed M. Hajiyev; Elena V. Zadneprovskaya; Pavel Pashkovskiy; Rahul Kumar; Nabil I. Elsheery; et al. (Plant Science, 2026)

Emerging trends in the development of efficient CAS nucleases for meticulous gene editing in plants - Ranjit Singh Gujjar; Shehla Sherin; Sejal Batra; Arunima Mahto; Sanjay Kumar Goswami; Rajeev Kumar; Rahul Kumar Tiwari; Arjun Singh; Mala Kumari (Plant Science, 2026)

Advances in remote sensing and GIS applications in watershed hydrology: a systematic review - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of Hydrology, 2026)

Enhancing rockfall barrier performance using waste used car tyres: A step towards sustainable civil engineering - Rahul Kumar; M.R. Sadique; Mohd Masroor Alam (Journal of Cleaner Production, 2026)

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

A modified semi-quantitative framework for assessing the impacts and sustainability of iron ore mining in a biodiverse forest - Rahul Kumar; Ashish Kumar; Pranjal Pathak; Biswajit Samanta (Environmental Development, 2026)

Sustainability evaluation of leaching processes for lithium-ion battery recycling using life cycle assessment, costing, and multi-criteria decision analysis - Rahul Rautela; Rohan Wandhre; Hemant Bherwani; Bholu Ram Yadav; Sunil Kumar (Chemical Engineering Journal, 2026)

From Molecular Networks to Medicines: Targeting Complexity in Alzheimer’s Disease (AD) Therapy - Rahul Kumar; Sakshi Patel; Prem Shankar Mishra; Shriyansh Srivastava; Sathvik Belagodu Sridhar; Javedh Shareef; Rakesh Sahu; Mohd Tariq; Jalal Uddin; Abdullatif Bin Muhsinah (Molecular Neurobiology, 2026)

Urdamycin V from Streptomyces sp induces p53 independent apoptosis in cervical cancer cells inconsiderate of HPV status and inhibited growth of gram-positive human pathogens - Vipin Mohan Dan; Rahul Sanawar; Gama M. G. Mohan; Soniya P. Cheriyan; Thankayyan R. Santhosh Kumar (Natural Product Research, 2025)

Harnessing therapeutic potential of bromelain and its nanoformulations: sojourn of pineapple from food to nanomedicine - Rajge Rahul Ravindra; Jaskiran Kaur; Sukriti Vishwas; M.V.N.L. Chaitanya; Narendra Kumar Pandey; Md Sadique Hussain; Poonam Negi; Gaurav Gupta; Popat Kumbhar; John Disouza; Sachin Kumar Singh (DARU Journal of Pharmaceutical Sciences, 2025)

Revolutionising shift in advanced wound healing therapies: nanoengineered herbal gels - Rahul Singh; Jatin Kumar; Satyendra Kumar Rajput; Rohit Bhardwaj; Gnana Ranjan (Natural Product Research, 2025)

Uptake and bioaccumulation of microplastics by plants: Exploring impacts and remediation potential in terrestrial and aquatic environment - Yatta Esther Kallon; Snigdha; Rahul Kumar Sinha; Isha Gupta; Nalok Dutta; Sayan Bhattacharya; Jayanta Kumar Biswas; Prabhakar Sharma (Chemosphere, 2025)

Smart Shields: A conceptual approach to bridging surface functionality and self-healing for next-generation food packaging 4.0 - Umme Habiba; Rahul Singh; Bhawana Jeena; Vinod Kumar; Alexey A. Dmitriev; Bhawna Bisht (Trends in Food Science & Technology, 2025)

Vitamin D supplementation stimulates germ cell proliferation in a restraint-stressed mouse - Rahul Kumar; Lalrawngbawli Annie; Guruswami Gurusubramanian; Ajit Singh; Vikas Kumar Roy (Reproductive Toxicology, 2025)

An uncertainty-aware decision support system: Integrating text narratives and conformal prediction for trustworthy accident code classification - Ashish Kumar; Amrites Senapati; Rahul Upadhyay; Snehamoy Chatterjee; Ashis Bhattacherjee; Biswajit Samanta (Process Safety and Environmental Protection, 2025)

Atmospheric pressure waves and seismic signatures of the Hunga Tonga-Hunga Haʻapai eruption in Antarctica - Vivek Kumar; Rahul Kumar; B. Padma Rao; Anand K. Singh; Shailendra Saini; Vijay K. Soni (Polar Science, 2025)

Valorization of fish wastes and by-products towards green circular bio-economy - Rahul Kumar Rout; S Sivaranjani; Nelluri Puja; Shagolshem Mukta Singh; Tammineni Dushyanth Kumar; Jayasree Joshi T; P․Srinivasa Rao (Next Research, 2025)

Lead exposure during development alters synaptic organization and protein expression in rat hippocampus - Omkar Shirke; Sneha Velu; Satyarth Pandita; Amit Kumar Saha; Rahul Ravindranath Patil; Neha S. Joshi; Periyasamy Govindaraj; Laxmi T. Rao; Yogananda S. Markandeya; Bhupesh Mehta (Journal of Hazardous Materials, 2025)

Anti-nutritional factors: Nutrient interactions, processing interventions, and health aspects - Ankan Kheto; Debojit Baidya Choudhury; Shubhajit Sarkhel; Ayan Sarkar; Yogesh Kumar; Samandeep Kaur; Arun Kumar Gupta; Yograj Bist; Rahul Vashishth; N. Bharath; Rachna Sehrawat; Anupam Roy; et al. (Food Chemistry, 2025)

Fruit seeds as functional ingredients: Gut microbiota interactions and health benefits - Zaryab Shafi; Rahul Singh; Kshirod Kumar Dash; Aamir Hussain Dar (Food and Humanity, 2025)

Potential health benefits of postbiotics and its utilization as natural food preservatives - Rahul Singh; Poornima Singh; Umme Habiba; Vinay Kumar Pandey; Sawinder Kaur; Sarvesh Rustagi (Food and Humanity, 2025)

Retraction notice to ‘Closing the loop: A comprehensive exploration of Taiwan's e-waste to resource conversion journey’ [Environ. Res. 263-Part 3 (2024) 120243] - Anjani R.K. Gollakota; Rahul Mishra; Cheuh-Ling Pai; Chi-Min Shu; Prakash Kumar Sarangi; Pugazhendhi Arivalagan (Environmental Research, 2025)

Interfacial-bulk electrochemistry of sodium-ion storage in multiwalled carbon nanofiber anode with incorporated Mn−N4 single-atoms - Anubha Yadav; Prakash Kumar Pathak; Babasaheb M. Matsagar; Rahul Patil; Norman C.-R. Chen; Rajashri R. Urkude; Masaki Ujihara; Kevin C.-W. Wu; Rahul R. Salunkhe; Saikat Dutta (Chemical Engineering Journal, 2025)

A Critical Review on Abatement of VOCs By Adsorption: Adsorbent Types and Their Characteristics - Kaushal Naresh Gupta; Rahul Kumar; Amit Kumar Thakur (Water, Air, & Soil Pollution, 2025)

Restoration of urban degraded soil in the dry tropics: role of multipurpose shrub plants - Amrita Kumari; Priyanka Soni; Fahami Zaya; Rahul Kumar; Riya Gupta; Nandita Ghoshal (Tropical Ecology, 2025)

Fine mapping, introgression, and KASP marker development for powdery mildew resistance in watermelon using an interspecific RIL population (Citrullus mucosospermus × C. lanatus) - Rahul Kumar; Jennifer Ikerd; Raghupathy Karthikeyan; Chandrasekar Kousik (Theoretical and Applied Genetics, 2025)
Key message A major QTL conferring powdery mildew resistance was fine mapped to a 54.8 kb region on chromosome 2 using an interspecific RIL population ( Citrullus mucosospermus × Citrullus lanatus ). Four co-segregating KASP markers were developed and validated across multiple populations, demonstrating their utility for marker-assisted selection. Abstract Powdery mildew, caused by Podosphaera xanthii , is a major fungal disease that significantly affects watermelon production worldwide. Developing resistant cultivars through marker-assisted selection (MAS) offers an effective and sustainable strategy for disease management. In this study, a 54,772 bp quantitative trait locus (QTL) associated with powdery mildew resistance was mapped to chromosome 2 (30,111,475–30,166,247 bp) using an F 11 recombinant inbred line (RIL) population derived from an interspecific cross between the resistant C. mucosospermus line USVL531-MDR and the susceptible C. lanatus line USVL677-PMS. Genetic analysis revealed that resistance is controlled by a single dominant gene, supported by a 3:1 segregation ratio observed in F 2 populations. The mapped region harbored three lipoxygenase ( LOX ) genes and one 50S ribosomal protein L27-like gene. Four KASP markers were developed from SNPs located within four putative genes in the QTL region and were validated across multiple segregating populations, including the RIL (USVL531-MDR × USVL677-PMS) and two F 2 populations (USVL531-MDR × ’Sugar Baby’ and PI 560003 × USVL677-PMS). These markers accurately differentiated resistant and susceptible individuals ( R 2 = 0.68–0.82) and exhibited 100% co-segregation with powdery mildew resistance in the RIL and two F 2 populations, demonstrating their utility for MAS. The identified QTL and validated KASP markers will facilitate MAS for powdery mildew resistance breeding and enable future gene cloning work.

Insights into Pinus species: phytochemistry, pharmacology and industrial potential of Indian Pinus species - Rohit Sharma; Rahul Sharma; Varun Thakur; Aditi Randhawa; Rajneesh Kumar; Bhupender Dutt; Ashun Chaudhary; Sunil Kumar (Phytochemistry Reviews, 2025)

Morin hydrate treatment minimizes Di(2-ethylhexyl) phthalate-induced uterine fibrosis, oxidative stress, and apoptosis in mice - Vikash Kumar; Rahul Kumar; Guruswami Gurusubramanian; Saurabh Singh Rathore; Vikas Kumar Roy (Molecular Biology Reports, 2025)

Artemisinin’s molecular symphony: illuminating pathways for cancer therapy - Sandeep Kumar Jhade; Karthik Kalidoss; Poonam Kumari Pathak; Rahul Shrivastava (Molecular Biology Reports, 2025)

Diversity and Functional Characterization of Endophytes in Two Contrasting Cultivars of Ocimum sanctum: Insights from Culture-Based and Metagenomic Approaches - Rahul Kumar Gupta; Shiwangi Singh; C S Chanotiya; Kapil Dev; Prabodh Kumar Trivedi; Akanksha Singh (Journal of Plant Growth Regulation, 2025)

Deciphering pathological and population dynamics in Tilletia indica of Karnal bunt of wheat - Sangale Smita; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Jitender Kumar; Poulami Basak; Natasha Kashyap; Rahul Patidar; Muthyala Mahendra; Sri Ananth Kurella; Kartiki Sharma; Sundeep Kumar; Mahender Singh Saharan (Indian Phytopathology, 2025)

SARS-CoV-2 pathophysiology and post-vaccination severity: a systematic review - Vanshika Rustagi; Shradheya R. R. Gupta; Chandni Talwar; Archana Singh; Zhen-Zhu Xiao; Rahul Jamwal; Kiran Bala; Akash Kumar Bhaskar; Shekhar Nagar; Indrakant K. Singh (Immunologic Research, 2025)

Integrating multi-traits mixed model and multivariate statistics for genetic diversity assessment in mungbean (Vigna radiata L.) - Vijay Kamal Meena; Vijay Singh Meena; Shahil Kumar; Harshvardhan Singh Shekhawat; Kapil Choudhary; Jitendar Kumar Sharma; Lekha Meal; Rahul Bhardwaj; Sitaram Kumawat (Genetic Resources and Crop Evolution, 2025)

Enhanced Biodegradation and Detoxification of Diesel in Soil and Water Using a Novel Mixed Bacterial Culture - Rahul Kumar; Mahuya De (Bulletin of Environmental Contamination and Toxicology, 2025)

Prediction of rice yield using sensors mounted on unmanned aerial vehicle - Rahul Tripathi; Bismay Ranjan Tripathy; Shiv Sundar Jena; Chinmaya Kumar Swain; Sangita Mohanty; R. N. Sahoo; A. K. Nayak (Agricultural Research, 2025)

Soil organic carbon dynamics in dry tropics: impact of tree plantations on restoration of urban degraded lands - Rahul Kumar; Riya Gupta; Priyanka Soni; Fahami Zaya; Amrita Kumari; Nidhi Singh; Nandita Ghoshal (Environmental Sustainability, 2025)

Mucoadhesive Carbohydrate-Based Polymeric Nanocapsule Loaded with Palbociclib for Enhanced GIT Retention and In Vitro Anticancer Efficacy in MDA-MB-231 Cells - Pooja Khade; Ujala Gupta; Rahul Kumar; Neelesh Kumar Mehra; Pankaj Kumar Singh (AAPS PharmSciTech, 2025)

Sustainable computing using machine learning and copula-based modelling for drought classification from meteorological features - Sanjeev Kumar; Karandeep Saluja; Dilkeshwar Pandey; Saurav Chandra; Rahul Silori; Balendu Shekher Giri (Journal of Earth System Science, 2025)

Mapping agro-potential through evaluating soil suitability and crop productivity using geospatial techniques - Rituparna Saikia; Dilip Kumar Patgiri; Bipul Deka; Prem Kumar Bharteey; Suman Dutta; Ramani Kanta Thakuria; Marami Dutta; Sanjib Ranjan Borah; Rahul Sadhukhan; Ranabir Chakraborty; Malini Roy Choudhury; Parag Saikia; et al. (Environmental Monitoring and Assessment, 2025)

A comprehensive safety assessment of algae protein from Picochlorum for human consumption - Manish R. Shukla; Tomal Dattaroy; Ashish Waghmare; Bhaskar Bhadra; Chitranshu Kumar; Debanjan Sanyal; Jayesh Sakariya; Kshipra Gautam; Mahadev S. Gaikwad; Manish Shukla; Meenakshi Chelliah; Meghna Rajvanshi; et al. (Regulatory Toxicology and Pharmacology, 2025)

Genome sequence of Bipolaris maydis inciting maydis leaf blight provides insights into genome architecture and putative effector repertoire - Poulami Basak; Malkhan Singh Gurjar; Tej Pratap Jitender Kumar; Natasha Kashyap; Sri Ananth Kurella; Muthyala Mahendra; Rahul Patidar; Sangale Smita; Kartiki Sharma; Robin Gogoi (Physiological and Molecular Plant Pathology, 2025)

Precision health monitoring in spaceflight with integration of lower body negative pressure and advanced large language model artificial intelligence - Rahul Kumar; Ethan Waisberg; Joshua Ong; Phani Paladugu; Kyle Sporn; Karsten Chima; Dylan Amiri; Nasif Zaman; Alireza Tavakkoli (Life Sciences in Space Research, 2025)

Shared mechanisms in neuromyelitis optica spectrum disorder and spaceflight-associated neuro-ocular syndrome: Insights into central nervous system fluid dynamics, glymphatic function, and astrocyte dysregulation - Phani Paladugu; Rahul Kumar; Kyle Sporn; Joshua Ong; Amy Song; Tejas Sekhar; Chirag Gowda; Nicole Davidoff; Samuel Shin; Andrew G. Lee (Life Sciences in Space Research, 2025)

Seasonal dynamics of suspended sediment transport and controlling factors from monthly water-sediment hysteresis relationship in the tropical rivers of the Western Ghat - Shantamoy Guha; Ajit Singh; Rahul Kumar Kaushal (Journal of Hydrology, 2025)

Galactinol synthase 1, AtGolS1, affects arsenate tolerance by modulating phosphate homeostasis in sensitive ecotype Slavi-1 of Arabidopsis - Avriti Ranjan; Swati Gautam; Rahul Michael; Prabodh Kumar Trivedi (Journal of Hazardous Materials, 2025)

Soil surface management for enhanced morpho-physiological traits, yield and water use efficiency of chickpea: A sustainable and climate resilient strategy - Anita Kumawat; I. Rashmi; Shakir Ali; Kuldeep Kumar; Ashok Kumar; Devideen Yadav; M. Madhu; Rahul Sadhukhan; R.A. Jat; G.L. Meena; G.K. Sharma; S. Kala (Field Crops Research, 2025)

Synergetic catalysis methods for sustainable wastewater treatment - Manish Kumar; Abhishek Shukla; Neha Thakur; Rahul Vaish (Environmental Research, 2025)

Economic analysis of free & subsidized power supply versus solar PV cell subsidy towards sustainable agriculture in India - An external cost approach and policy implications - S Shri Ram Kumar; S Rahul Bharath; Srinivasan Periaswamy (Energy Policy, 2025)

Pathological alterations and molecular-immunohistochemical detection of bovine respiratory syncytial virus in dairy calves of Himachal Pradesh, India: a first study - Rahul Singh; Rajendra Damu Patil; Priyanka Choudhary; S. D. Vinay Kumar; Ishita Gupta; Vidya Singh; Rakesh Kumar; Rajesh Kumar Asrani; Vipan Kumar Gupta (Tropical Animal Health and Production, 2025)

Improving drought tolerance in rice seedlings through melatonin-induced alterations in root architecture, photosynthetic and antioxidant enzymes - Milan Kumar Lal; Ujala Rashmi Sahoo; Laxmipriya Behera; Bandana Mohapatra; Awadhesh Kumar; Rupak Jena; Koushik Chakraborty; Rahul Kumar Tiwari; Ravinder Kumar; M. J. Baig (Physiology and Molecular Biology of Plants, 2025)

Cannabichromene, a key non-psychotropic phytocannabinoid in treatment of major depressive disorder: in silico and in vivo explorations - Abhishek Sharma; Rahul Singh; Tarun Virmani; Neeraj Kumar Chouhan; Garima Kapoor; Girish Kumar; Rubina Bhutani; Neha Rana; Shivkant Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Antioxidant Defence Mechanism of Potato (Solanum tuberosum) by Regulation of Physiological and Biochemical Response Under Potato Virus Y Necrotic Strain (PVYNTN) Infection - Ravinder Kumar; Milan Kumar Lal; Rahul Kumar Tiwari; Dinesh Kumar; Vinay Sagar; Rupak Jena; Rakesh Kumar; Gyanendra Singh; Brajesh Singh (Journal of Plant Growth Regulation, 2025)

The multifaceted regulation of white adipose tissue browning and their therapeutic potential - Abhishek Satheesan; Janardanan Kumar; Kakithakara Vajravelu Leela; Rahul Harikumar Lathakumari; Matcha Angelin; Ria Murugesan; Venkata Chaithanya (Journal of Physiology and Biochemistry, 2025)

Advancing agriculture through speed breeding: protocols, integration, achievements and challenges - Rahul Pathania; Sanjeev Kumar; Amanpreet Singh Chahal; Ajay Singh; Abhishek Kaplex; Akanksha Sharma (Euphytica, 2025)

A sustainable machining process to enhance the performance of the turning process using nanofluids assisted by minimum quantity lubrication - Lokesh Kumar; Rahul Goyal; Ashish Goyal (Environmental Science and Pollution Research, 2025)

Exogenous melatonin improves blastocyst developmental competence and levels of antioxidants in indigenous donor cattle under heat stress - Anupama Solanki; Anand Kumar Pandey; Hitesh Jangra; Pradeep Saini; Sandeep Kumar; Ramakant Kaushik; Meenakshi Virmani; Rajesh Kumar; Rahul Verma; Yogesh Bangar (Theriogenology, 2025)

Three-component models for the detection of phytoplankton size classes in the Indian sector of the Southern Ocean: Insights into climate-driven community shifts - Sudarsana Rao Pandi; Sarat Chandra Tripathy; Carlos Rafael B. Mendes; R. Chandrasekhar Naik; Sunil Kumar Padhi; Aneesh A. Lotliker; Rahul Mohan (Journal of Marine Systems, 2025)

Retraction notice to “Deep insights into kinetics, optimization and thermodynamic estimates of methylene blue adsorption from aqueous solution onto coffee husk (Coffee arabica) activated carbon” [Environ. Res. 236-P2 (2023) 116735] - Prabu Deivasigamani; P. Senthil Kumar; Sathish Sundaraman; Michael Rahul Soosai; A. Annam Renita; Karthikeyan M; Nessipkhan Bektenov; Omirserik Baigenzhenov; Venkatesan D; Aravind Kumar J (Environmental Research, 2025)

Metals in the human liver: An underappreciated risk factor of hepatic insulin resistance and associated pathophysiology - Rahul Kumar; Ashwin Chinala; Dhruv Grandhe; S. Joseph Endicott; Marcus A. Garcia; Matthew J. Campen; Rama R. Gullapalli (Environmental Pollution, 2025)

Homemade disposable paper electrode modified with amine-functionalised carbon dot and multi-walled carbon nanotube nanocomposite for electrochemical biosensing of E. coli O157:H7 - Pravat Kumar Sahu; Asha Ramesh; Karri Trinadha Rao; Rahul Gangwar; Siva Rama Krishna Vanjari; Subrahmanyam Challapalli (Chemical Engineering Journal, 2025)

Development of Or-gene-based co-dominant markers and their utilization in marker-assisted breeding for ß-carotene biofortification in different maturity groups of cauliflower - Shrawan Singh; Vinay Verma; Bhagchand Shivran; Rahul Kumar Meena; Anamika Chandel; Sandhya Saroha; Navinder Saini (Theoretical and Applied Genetics, 2025)

Unlocking the Power of Xylooligosaccharides as Nutraceuticals: Sources, Production Strategies, and Applications - Anupama Sharma; Garima Dulgach; Rahul Warmoota; Kumud Sharma; Aditya Kumar; Phalguni Gupta; Naveen Gupta (Sugar Tech, 2025)

Widespread Occurrence of Colletotrichum falcatum Pathotype CF13 in the Subtropical India Dictates Continuous Pathogenic Virulence and Severe Sugarcane Crop Destructions - R. Viswanathan; Sujeet Pratap Singh; R. Selvakumar; Chandramani Raj; Dinesh Singh; Y. P. Bharti; M. L. Chhabra; Anuradha Sharma; Md. Minnatullah; Rakesh Mehra; Harvinder Singh Yadav; Sanjay Kumar Goswami; et al. (Sugar Tech, 2025)

Preclinical evaluation of sodium copper chlorophyllin: safety, pharmacokinetics, and therapeutic potential in breast cancer chemotherapy and cyclophosphamide-induced bladder toxicity - Neha Ramani; Raghavendra S. Patwardhan; Rahul Checker; Babita Singh; Shruti Morjaria; Binita K. Kumar; Murari Gurjar; Vikram Gota; Deepak Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Modeling of slope stability for predicting classification steps and effective performance integrating supervised machine learning approaches - Furquan Ahmad; Rahul kumar; Divesh Ranjan Kumar; Pijush Samui; Warit Wipulanusat (Modeling Earth Systems and Environment, 2025)

Devastating landslide incident in Ramban District of Jammu and Kashmir (J&K), India on April 20, 2025: a combined effect of intense rainfall, anthropogenic factors, flash floods, and geomorphology - Prateek Sharma; Rahul Kumar Verma; Rajesh Singh (Landslides, 2025)

Production of lutein from various microalgae species using different cultivation methods: Structural characterization and assessment of functional integrity - Udaypal; Rahul Kumar Goswami; Pradeep Verma (Journal of Applied Phycology, 2025)

Development and experimental investigations on pebbles and erythritol-based energy storage unit for indoor solar cooking - Rahul Khatri; Rahul Goyal; Ravi Kumar Sharma (Clean Technologies and Environmental Policy, 2025)

Green synthesis of iron oxide nanoparticles from Calotropis procera latex: an eco-friendly catalyst for biodiesel production from Calotropis procera seed oil - Surinder Kumar; Shilpa Kumari; Asha Kumari; Neha Kondal; Prashant Choudhary; Vikas Dhiman; Rahul Sharma (Clean Technologies and Environmental Policy, 2025)

Lead and arsenic toxicity: emerging mechanisms, immunotoxic effects, and future research perspectives - Rahul Thakur; Sukhpal Singh; Aman Chauhan; Pawan Kumar; Reena V. Saini; Adesh K. Saini (BioMetals, 2025)

Effects of Mulching On Soil, Growth, and Biochemical Traits of Strawberry (Fragaria × ananassa) Under Protected Cultivation - Shailaja Punetha; Pooja Oli; Nidhi Joshi; Supriya Gupta; Prabhat Kumar; Manpreet Singh Preet; Vineet Kaswan; Rahul Dev; A. K. Goswami; Anjali Jingar; Daya Shankar Mishra; Prakashbhai Ravat; et al. (Applied Fruit Science, 2025)

Paddy cultivar diversification for management of soil methane emissions and sustainable rice production - Jay Shankar Singh; Shashank Tiwari; Prateek Singh; Rahul Kumar Nigam; Irina K. Kravchenko (Environmental Sustainability, 2025)

Characterization of new natural cellulosic fiber from Calamus andamanicus Kurz in special reference to its conservation - Roni Saha; Rahul Deb Barman; Amal Kumar Mondal (Vegetos, 2025)

Development of thymol-enriched basil oil nanoemulsions for management of tomato bacterial pathogens - Rahul Patidar; Malkhan Singh Gurjar; Ganesan Prakash; Kajal Kumar Biswas; Lokesh Babu P; Rashid Pervez; Parshant Kaushik; Navin Chandra Gupta; Dinesh Singh (Physiological and Molecular Plant Pathology, 2025)

The role of atmospheric and oceanic factors on the record low Antarctic sea ice extent of 2023 - M. Swathi; Avinash Kumar; Juhi Yadav; Rahul Mohan (Global and Planetary Change, 2025)

A sustainable technology for enhancing the oxidative stability of edible oils using jackfruit (Artocarpus heterophyllus lam.) peel extract as a natural antioxidant - Rupali Koundal; Anil Kumar Chauhan; Rahul Das (Food Chemistry, 2025)

Supplemental effect of metallic nanoparticles on cryopreserved semen quality, lipid peroxidation, sperm head ultrastructure and field fertility levels in crossbred (Hampshire x Niang Megha) boars - Manoj Kumar Kalita; Prithviraj Mazumdar Baruah; Kutubuddin Ahmed; Sudip Sinha; Shantanu Tamuly; Sourabh Deori; Rahul Katiyar; Sayed Nabil Abedin; Prerona Patowary; Raju Dewry; Jitumoni Das; Biplab Sarkar; et al. (Cryobiology, 2025)

Factors Influencing Farmers to Adopt Potato Contract Farming in Gujarat - Sathish Kumar M.; Prity Kumari; Rahul Singh Gautam; Y. A. Lad (Potato Research, 2025)

Retraction Note: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2025)

Retraction Note: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2025)

An Economical Industrially Feasible Approach for Denim Biobleaching: Reusing of Laccase and Mediator for Multiple Cycles - Sunena Jassal; Rahul Warmoota; Anupama Sharma; Sarita Sheoran; Deepak Kumar; Naveen Gupta (Indian Journal of Microbiology, 2025)

Enhancing solar radiation forecasting accuracy with a hybrid SA-Bi-LSTM-Bi-GRU model - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav; Rahul Gupta (Earth Science Informatics, 2025)

Observations on deterministic seismic hazard analysis for the study region, Gujarat - Rahul Kumar; Jitesh T. Chavda (Arabian Journal of Geosciences, 2025)

Spatiotemporal analysis of NO2 trends over major air pollution hotspots in India using Sentinel-5P - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Journal of Earth System Science, 2025)

Elucidating the impact of persistent organic pollutants on male reproductive health and testicular structure - Shubhendu Shekhar Ray; Priya Gupta; Archisman Mahapatra; Anjali Suman; Rahul Kumar Singh (Toxicology Letters, 2025)

Dynamics of cytosolic and organellar gene transcripts in wild and cultivated genotypes of pigeon pea due to simulated herbivory - Swapnilkumar Meshram; Debajit Das; Sanjay Singh; Mamta Bhattacharjee; Rahul Ishwar Patil; S. Arunima; Prakash Jyoti Kalita; Jagdish Jaba; Bidyut Kumar Sarmah; Sumita Acharjee (Plant Science, 2025)

Leveraging lower body negative pressure for enhanced outcomes in orthopedic arthroplasty—Insights from NASA’s bone health research - Phani Paladugu; Rahul Kumar; Tamer Hage; Swapna Vaja; Tejas Sekhar; Samuel Weisberg; Kyle Sporn; Ethan Waisberg; Joshua Ong; AmarS. Vadhera; Mouayad Masalkhi; Ryung Lee; et al. (Life Sciences in Space Research, 2025)

Radiocarbon in soil organic carbon and soil pore space CO2 in sub-humid to semi-arid regions of western India: Implications to tropical soil carbon dynamics - Ranjan Kumar Mohanty; Rahul Kumar Agrawal; A. Shivam; Amzad Hussain Laskar (CATENA, 2025)

Gold nanocluster-based biosensing for rapid detection of carbapenem-resistant organisms in bloodstream infections - Rahul Harikumar Lathakumari; Leela Kakithakara Vajravelu; Poornima Baskar Vimala; Vishnu Priya Panneerselvam; Dakshina M. Nair; Jayaprakash Thulukanam; Ashwin Kumar Narasimhan (World Journal of Microbiology and Biotechnology, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Soil carbon and nitrogen dynamics under conservation agriculture components for direct seeded rice-green gram system - Gayatri Patra; Dibyendu Chatterjee; Khitish Chandra Moharana; Bitish Kumar Nayak; Rahul Tripathi; Mohammad Shahid; Dipti Ranjan Pani; Saikat Ranjan Das; Bipin Bihari Panda; Sushmita Munda; Upendra Kumar; Abhijit Pradhan; et al. (Plant and Soil, 2025)

Alteration of Source-Sink Dynamics and Antioxidant Responses in Potato (Solanum tuberosum L.) Under Potato Leafroll Virus (PLRV) Infection - Ravinder Kumar; Milan Kumar Lal; Rahul Kumar Tiwari; Dinesh Kumar; Vinay Sagar; Rakesh Kumar; Anirban Roy; Vaibhav Kumar Singh; Gyanendra Singh; Brajesh Singh (Journal of Plant Growth Regulation, 2025)

Gender differences in expression and localization of the apelin receptor in mice skin - Milirani Das; Rahul Kumar; Vikash Kumar; Guruswami Gurusubramanian; Vikas Kumar Roy (Journal of Molecular Histology, 2025)

Comprehensive 8E and 2C Analysis of a Modified Semi-Cylindrical Solar Still with Sensible Heat Storage Materials - Kshitij Yugbodh; Rahul Agrawal; Ekta Jain; Kennedy Sarangapani; Sanjay Kumar Singh; Ruchin Kacker (International Journal of Environmental Research, 2025)

Expanding pathogenic diversity in bacterial wilt- insights beyond Ralstonia solanacearum species complex - Manisha Saini; Meenu Gupta; Pankaj Kumar; Rahul Saini (Australasian Plant Pathology, 2025)

A Review on Novel Formulations and Delivery Systems of Botanical Insecticides for Enhanced Efficacy - Rahul Kumar; Rupinder Kaur; Aditya Singh Ranout; Gireesh Nadda (Neotropical Entomology, 2025)

Prediction of Cerebrospinal Fluid (CSF) Pressure with Generative Adversarial Network Synthetic Plasma-CSF Biomarker Pairing - Phani Paladugu; Rahul Kumar; Jahnavi Yelamanchi; Ethan Waisberg; Joshua Ong; Mouayad Masalkhi; Chirag Gowda; Ryung Lee; Dylan Amiri; Ram Jagadeesan; Nasif Zaman; Alireza Tavakkoli; et al. (Neuroinformatics, 2025)

Exploring Protein Aggregation in Biological Products: From Mechanistic Understanding to Practical Solutions - Satish Rojekar; Amol D. Gholap; Krishna Jadhav; Ganesh Shevalkar; Vrashabh V. Sugandhi; Rohan Pai; Kinjal Parikh; Mahendra Kumar Prajapati; Nimeet Desai; Lalitkumar K. Vora; Rahul G. Ingle; Keshav Raj Paudel (AAPS PharmSciTech, 2025)
Proteins are vital for the regulation of several cellular functions, including the synthesis of structural components. The change in environmental conditions will impact conformational stability and result in aggregation. Protein aggregation involves different states of proteins, like nonnative, unfolded, and native states, which make them complex processes. The proper understanding of protein aggregation pathways involving the role of thermodynamically unfavoured lag phase, soluble protofibrils triggered polymerization through an exponential phase, and depleted free monomers owing to the saturation phase resulted in the leveling off of the polymerization process. The aggregated therapeutic proteins can induce deleterious immune responses in patients, and control of the aggregation is essential for better therapeutic protein stability and targeting with the help of stable protein structures and function. Protein–protein interactions (PPIs) are important for protein stability, aggregation rate, and solubility, while advanced computational and biophysical methods have been developed to characterize therapeutic protein aggregation better. Hence, an effective strategy for controlling, monitoring, and reproducing protein aggregation propensities of the polypeptide chains is required. An in-depth understanding of protein aggregation mechanisms, characterization, and combat strategies will counter the issues of protein aggregation. It will also reduce the cost of the product, time constraints, stable & effective product availability, and potential immunogenicity. Graphical Abstract

Artificial Intelligent and Internet of Things framework for sustainable hazardous waste management in hospitals - Amit Krishan Kumar; Yasir Ali; Rahul R. Kumar; Mansour H. Assaf; Sadia Ilyas (Waste Management, 2025)

Rapid changes in warm and cold extremes in recent decades and their future projections for India - Rahul Kumar; G.S. Gopikrishnan; Jayanarayanan Kuttippurath (Journal of Environmental Management, 2025)

Genotype × environment interaction, marker-trait association, and SSR validation for grain micronutrient content and yield in wheat (Triticum aestivum L.) - Jitendra Kumar; Pradeep Singh; Shoeb Ahmed; Nitin Garg; Himanshu Sharma; Ritisha Singh; Rahul Kumar; Imran Sheikh; Joy Roy (Journal of Cereal Science, 2025)

Corrigendum to “Reconstructing the geological and geomorphological history of Morella Crater, Mars” [Geomorphology 479 (2025) 109740] - P.B. Hiral; S. Anbazhagan; S. Rahul; Shania James; T. Sadeeda Marjan; Devika Padmakumar; J. Aswathi; K.S. Sharini; Alka Rani; K.S. Sajinkumar; Rajiv R. Bharti; V.J. Rajesh; et al. (Geomorphology, 2025)

Production of α-tocopherol biomolecules using various cultivation strategies of diverse microalgal species: Purification, characterization and assessment of antioxidant properties - Udaypal; Rahul Kumar Goswami; Pradeep Verma (Biocatalysis and Agricultural Biotechnology, 2025)

Understanding the genetic epidemiology of hereditary breast cancer in India using whole genome data from 1029 healthy individuals - Aastha Vatsyayan; Prerika Mathur; Rahul C. Bhoyar; Mohamed Imran; Vigneshwar Senthivel; Mohit Kumar Divakar; Anushree Mishra; Bani Jolly; Sridhar Sivasubbu; Vinod Scaria (Cancer Causes & Control, 2025)

Comprehensive analysis of line-of-sight displacement and periodicity in ascending and descending pass time-series ground deformation in the mining-affected East Jharia Coalfield - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2025)

Understanding the prevalence of germline oncogenic biomarker variants across the Indian population - Aastha Vatsyayan; Rahul C. Bhoyar; Mohamed Imran; Vigneshwar Senthivel; Mohit Kumar Divakar; Anushree Mishra; Bani Jolly; Sridhar Sivasubbu; Vinod Scaria (Journal of Genetics, 2025)

Slope stability assessment of the section along Balipara–Charduar–Tawang Road, Arunachal Pradesh, India - Deepak Kumar Singh; Amit Kumar Verma; Rahul Kumar Verma; T N Singh (Journal of Earth System Science, 2025)

An Overview of the Design and Realized Performance of Ocean Colour Monitor (OCM-3) Payload On-Board the Oceansat-3 (EOS-06) Mission - Vishnukumar D. Patel; Manoj Kumar; Pradeep Soni; Rahul Dev; Dheeraj Adlakha; Moumita Dutta; Dhrupesh S. Shah; Manoj P. Detroja; Harish Seth; Ashok Kumar; Jimit Gadhia; P. Nandha Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2025)

A framework for sustainable urban settlement planning: Integrating geographic information system and multi-criteria decision analysis - S. K. Ray; A. Teja; S. Chaudhary; M. H. Kumar; R. Rahul; K. Rammohan; D. Himabindu (Environment, Development and Sustainability, 2025)

Morphological and biochemical characterization of salt stress tolerant and sensitive genotypes of horsegram [Macrotyloma uniflorum (Lam.) Verdc.] - Vasudha Maurya; Narayan Singh; Ashutosh Sharma; Rahul Kumar (Biologia, 2025)

Use of coal ash from thermal power plant in Vertisol of central India: II. Impact on soybean – Wheat productivity, elemental uptake and crop quality - Jayanta Kumar Saha; M.Vassanda Coumar; Sangeeta Lenka; Abhijit Sarkar; Rahul Kumawat; Seema Jatav; D.K. Yadav; M. Saha; Nisha Sahu; T. Adhikari; Ajay Srivastava; B.P. Meena; et al. (Total Environment Advances, 2025)

Use of coal ash from thermal power plant in Vertisol of central India: I. Impact on soil quality - Jayanta Kumar Saha; M. Vassanda Coumar; Sangeeta Lenka; Abhijit Sarkar; Rahul Kumawat; Priyanka Jadon; Seema Jatav; D.K. Yadav; M. Saha; Nisha Sahu; Asit Mandal; T. Adhikari; et al. (Total Environment Advances, 2025)

The built environment and adverse cardiovascular events in US veterans with cardiovascular disease - Skanda Moorthy; Zhuo Chen; Tong Zhang; Sai Rahul Ponnana; Santosh Kumar Sirasapalli; Kanimozhi Shivanantham; Haitham Khraishah; Jean-Eudes Dazard; Sadeer G. Al-Kindi; Salil V. Deo; Sanjay Rajagopalan (Science of The Total Environment, 2025)

Paleomonsoon variability during the past seven centuries: Insights from a northwest Himalayan lake - Sreya Sengupta; Anil Kumar Gupta; Pankaj Kumar; Prasanta Sanyal; Manoj Kumar Jaiswal; Abhayanand Singh Maurya; Arun Kaushik; Rahul Pawar; Rajveer Sharma; Nitish Kumar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluation of some plant products against Trogoderma granarium everts and Rhyzopertha dominica fabricius in pearl millet and their effects on nutritional composition and organoleptic characteristics - Sudhir Dayal Yadav; Shalini Pandey; Ankur Tripathi; Mujahid Khan; Prashant Sahni; Rahul Bhardwaj; Manish Kumar; Ram Singh (Journal of Stored Products Research, 2025)

Seasonality in negative removal of pharmaceutical and personal care products at the Himalayan foothills wastewater treatment plants - Rahul Silori; Durga Madhab Mahapatra; Syed Mohammad Tauseef; Pinakshi Biswas; Bhanu Prakash Vellanki; Ritusmita Goswami; Mats Leifels; Abrahan Mora; Jürgen Mahlknecht; Manish Kumar (Journal of Environmental Chemical Engineering, 2025)

Reconstructing the geological and geomorphological history of Morella Crater, Mars - P.B. Hiral; S. Anbazhagan; S. Rahul; Shania James; T. Sadeeda Marjan; Devika Padmakumar; J. Aswathi; K.S. Sharini; Alka Rani; K.S. Sajinkumar; Rajiv R. Bharti; V.J. Rajesh; et al. (Geomorphology, 2025)

Environmental magnetism linked to weathering processes: A study on surface soils from an East Antarctic oasis - Adyasha Rath; G.S. Joju; Anish Kumar Warrier; Marcos A.E. Chaparro; Firoz Badesab; Mamilla Venkateshwarlu; B.S. Mahesh; Rahul Mohan (Geoderma Regional, 2025)

Potato Growers: A Linear Discriminant Analysis - Ganeshkumar D. Rede; Vaishnavi G. Magar; Sathish Kumar M; Rahul Singh Gautam (Potato Research, 2025)

Geostatistics-Based Understanding of Temporal Changes In Spatial Distribution of Soil Fertility Parameters In An Intensively Cultivated Area of North India - Sanjib Kumar Behera; Arvind Kumar Shukla; Rohtas Kumar; Rahul Mishra; Vimal Shukla; Harendra Yadav; Siba Prasad Datta (Journal of Soil Science and Plant Nutrition, 2025)

State-of-the-Art Status of Google Earth Engine (GEE) Application in Land and Water Resource Management: A Scientometric Analysis - Nishtha Sharnagat; Anupam Kumar Nema; Prabhash Kumar Mishra; Nitesh Patidar; Rahul Kumar; Ashwini Suryawanshi; Lakey Radha (Journal of Geovisualization and Spatial Analysis, 2025)

Colletotrichum falcatum Proteome Unraveled the Promising Functions of Myosin-1 and Polyketide Synthase Proteins in Instigating the Pathogen Virulence - Sejal Batra; Ranjit Singh Gujjar; Rajeev Kumar; Sanjay Kumar Goswami; Rahul Kumar Tiwari; Appunu Chinnaswamy; Ramaswamy Manimekalai; Valarmathi Ramanathan; Sanjeev Kumar (Journal of Crop Health, 2025)

Biotic Stress Alleviation in Plant Using Rhizobacteria: An Overview of Mechanism of Action, Antimicrobial Compounds Production, (Nano) Formulations and Employment Methods - Anuj Rana; Annu Rani; KR. Nayana; Sumit Deswal; Arvind Pratap Singh; Sravendra Rana; Madhvi Chahar; Namita Singh; Rahul Kumar Dhaka (Indian Journal of Microbiology, 2025)

Development of breeding lines with multiple stress tolerance to cold, drought, and high-temperature stress in rice (Oryza sativa L.) - Rahul Priyadarshi; Shailesh Yadav; Mamatha Pettem; Challa Venkateshwarlu; K. J. Pranesh; Vikas K. Singh; Arvind Kumar (Euphytica, 2025)

Intelligent growth of holy basil: an iot-based hydroponics system empowered by the CRL-SHS Algorithm - T. Kumaragurubaran; Rahul Chiranjeevi; Elangovan D; Deepak Kumar K (Earth Science Informatics, 2025)

Soil Attributes Modulate the Fungal Population and Diversity of Phytopathogens and Biocontrol Agents - Isha Verma; Sumit K. Soni; Rahul Kumar; Bhavya Priyadarshini Mishra; Udit Yadav; Anshu anshu; Touseef Fatima; Sanjeeva Nayaka; Mariya Naseem; Suchi Srivastava; Poonam C. Singh (Agricultural Research, 2025)

Land subsidence dynamics and its structural impact assessment over East Jharia, Jharkhand, India - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2025)

Molecular identification and management of Ralstonia pseudosolanacearum (Phylotype I) causing bacterial wilt of tomato using copper oxide nanoparticles in Himachal Pradesh, India - Manisha Saini; Meenu Gupta; Vinay Sagar; Anjali Chauhan; Rahul Saini; Gaurav Kumar (Crop Protection, 2025)

Urolithin improves α-synuclein aggregation and DNMT1 expression in rotenone model of Parkinson’s disease - Ankita Devi; Sharon Munagalasetty; Pardeep Kumar; Rahul Kumar; Vasundhra Bhandari; Manoj P. Dandekar (NeuroToxicology, 2025)

Advancing sustainability through modified atmosphere packaging (MAP) for fresh food preservation: A critical review - Umme Habiba; Ananya Bajpai; Zaryab Shafi; Vinay Kumar Pandey; Rahul Singh (Journal of Stored Products Research, 2025)

Production of Indian cultured butter (makkhan) from buffalo creams with varied fat globule size: Process improvement and quality assessment - Kumaresh Halder; Jatindra K. Sahu; Satya Narayan Naik; Anil Kumar; Rahul Yadav; Lopamudra Haldar; Surajit Mandal; Anindita Debnath (International Dairy Journal, 2025)

Encapsulated kinnow peel powder using freeze drying: Effect of maltodextrin and gum arabic concentrations on physiochemical, functional and thermal properties - Masud Alam; Saurabh Sid; Souvik Giri; Rahul Das; Anand Kishore; Nitin Kumar (Food and Humanity, 2025)

Metabolic dysregulation in amyotrophic lateral sclerosis: insights from 1H NMR-based metabolomics in a tertiary care center in India - Priyanka Gautam; Rahul Yadav; Ranjeet Kumar Vishwakarma; Abhishek Pathak; Chandan Singh (Metabolic Brain Disease, 2025)

Seasonal patterns of air pollution in Delhi: interplay between meteorological conditions and emission sources - Najib Ansari; Preeti Kumari; Rahul Kumar; Pavan Kumar; Aquib Shamshad; Saddam Hossain; Ashutosh Sharma; Yogeshwar Singh; Maya Kumari; Varun Narayan Mishra; Rukhsana; Akram Javed (Environmental Geochemistry and Health, 2025)

Comprehensive elemental and carbon profiling of Punjab’s soils: distribution patterns, pollution assessment, and source attribution - Mahesh Tiwari; Tejas Rathod; Rahul Bhangare; Sanjay Kumar Sahu; Vandana Pulhani (Environmental Geochemistry and Health, 2025)

Trends in Antarctic Sea Ice and Albedo: Impacts of Ocean‐Atmospheric Processes - M Swathi; Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (International Journal of Climatology, 2025)
Surface albedo (SAL), a critical factor in climate studies, significantly impacts the Earth's radiation budget and sea ice dynamics. The long‐term spatial and temporal variability of Antarctic SAL were derived from the third edition of the Cloud, Albedo, and Surface Radiation Dataset (CLARA‐A3). The analysis focused on spring and summer across five longitudinal sectors around Antarctica. The relationships of sea ice concentration (SIC) and SAL with climatic variables such as sea surface temperature (SST), 2 m air temperature (T2m), turbulent heat flux, and total cloud cover are explored in detail. The study examined SAL changes in two distinct timescales, pre‐2015 (1979–2015) and post‐2015 (2016–2021), to understand sea ice variations and trends in Antarctic climate change. The study revealed contrasting summer SAL trends, with a positive trend pre‐2015 and a decreasing trend post‐2016 across most of Antarctica, except the Amundsen‐Bellingshausen Sea, which showed an opposite trend. West Antarctica exhibited higher SAL compared to East Antarctica. SAL and SIC were significantly negatively correlated with SST, T2m, and turbulent heat flux across all sectors. Cross‐seasonal lead–lag analysis indicated that increased turbulent heat flux was followed by an increase in SAL after 1–5 months. Wind patterns showed that winds from higher to lower latitudes increased SIC and SAL, while winds from lower to higher latitudes reduced SIC. Post‐2015, notable wind direction reversals were observed in the Antarctic Peninsula during spring. Sectors with higher cloud cover absorbed more ocean heat, reducing turbulent heat flux and affecting SAL. Overall, post‐2015 observations highlighted major shifts in sea ice dynamics and SAL trends during both spring and summer seasons. The SIC decreased markedly across all sectors, with the Weddell Sea showing the most significant reduction. This study highlights regional and seasonal variations in SAL and its interactions with SIC and climatic factors, emphasising shifts in trends post‐2015.

First report of Penicilliopsis clavariiformis causing seed rot in Diospyros crumenata based on morphological, pathological and molecular assessment - S. Praveena; Rahul Jose; Shambhu Kumar; P. Sujanapal (Crop Protection, 2025)

Linear-no-threshold concept for evaluating arsenic toxicity in rice grains - Sripati Abhiram Sahoo; Jayant Kulkarni; Suvarna Sounderajan; Rahul Checker; Santosh Kumar Sandur; Ashish Kumar Srivastava (Journal of Hazardous Materials, 2025)

Effect of heat stress on pig production and its mitigation strategies: a review - Rahul Katiyar; Chamniugongliu Gonmei; Sourabh Deori; Mahak Singh; Sayed Nabil Abedin; Rupali Rautela; Ningthoujam Suraj Singh; Himsikha Chakravarty; Meena Das; B. U. Choudhury; Vinay Kumar Mishra (Tropical Animal Health and Production, 2025)

A fusion approach of discrete wavelet decomposition and deep learning techniques for the enhancement of wind speed prediction accuracy - Sarvendra Kumar Singh; S. K. Jha; Rahul Gupta (Theoretical and Applied Climatology, 2025)

Morpho-molecular delineation of rice germplasm for leaf blast resistance under intermediate hill ecology of UT of J&K India - Rahul Saini; Bupesh Kumar; Manmohan Sharma; Vikas Sharma; V. B. Singh; R. S. Sudan; Komaljeet Gill (Genetic Resources and Crop Evolution, 2025)

State-of-the-art review of mitigation techniques and performance enhancement methods of phase change materials for thermal energy storage technology - Rahul Bidiyasar; Rohitash Kumar; Narendra Jakhar (Environmental Science and Pollution Research, 2025)

In-silico repurposing of antiviral compounds against Marburg virus: a computational drug discovery approach - Rahul Kumar Singh; Kaushik Sarkar; Rajesh Kumar Das (In Silico Pharmacology, 2025)

The occurrence of follicular cyst affects the embryonic developmental competences of buffalo oocytes under in vitro culture conditions - Pradeep Saini; Sandeep Kumar; Hitesh Jangra; Anupama Solanki; Rahul Verma; Rajesh Kumar; Ramakant Kaushik; Kushal Grakh; Gitesh Saini; Yogesh Bangar; Anand Kumar Pandey (Theriogenology, 2025)

Nanoplastics in heat-sensitive food packaging: A review of migration, detection, health, and environmental impacts - Senthilkumar Palanisamy; Barani Kumar Saravana Kumar; Aishwarya Vetrivel; Rahul Jacob Michael; Nivethitha Babu; Sanjay Sharan Nallamuthu; Kokila Saravanan; Shanmugam Venkatachalam; Naveen Kumar R J; Gayathri Devi Selvaraju; Rajendran K. Selvakesavan; Jintae Lee; et al. (Food Control, 2025)

Stability assessment of road-cut slopes along a section of NH-109 in Lesser Kumaun Himalaya, Uttarakhand, India - Rahul Kumar Verma; Rajesh Singh; Prateek Sharma; T. N. Singh; Ravi Kumar Umrao; Rahul Kumar Chaurasia (Natural Hazards, 2025)

Next-Gen Nano Biosensor Technologies to Monitor Carbapenem Resistance for Personalized Medicine - Rahul Harikumar Lathakumari; Leela Kakithakara Vajravelu; Jayaprakash Thulukanam; Ashwin Kumar Narasimhan (Indian Journal of Microbiology, 2025)

Gold Nanoparticles as a Tool to Detect Biomarkers in Osteoarthritis: New Insights - Atul Mourya; Shristi Arya; Ayush Singh; Gopal Bajad; Soham Loharkar; Shubhra; Pawan Devangan; Neelesh Kumar Mehra; Rahul Shukla; Ramesh Chandra; Jitender Madan (Indian Journal of Microbiology, 2025)

Exploring genetic diversity, population structure and stability for yield related traits in rice germplasm of northeastern India - C. Balakrishnan; Amit Kumar; Riya Raj; Veerendra Kumar Verma; Letngam Touthang; Rahul Kumar; Mayank Rai; S. P. Das; Vinay Kumar Mishra (Genetic Resources and Crop Evolution, 2025)

Novel Damage Quantification and Strength Degradation of Thermally Treated Bundelkhand Granite: An Indian Heritage Stone - Rahul Rooplal Katre; Shivani Verma; Rishabh Dwivedi; Sandeep Panchal; Nikhil Ninad Sirdesai; Kumar Hemant Singh; Trilok Nath Singh (Geoheritage, 2025)

Impact of microwave-assisted acid extraction (MW-AAE) methods on simultaneous ICP-MS analysis of multi-elements in edibles besides associated greenness and human health risk assessment - Naresh Pothuraju; Harish Kumar Pogula; Rushikant Jagdale; Udaya Kumar Vadla; Rahul Laxman Gajbhiye; Vipan Kumar Parihar; Ravichandiran Velayutham; Ramalingam Peraman (Environmental Monitoring and Assessment, 2025)

Quantifying Climate Influence on Net Ecosystem Exchange in Lowland Tropical Rice: A Five-Year Eddy Covariance Study - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Suchismita Pattanaik; Vijayakumar Shanmugam; Sumanta Chatterjee; Pratap Bhattacharyya; Rahul Tripathi; Mohammad Shahid; Kiran Kumar Mohapatra; Abhijit Pradhan; Nihar Ranjan Singh (Agricultural Research, 2025)

Overcoming Neuroanatomical Mapping and Computational Barriers in Human Brain Synaptic Architecture - Rahul Kumar; Ethan Waisberg; Joshua Ong; Phani Paladugu; Dylan Amiri; Ram Jagadeesan (Neuroinformatics, 2025)

Corrigendum to “Resource recovery from legacy waste dumpsites in India: A path towards sustainable waste management” [Chemosphere 365 (2024) /143337] - Vivek Ojha; Apurva Sharma; Ved Prakash Ranjan; Rahul Rautela; Aachal Dhawral; Sunil Kumar (Chemosphere, 2025)

Optimizing autonomous artificial intelligence diagnostics for neuro-ocular health in space missions - Rahul Kumar; Ethan Waisberg; Joshua Ong; Karsten Chima; Dylan Amiri; Alireza Tavakkoli (Life Sciences in Space Research, 2025)

Advanced environmental remediation using enhanced performance of hollow ZnO@SnIn4S8 core-shell nanorod arrays for hazardous ion and organic pollutant removal - Mohan Reddy Pallavolu; Vanish Kumar; Rahul Ranjan; Sanjeev Kumar; Adem Sreedhar; Mrinmoy Misra (Journal of Environmental Management, 2025)

Understanding the role of Mn in Ni-Mn/Al2O3 and Ni3Fe-Mn/Al2O3 catalysts for enhanced CO2 methanation activity - Jitendra Kumar Prabhakar; Rahul Kumar; Koustuv Ray; Pankaj A. Apte; Goutam Deo (Journal of Environmental Chemical Engineering, 2025)

Performance comparison between E-learning during COVID-19 pandemic versus traditional classes utilizing sentiment analysis - Rahul Kumar Singh; Gourav Bathla; Pardeep Singh; Tanupriya Choudhury; Jung-Sup Um (Spatial Information Research, 2025)

L-proline H2SO4 catalyzed synthesis of novel coumarin-based spiroindolino-3,4-dihydropyrimidin-2(1H)-ones: in vitro cytotoxic assay and molecular docking study - Mezhubeinuo; Rahul Mohanta; Hemanta Bordoloi; Akalesh Kumar Verma; Ghanashyam Bez (Molecular Diversity, 2025)

Exploring Salt Stress Tolerance in Horsegram (Macrotyloma Uniflorum): Insights from Growth, Physiological and Biochemical Approaches - Narayan Singh; Vasudha Maurya; Ashutosh Sharma; Rahul Kumar (Journal of Crop Health, 2025)

Biomass-Derived Biochar and CuO–NiO Nanocomposites: Eco-Friendly Solutions for Environmental Cleanup - Ravi Kumar; Shivani Sharma; Neha Kumari; Priyanka Sharma; Nitin Sharma; Shabnam Thakur; Rahul Sharma; Naveen Thakur; Kuldeep Kumar (International Journal of Environmental Research, 2025)

Unravelling the role of tumor microenvironment responsive nanobiomaterials in spatiotemporal controlled drug delivery for lung cancer therapy - Dadi A. Srinivasarao; Saurabh Shah; Paras Famta; Ganesh Vambhurkar; Naitik Jain; Sai Kiran S.S. Pindiprolu; Anamika Sharma; Rahul Kumar; Hara Prasad Padhy; Meenu Kumari; Jitender Madan; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Amelioration of breast cancer therapies through normalization of tumor vessels and microenvironment: paradigm shift to improve drug perfusion and nanocarrier permeation - Paras Famta; Saurabh Shah; Ganesh Vambhurkar; Giriraj Pandey; Deepkumar Bagasariya; Kondasingh Charan Kumar; Sajja Bhanu Prasad; Akshay Shinde; Suraj Wagh; Dadi A. Srinivasarao; Rahul Kumar; Dharmendra Kumar Khatri; et al. (Drug Delivery and Translational Research, 2025)

Flupyradifurone application: A promising approach to curtail tomato leaf curl New Delhi virus (ToLCNDV) transmission vectored by Bemisia tabaci in potato farming - Nitish Modgill; Kailash Chandra Naga; Dnyaneshwar Madhukar Firake; Rahul Kumar Tiwari; Subhash Shivaramu; Ravinder Kumar; Anuj Bhatnagar; Tanuja Buckseth; Aarti Bairwa; Chandan Maharana; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2025)

Digitization of the mining industry: Pathways to sustainability through enabling technologies - Chinmayee Chatterjee; Rahul Sindhwani; Sachin Kumar Mangla; Nitasha Hasteer (Resources Policy, 2025)

An assessment of the spatiotemporal dynamics and seasonal trends in NO₂ concentrations across India using advanced statistical analysis - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg (Remote Sensing Applications: Society and Environment, 2025)

An assessment of different line-of-sight and ground velocity distributions for a comprehensive understanding of ground deformation patterns in East Jharia coalfield - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Remote Sensing Applications: Society and Environment, 2025)

Effect of heavy metals contamination due to leachate migration from uncontrolled dumpsites: A comprehensive analysis on soil and groundwater - Jatin Kumar Drall; Rahul Rautela; Rohit Jambhulkar; Ajay Kumar Kataria; Sunil Kumar (Journal of Environmental Management, 2025)

Graphene-sponges containing multi-walled carbon nanotubes for electrosorption of salt-ions - Rahul Patil; Dong Jiang; Xingtao Xu; Nitish Kumar; Sudip Bhattacharjee; Sunil Kumar Yadav; Dinesh Kalyanasundaram; Rahul R. Salunkhe; Asim Bhaumik; Nithima Khaorapapong; Yusuke Yamauchi; Saikat Dutta (Chemical Engineering Journal, 2025)

Engineered mechanically exfoliated flexible graphene-based frugal strain sensors - Abhay Singh Thakur; Shivam Dubey; Shivam Kumar; Aditya Singh Thakur; Rahul Vaish (Chemical Engineering Journal, 2025)

Chitosan nanoparticles of imatinib mesylate coated with TPGS for the treatment of colon cancer: In-vivo & in-vitro studies - Darshan Bhirud; Sankha Bhattacharya; Harshvardhan Raval; Preeti Chidambar Sangave; Girdhari Lal Gupta; Gaurav Paraskar; Megha Jha; Satyam Sharma; Sateesh Belemkar; Devendra Kumar; Rahul Maheshwari; Mayank Sharma (Carbohydrate Polymers, 2025)

Quality by design empowered preparation of itraconazole albumin nanoparticles for prostate cancer - Saurabh Shah; Paras Famta; Anamika Sharma; Rahul Kumar; Giriraj Pandey; Ganesh Vambhurkar; Dadi A. Srinivasarao; Akshay Shinde; Sajja Bhanu Prasad; Amit Asthana; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Seismic hazard assessment of Agartala agglomeration based on 1D nonlinear ground response analysis and empirically derived liquefaction susceptibility - Rajat Debnatha; Rima Das; Rahul Kumar; Rajib Saha (Acta Geophysica, 2024)

Microalgae-derived tocopherols: Biotechnological advances in production and its therapeutic potentials - Udaypal; Rahul Kumar Goswami; Sanjeet Mehariya; Pradeep Verma (Sustainable Chemistry and Pharmacy, 2024)

Interventions of citizen science for mitigation and management of plastic pollution: Understanding sustainable development goals, policies, and regulations - Rahul Kumar Sinha; Rakesh Kumar; Shyam S. Phartyal; Prabhakar Sharma (Science of The Total Environment, 2024)

Multi-environment evaluation of Clary sage (Salvia sclarea L.) selections for yield and essential oil traits under Western Himalayan conditions - Ajay Kumar; Romika Thakur; Rahul Dev Gautam; Ramesh Chauhan; Dinesh Kumar; Ashok Kumar; Satbeer Singh; Sanatsujat Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

RETRACTED: Closing the loop: A comprehensive exploration of Taiwan's e-waste to resource conversion journey - Anjani R.K. Gollakota; Rahul Mishra; Cheuh-Ling Pai; Chi-Min Shu; Prakash Kumar Sarangi; Pugazhendhi Arivalagan (Environmental Research, 2024)

Deciphering phenomics approaches for understanding plant–microbe interactions in nutrient absorption and utilization - Milan Kumar Lal; Rahul Kumar Tiwari; Sandeep B. Adavi; Awadhesh Kumar; Ibragim Bamatov; Ekaterina Ivanova; Laxmipriya Behera; Rupak Jena; Ravinder Kumar (Plant Physiology Reports, 2024)

Evaluation of blood based quantitative PCR as a molecular diagnostic tool for post kala-azar dermal leishmaniasis (PKDL) - Awnish Kumar; Vishal K. Singh; Prasoon Madhukar; Rahul Tiwari; Ritirupa Roy; Rajneesh; Sanjana Mehrotra; Shyam Sundar; Rajiv Kumar (Molecular Biology Reports, 2024)

Morin hydrate ameliorates heat-induced testicular impairment in a mouse model - Rahul Kumar; Vikash Kumar; Guruswami Gurusubramanian; Saurabh Singh Rathore; Vikas Kumar Roy (Molecular Biology Reports, 2024)

Recent Advances in Targeting Transition Metals (Copper, Iron, and Zinc) in Alzheimer’s Disease - Raghuraj Singh; Archna Panghal; Krishna Jadhav; Ashima Thakur; Rahul Kumar Verma; Charan Singh; Manoj Goyal; Jayant Kumar; Ajay G. Namdeo (Molecular Neurobiology, 2024)

Delineating Homogeneous Management Zones for Nutrient Management in Rice Cultivated Area of Eastern India - Rahul Tripathi; Bismay Ranjan Tripathy; Ashish Kumar Gouda; Chinmay Kumar Swain; Sangita Mohanty; A. K. Nayak (Journal of Soil Science and Plant Nutrition, 2024)

The Chambal Badlands of Ganga River Basin, India: A Fading Geoheritage Odyssey - Rohit Kumar; Parv Kasana; Rahul Devrani; Shikha Panwar Devrani (Geoheritage, 2024)

Unveiling the bountiful treasures of India’s fruit genetic resources - Vartika Srivastava; K. Pradheep; Pragya Ranjan; R. Gowthami; J. K. Ranjan; Rahul Chandora; Neelam Shekhawat; D. P. Semwal; Anuradha Agrawal; Sanjay Kumar Singh; G. P. Singh (Food Security, 2024)

Introgression of opaque2 allele into sweetcorn composite through marker-assisted selection - Pratibha Sharma; Vivek Sharma; Harcharan S. Dhaliwal; Rahul Kumar (Cereal Research Communications, 2024)

Mechanistic Concepts of Multifaceted Roles of Neurotransmitters Like Signalling Molecules in Plant Responses to Biotic Stress - Ritul Saharan; Sudeepta Pattanayak; Rajendran Poorvasandhya; Jagmohan Singh; Priyanka Lal; Muhammad Ahsan Altaf; Awadhesh Kumar; Milan Kumar Lal; Rahul Kumar Tiwari; Ravinder Kumar (The Botanical Review, 2024)

Public Health Monitoring Based on Food Security Measures in Sustainable Smart City Development Using Machine Learning Techniques - Karri Sasi Kumar; Botta Sudha Sai; Rahul Ganpat Mapari; Mohd Shukri Ab Yajid; B. H. K. Bhagat Kumar; Hemlata Makarand Jadhav; P. Purushotham (Remote Sensing in Earth Systems Sciences, 2024)

Synergistic microalgal co-cultivation for treatment of municipal wastewater using a two-stage cultivation system and biomass valorization - Rahul Kumar Goswami; Sanjeet Mehariya; Pradeep Verma (Algal Research, 2024)

GIS-Based optimum path analysis for tourist places in Haridwar City - Pankaj P. Tasgaonkar; Rahul Dev Garg; Pradeep Kumar Garg (Applied Geomatics, 2024)

Hydrothermal synthesis of tungsten oxide photo/electrocatalysts: precursor-driven morphological tailoring and electrochemical performance for hydrogen evolution and oxygen reduction reaction application - Rahul Sarma; Biraj Kumar Kakati (Environmental Science and Pollution Research, 2024)

Synergistic Bioactivity of Aegiceras corniculatum (L.) Blanco and Its Endophytic Fungus Aspergillus: Antioxidant, Antimicrobial, and Cytotoxic Effects - Sharika Noshin; Rahul Dev Bairagi; Sadia Airin; Dipa Debnath; Md. Sohanur Rahaman; Amit Kumar Acharzo; Most. Nazmin Aktar; Mohammed Bourhia; Ahmad Mohammad Salamatullah; Md. Amirul Islam (Cell Biochemistry and Biophysics, 2024)

Exploring soil fertility dynamics and microbial flora in the east kolkata wetlands: implications for sustainable agriculture and ecosystem conservation - Sanjana Ghosh; Rahul Rautela; Arup Kumar Mitra; Sudeshna Shyam Choudhury; Ayan Chandra; Sunil Kumar; Bikram Dhara (Vegetos, 2024)

The Neoteric Paradigm of Biomolecule-Functionalized Albumin-Based Targeted Cancer Therapeutics - Swati Gunjkar; Ujala Gupta; Rahul Nair; Priti Paul; Mayur Aalhate; Srushti Mahajan; Indrani Maji; Manish K. Chourasia; Santosh Kumar Guru; Pankaj Kumar Singh (AAPS PharmSciTech, 2024)

Evaluating combined effects of chronic, low-dose exposures of cadmium (CLEC) and hyperglycemia on insulin signaling dysfunction in a hepatocellular model - Rahul Kumar; Rama R. Gullapalli (Toxicology, 2024)

Discerning the dynamics of urbanization-climate change-flood risk nexus in densely populated urban mega cities: An appraisal of efficient flood management through spatiotemporal and geostatistical rainfall analysis and hydrodynamic modeling - Rahul Deopa; Dev Anand Thakur; Satish Kumar; Mohit Prakash Mohanty; Punyo Asha (Science of The Total Environment, 2024)

First comprehensive evaluation of genetic variability for bacterial blight resistance in wild Punica granatum L. populations from the North-Western Himalayas - Rahul Sharma; Som Dev Sharma; Vikas Kumar Sharma; Monica Sharma; Dinesh Kumar; Rajat Sharma; Yashasvi Thakur; Shireen Khatri (Physiological and Molecular Plant Pathology, 2024)

Late-Holocene sea-level markers preserved in a beach ridge system on Phra Thong Island, Thailand - Rahul Kumar; Adam D. Switzer; Chris Gouramanis; Charles S. Bristow; Timothy A. Shaw; Kruawun Jankaew; Tanghua Li; Dominik Brill (Geomorphology, 2024)

Reduction of local scour around a circular bridge pier using the collars and sacrificial piles in non-uniform sediment - Mangu Rahul Bharadwaj; Lav Kumar Gupta; Manish Pandey (Geomorphology, 2024)

Carbon dots-nanosensors: Advancement in food traceability for a sustainable environmental development - Zaryab Shafi; Vinay Kumar Pandey; Rahul Singh; Sarvesh Rustagi (Food Control, 2024)

Comparative Preclinical Pharmacokinetics and Disposition of Favipiravir Following Pulmonary and Oral Administration as Potential Adjunct Therapy Against Airborne RNA Viruses - Venkata Siva Reddy Devireddy; Hasham Shafi; Sonia Verma; Sanjay Singh; J. V. U. S. Chakradhar; Naresh Kothuri; Himanshu Bansode; Sunil Kumar Raman; Deepak Sharma; Lubna Azmi; Rahul Kumar Verma; Amit Misra (Pharmaceutical Research, 2024)

Estimating Soil Organic Carbon Using Sensors Mounted on Unmanned Aircraft System and Machine Learning Algorithms - Rahul Tripathi; Shiv Sundar Jena; Chinmaya Kumar Swain; Gopal Dutta; Bismay Ranjan Tripathy; Sangita Mohanty; P. C. Jena; Asit Pradhan; R. N. Sahoo; S. D. Mohapatra; A. K. Nayak (Journal of the Indian Society of Remote Sensing, 2024)

Enhancing the silica-magnetic catalyst-assisted bioethanol production from biowaste via ultrasonics - Hemalatha Manivannan; Anikesh Krishnamurthy; Rahul Macherlla; Siva Chidambaram; Saravanan Pandiaraj; Muthumareeswaran Muthuramamoorthy; Selvarajan Ethiraj; G. Mohan Kumar (Clean Technologies and Environmental Policy, 2024)

Sorption of PFOS onto polystyrene microplastics potentiates synergistic toxic effects during zebrafish embryogenesis and neurodevelopment - Priya Gupta; Archisman Mahapatra; Bharat Manna; Anjali Suman; Shubhendu Shekhar Ray; Naresh Singhal; Rahul Kumar Singh (Chemosphere, 2024)

Resource recovery from legacy waste dumpsites in India: A path towards sustainable waste management - Vivek Ojha; Apurva Sharma; Ved Prakash Ranjan; Rahul Rautela; Aachal Dhawral; Sunil Kumar (Chemosphere, 2024)

A critical meta-analysis of CO2-water-rock interaction in basalt for CO2 storage: A review based on global and Indian perspective - Rahul Kumar Singh; Nirlipta P. Nayak; Sanjeev Kumar; Vikram Vishal (Marine and Petroleum Geology, 2024)

Real time monitoring of nerve agent mimics: Novel solid state emitter for enhanced precision and reliability - Anju Ranolia; Kiran; Priyanka; Rahul Kumar Dhaka; Jayant Sindhu (Journal of Hazardous Materials, 2024)

Progress and development of biochar as a catalyst for hydrogen production - Rahul Mishra; Chi-Min Shu; Hwai Chyuan Ong; Anjani R.K. Gollakota; Sunil Kumar (Journal of Cleaner Production, 2024)

How pulse electric field treatment affects anti-nutritional factors and plant protein digestibility: A concise review - Ankan Kheto; Sakshi Manikpuri; Ayan Sarkar; Rahul Das; Ram Prasad Bebartta; Yogesh Kumar; Yograj Bist; Rahul Vashishth; Rachna Sehrawat (Food Bioscience, 2024)

Candy leaf - Stevia rebaudiana (Bertoni) Bertoni attenuated LPS-induced protein kinase C phosphorylation in mouse macrophages cells: Target search by network pharmacology and validation using ex vivo and in vivo assays - Piyali Devroy; Suraj Kumar Chatterjee; Rahul Singh; Satyabrata Mohapatra; Sagnik Haldar; Ashis K. Mukherjee; Asis Bala (Food Bioscience, 2024)

Precision nutrient management influences the productivity, nutrients use efficiency, N2O fluxes and soil enzymatic activity in zero-till wheat (Triticum aestivum L.) - Rahul Sadhukhan; Dinesh Kumar; Seema Sepat; Avijit Ghosh; Koushik Banerjee; Y.S. Shivay; Sandeep Gawdiya; MN Harish; Arti Bhatia; Anita Kumawat; Suman Dutta; Niraj Biswakarma; et al. (Field Crops Research, 2024)

Investigating the performance of CoFe2O4@TiO2 nanomaterial as multifunctional cathode catalyst for simultaneous dye degradation and oxygen reduction in microbial desalination cell - Mohit Sahni; Rahul Kumar Mishra; Aarti Gupta; Bhim Sen Thapa; Anjali Thakur; Azmat Ali Khan; Soumya Pandit; Kuldeep Sharma; Amit Roy; Abdul Malik; Dipak A. Jadhav (Desalination, 2024)

Challenges in current pest management practices: Navigating problems and a way forward by integrating controlled release system approach - Amrita Singh; Nikita Shraogi; Rahul Verma; Joel Saji; Aditya Kumar Kar; Sarita Tehlan; Debabrata Ghosh; Satyakam Patnaik (Chemical Engineering Journal, 2024)

Long-term changes in tropospheric temperature in India: Insights from radiosonde measurements, reanalysis data and CMIP6 model projections - Rahul Kumar; Jayanarayanan Kuttippurath (Atmospheric Research, 2024)

An insight on medicinal attributes of 1,2,3‐ and 1,2,4‐triazole derivatives as alpha-amylase and alpha-glucosidase inhibitors - Anushka Sharma; Rahul Dubey; Ritu Bhupal; Preeti Patel; Sant Kumar Verma; Savas Kaya; Vivek Asati (Molecular Diversity, 2024)

Impact assessment of precipitation and temperature trends on crop yield in water stress zone of Bundelkhand, India - Rahul Dwivedi; Vivek Kumar; Deepak Khare (Journal of Earth System Science, 2024)

Potential and Limitation of Peptides from Native Plants of Uttarakhand - Neha Kamboj; Rahul Kumar; Navin Kumar; Pankaj Gautam (International Journal of Peptide Research and Therapeutics, 2024)

Response surface methodology–based optimisation of adsorption of diclofenac and treatment of pharmaceutical effluent using combined coagulation-adsorption onto nFe2O3 decorated water chestnut shells biochar - Amreen Bano; Mohd Kashif Aziz; Rahul Mishra; Hemen Dave; Bablu Prasad; Madhu Kumari; Darpan Dubey; Lucas Meili; Maulin P. Shah; Kumar Suranjit Prasad (Environmental Science and Pollution Research, 2024)

Harnessing the power of hybrid deep learning algorithm for the estimation of global horizontal irradiance - Rahul Gupta; Anil Kumar Yadav; S.K. Jha (Science of The Total Environment, 2024)

Contrasting response of regional spring Arctic Sea ice variations on Indian summer monsoon rainfall - Juhi Yadav; Avinash Kumar; Seong-Joong Kim; Rohit Srivastava; Rahul Mohan; M. Ravichandran (Remote Sensing of Environment, 2024)

HY5 and PIF antagonistically regulate HMGR expression and sterol biosynthesis in Arabidopsis thaliana - Rahul Michael; Avriti Ranjan; Swati Gautam; Prabodh Kumar Trivedi (Plant Science, 2024)

Colourful staples on your table: Unus ex genere suo - Eshita Sharma; Priyanka Lal; Awadhesh Kumar; Killi Prasad; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (Food Research International, 2024)

Quercetin in semen extender curtails reactive oxygen and nitrogen species and improves functional attributes of cryopreserved buck semen - Alok Kumar; J.K. Prasad; Nishant Kumar; Mukul Anand; Sonika Verma; Rahul Dhariya; Ajeet Kumar; Anil Gattani (Cryobiology, 2024)

Environmentally relevant concentrations of nickel and imidacloprid induce reproductive toxicity in earthworm (Eisenia fetida fetida) - Rahul Ladumor; Helly Pandya; Mansi Thakkar; Drashti Mehta; Priya Paithankar; Saleh Alfarraj; Mohammad Javed Ansari; Parth Pandya; Virendra Kumar Yadav; Dipak Kumar Sahoo; Ashish Patel (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Bio fabrication of microalgae mediated nanoparticles: An insight into its mechanism, characterization and applications - Rahul Kumar Goswami; Monika; Komal Agrawal; Sergey V. Alferov; Pradeep Verma (Biocatalysis and Agricultural Biotechnology, 2024)

Mapping Arsenic Contamination and Health Risk Assessment of Arsenic in Agricultural Soils of Eastern India - Rahul Mishra; Siba Prasad Datta; Debasis Golui; Mahesh Chand Meena; Md Basit Raza; Mohammad Mahmudur Rahman; Mahipal Chaudhary; Sanjib Kumar Behera; Amresh Chaudhary; Devi Prasad Upadhyay; Arvind Kumar Shukla (Water, Air, & Soil Pollution, 2024)

Modified speed breeding approach reduced breeding cycle to less than half in vegetable soybean [Glycine max (L.) Merr.] - Meniari Taku; Manisha Saini; Rahul Kumar; Pulak Debbarma; Nenavath Krishna Kumar Rathod; Reshma Onteddu; Deepshikha Sharma; Renu Pandey; Kishore Gaikwad; S. K. Lal; Akshay Talukdar (Physiology and Molecular Biology of Plants, 2024)

Microglial Neuroinflammation-Independent Reversal of Demyelination of Corpus Callosum by Arsenic in a Cuprizone-Induced Demyelinating Mouse Model - Shaivya Kushwaha; Joel Saji; Rahul Verma; Vikas Singh; Jamal Ahmad Ansari; Shubhendra Kumar Mishra; Opalina Roy; Satyakam Patnaik; Debabrata Ghosh (Molecular Neurobiology, 2024)

Multi-modal medical image fusion using improved dual-channel PCNN - Adarsh Sinha; Rahul Agarwal; Vinay Kumar; Nitin Garg; Dhruv Singh Pundir; Harsimran Singh; Ritu Rani; Chinmaya Panigrahy (Medical & Biological Engineering & Computing, 2024)

Effectiveness of base-isolator on the seismic behaviour of high-rise buildings with shear wall - Dolly Singh; Shashwata Chatterjee; Shobha Ram; Anju Agarwal; Rohit Ralli; Rahul Kumar (Innovative Infrastructure Solutions, 2024)

Whole-genome sequence analysis of canine parvovirus reveals replacement with a novel CPV-2c strain throughout India - Harish Reddy; Mouttou Vivek Srinivas; Jayalakshmi Vasu; Abiramy Prabavathy; Rahul Dhodapkar; Hirak Kumar Mukhopadhyay (Archives of Virology, 2024)

Recuperative potential of Indian medicinal plant compounds- a tool to encumber henipaviruses: an in -silico study - Sukanth Kumar Enmozhi; Infant Xavier; Theepan Raaj; R. Sarveswaran; Jeba Blessings; Yugesh Kesavamoorthy; Rahul Vivek; Kavitha Raja; Irudhayasamy Sebastine; Antony Jeffri; Sumathy Arockiasamy; Jerrine Joseph; et al. (In Silico Pharmacology, 2024)

Quality by Design in Pulmonary Drug Delivery: A Review on Dry Powder Inhaler Development, Nanotherapy Approaches, and Regulatory Considerations - Ashish Dilip Sutar; Rahul Kumar Verma; Rahul Shukla (AAPS PharmSciTech, 2024)

Lower body negative pressure as a research tool and countermeasure for the physiological effects of spaceflight: A comprehensive review - Phani Paladugu; Joshua Ong; Rahul Kumar; Ethan Waisberg; Nasif Zaman; Sharif Amit Kamran; Alireza Tavakkoli; Maria Chiara Rivolta; Nicolas Nelson; Taehwan Yoo; Vivian Paraskevi Douglas; Konstantinos Douglas; et al. (Life Sciences in Space Research, 2024)

Sequential two-stage cultivation system using novel microalga consortia for treatment of municipal wastewater and simultaneous biomass production: Sustainable environmental management - Rahul Kumar Goswami; Sanjeet Mehariya; Pradeep Verma (Journal of Environmental Management, 2024)

PCA and fuzzy clustering-based delineation of soil nutrient (S, B, Zn, Mn, Fe, and Cu) management zones of sub-tropical Northeastern India for precision nutrient management - Arvind Kumar Shukla; Sanjib Kumar Behera; Anjali Basumatary; Indira Sarangthem; Rahul Mishra; Samiron Dutta; Yogesh Sikaniya; Akanksha Sikarwar; Vimal Shukla; Siba Prasad Datta (Journal of Environmental Management, 2024)

A hybrid SWAT-ANN model approach for analysis of climate change impacts on sediment yield in an Eastern Himalayan sub-watershed of Brahmaputra - Swapnali Barman; Waikhom Rahul Singh; Jaivir Tyagi; Sanjay Kumar Sharma (Journal of Environmental Management, 2024)

Exploring sources, extraction techniques and food applications: a review on biocolors as next-generation colorants - Iqra Bashir; Vinay Kumar Pandey; Aamir Hussain Dar; Kshirod Kumar Dash; Rafeeya Shams; Shabir Ahmad Mir; Ufaq Fayaz; Shafat Ahmad Khan; Rahul Singh; Insha Zahoor (Phytochemistry Reviews, 2024)

Artificial intelligence assisted identification of potential tau aggregation inhibitors: ligand- and structure-based virtual screening, in silico ADME, and molecular dynamics study - Bhanuranjan Das; Alen T. Mathew; Anurag T. K. Baidya; Bharti Devi; Rahul Rampa Salmon; Rajnish Kumar (Molecular Diversity, 2024)

Conservation Agricultural Practices Influencing the Seasonal Weed Dynamic and Productivity of Wheat in the Trans Indo-Gangetic Plains of India - Seema Sepat; Arvind Kumar; Ramanjit Kaur; Harminder Singh; Bhagyashree Phogat; Dinesh Kumar; Rahul Sadhukhan; S. L. Meena; S. R. Choudhary; Ahmed Gaber; Akbar Hossain (Journal of Crop Health, 2024)

Enhanced Bioremediation of Commercial Diesel Contamination by Mixed Culture of Newly Isolated Providencia vermicola IITG20 and Pseudomonas aeruginosa IITG21 from Local Refinery Waste - Rahul Kumar; Mahuya De (International Journal of Environmental Research, 2024)

A machine learning-based overlay technique for improving the mechanism of road traffic prediction using global positioning system - Amar Deep Pandey; Brind Kumar; Manoranjan Parida; Ashish Kumar Chouksey; Rahul Mishra (Innovative Infrastructure Solutions, 2024)

Chronic hyperglycemia impairs anti-microbial function of macrophages in response to Mycobacterium tuberculosis infection - Gaurav Kumar Chaubey; Radheshyam Modanwal; Rahul Dilawari; Sharmila Talukdar; Asmita Dhiman; Surbhi Chaudhary; Anil Patidar; Chaaya Iyengar Raje; Manoj Raje (Immunologic Research, 2024)

Strategies for improvement of bioactive compounds production using microalgal consortia: An emerging concept for current and future perspective - Udaypal Udaypal; Rahul Kumar Goswami; Pradeep Verma (Algal Research, 2024)

A novel approach for assessment of seismic induced liquefaction susceptibility of soil - Divesh Ranjan Kumar; Pijush Samui; Avijit Burman; Rahul Biswas; Sai Vanapalli (Journal of Earth System Science, 2024)

Point-junction and alkali-assisted surface selenium diffusion: Unveiling a two-step method for enhancing the efficiency of VTD-SnS thin-film solar cells - Indu Sharma; Pravin S. Pawar; Rahul Kumar Yadav; Yong Tae Kim; Neha Bisht; Parag R. Patil; Jaeyeong Heo (Chemical Engineering Journal, 2024)

Advances and challenges in organ-on-chip technology: toward mimicking human physiology and disease in vitro - Dhiraj Kumar; Rahul Nadda; Ramjee Repaka (Medical & Biological Engineering & Computing, 2024)

Formulation and Characterization of Silibinin Entrapped Nano-Liquid Crystals for Activity against Aβ1-42 Neurotoxicity in In-Vivo Model - Ajit Singh; Debarati Rakshit; Ankit Kumar; Awanish Mishra; Rahul Shukla (AAPS PharmSciTech, 2024)

Neottia bicallosa X.H. Jin, a new distributional record of bird’s nest orchid for India - Vikas Kumar; Rahul Kumar (Vegetos, 2024)

Panicle compactness along with abiotic factors influence the abundance of earhead feeding insect pests of sorghum [Sorghum bicolor (L.) Moench] - Rahul Saini; Dalip Kumar; Jyotsana Chauhan; Poonam Jasrotia (International Journal of Tropical Insect Science, 2024)

Increased global cropland greening as a response to the unusual reduction in atmospheric PM₂.₅ concentrations during the COVID-19 lockdown period - Vikas Kumar Patel; Jayanarayanan Kuttippurath; Rahul Kashyap (Chemosphere, 2024)

Comparative expression and localization of visfatin, chemerin, and chemerin receptor proteins in a heat-stressed mouse testis - Miti Jerang; Rahul Kumar; Guruswami Gurusubramanian; Vikas Kumar Roy (Tissue and Cell, 2024)

Removal of encapsulant ethylene-vinyl acetate for recycling of photovoltaic modules: Hansen solubility parameters analysis - Harish Kumar Trivedi; Rahul Kumar Yadav; Arunabh Meshram; Rajeev Gupta (Process Safety and Environmental Protection, 2024)

Performance monitoring of the wastewater system of Bharati Station, Antarctica - Rahul Kumar; N.S. Magesh; Vivek Kumar; Kirti Ranjan Das; Ariz Ahmad; Vikas Singh; Partha Sarathi Majhi; Ravi Mishra; Anand K. Singh; Shailendra Saini; Yogesh Ray (Polar Science, 2024)

Influence of Plant Growth Regulators on In Vitro Morphogenesis in Sprout Culture of Potato (Solanum tuberosum L.) - Rahul Sharde; Manoj Kumar Tripathi; Deepa Bhatt; Sushma Tiwari; Mohini Sharma; Yashi Singh Tomar; Niraj Tripathi (Potato Research, 2024)

Nonsterile Process for Biohydrogen Production: Recent Updates, Challenges, and Opportunities - Sanjay K. S. Patel; Rahul K. Gupta; Karthikeyan K. Karuppanan; Deepak Kumar Padhi; Sampathkumar Ranganathan; Parasuraman Paramanantham; Jung-Kul Lee (Indian Journal of Microbiology, 2024)

Development of southern corn leaf blight (SCLB) resistant and high-popping volume composite popcorn using phenotypic and marker-assisted selection (MAS) - Shivani Thakur; Rahul Kumar; Baldeep Singh; Yogesh Vikal; H. S. Dhaliwal; Vikrant Tyagi; Imran Sheikh (Cereal Research Communications, 2024)

Countermeasures for local scour around the bridge pier: a review - Mangu Rahul Bharadwaj; Lav Kumar Gupta; Manish Pandey; Manousos Valyrakis (Acta Geophysica, 2024)

First report of Alternaria tenuissima causing leaf black spot on Aloe barbadensis in India - Kajal Singh; Poonam Kumari; Rahul Kumar Gupta; Anil Kumar Gupta; Akanksha Singh (Journal of Plant Pathology, 2024)

Sustainable microalgal biomass as a potential functional food and its applications in food industry: a comprehensive review - Akhil Dhandwal; Omar Bashir; Tanu Malik; Rahul Vinayak Salve; Kshirod Kumar Dash; Tawheed Amin; Rafeeya Shams; Ab Waheed Wani; Yasir Abbas Shah (Environmental Science and Pollution Research, 2024)

Microalgal biochar assisted simultaneous removal of particulate matter, formaldehyde, and total volatile organic compounds (TVOC's) from indoor air - Rahul Kumar; Vivek Dalvi; Kamal Kishore Pant; Anushree Malik (Chemosphere, 2024)

Projected water availability in the Tawa River Basin India in changing climate - Pragya Badika; Mahendra Kumar Choudhary; Tejram Nayak; Rahul Kumar Jaiswal; Ankit Agarwal (Groundwater for Sustainable Development, 2024)

Exploring CO2 sequestration potential as gas hydrates in clay dominated subsea system with and without surfactant - Yogendra Kumar; Milind Ghoderao; Rahul Sarkhel; Jitendra Sangwai (Fuel, 2024)

Technologies for management of fish waste & value addition - Puja Nelluri; Rahul Kumar Rout; Dushyanth Kumar Tammineni; T. Jayasree Joshi; S. Sivaranjani (Food and Humanity, 2024)

Ultrasound-assisted oxalate reduction vs. conventional methods: A comparative study in Elephant foot yam (Amorphophallus paeoniifolius) and process optimization using response surface methodology - Shivangi Srivastava; Vinay Kumar Pandey; Anjali Tripathi; Rahul Singh; Kshirod K. Dash (Food and Humanity, 2024)

Advances in microalgae-based carbon sequestration: Current status and future perspectives - Udaypal; Rahul Kumar Goswami; Sanjeet Mehariya; Pradeep Verma (Environmental Research, 2024)

Sub-pilot scale sequential microalgal consortium-based cultivation for treatment of municipal wastewater and biomass production - Rahul Kumar Goswami; Sanjeet Mehariya; Pradeep Verma (Environmental Pollution, 2024)

Superior electron mobility, red electroluminescence with high quantum efficiency from printable room temperature columnar liquid crystalline perylene bisimide - Paresh Kumar Behera; Feng-Rong Chen; Indrajit Mondal; Sushanta Lenka; Prakalp Gautam; Nihal Khatiwoda; Iram Siddiqui; V.E. Krishnaprasad; Rahul Ahmed; Doddamane Sreenivasamurthy Shankar Rao; Satyaprasad P. Senanayak; Jwo-Huei Jou; et al. (Chemical Engineering Journal, 2024)

Sparse deep belief network coupled with extended local fuzzy active contour model-based liver cancer segmentation from abdomen CT images - A. Joel Dickson; J. Arul Linsely; V. Antony Asir Daniel; Kumar Rahul (Medical & Biological Engineering & Computing, 2024)

A highly divergent enteric calicivirus in a bovine calf in India - Naveen Kumar; Rahul Kaushik; Pragya Yadav; Shubhankar Sircar; Anita Shete-Aich; Ashutosh Singh; Yashpal Singh Malik (Archives of Virology, 2024)

Melatonin alleviates cadmium phytotoxicity through regulation of growth, photosynthesis, and antioxidant potential in two pepper genotypes - Muhammad Saqib; Umbreen Shahzad; Zakia Abid; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Waleed Amjad Khan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (Acta Physiologiae Plantarum, 2024)

Green synthesis of chitosan-encapsulated CuO nanocomposites for efficient degradation of cephalosporin antibiotics in contaminated water - Nishat Bhatia; Asha Kumari; Ragini Raj Singh; Gulshan Kumar; Abhishek Kandwal; Rahul Sharma (Environmental Science and Pollution Research, 2024)

From stress to success: Silicon and nano-silicon strategies for enhancing fruit yield and quality in cadmium-exposed trees - Riaz Ahmad; Hafiza Muniba Din Muhammad; Safina Naz; Rahul Kumar Tiwari; Milan Kumar Lal; Parvaiz Ahmad; Muhammad Ahsan Altaf (South African Journal of Botany, 2024)

Development and validation of RP-HPLC method for estimation of quercetin present in hydro alcoholic extract of Erigeron bonariensis Linn. - Vishal B. Mahanur; Rahul R. Rajge; Sukriti Vishwas; M.V.N.L. Chaitanya; Salahuddin; Rashmi Mishra; Narendra Kumar Pandey; Saurabh Singh; Dileep Singh Baghel; Gaurav Gupta; Trudi Collet; Oluwafemi Omoniyi Oguntibeju; et al. (South African Journal of Botany, 2024)

Assessing the sustainability of threadfin bream fishery along South-eastern coast of the Arabian Sea: A comprehensive analysis of climate change impact and fishing frontiers - Radhika Balachandran; P.U. Zacharia; G.B. Purushottama; K.S. Sudarsan; Muhammad Shafeeque; R. Ratheesh Kumar; Eldho Varghese; Alphonsa Joseph; R. Rahul; Nanda Kishore; Rose P. Bright; P.K. Seetha; et al. (Regional Studies in Marine Science, 2024)

Comparative study of reduction of pier scour using octagonal and circular collars - Lav Kumar Gupta; M. Rahul Bharadwaj; Manish Pandey (Ocean Engineering, 2024)

Enhancing the efficiency of metals extraction from waste lithium-ion batteries through glycine leaching using response surface methodology for economic feasibility - Rahul Rautela; Bholu Ram Yadav; Sunil Kumar (Journal of Cleaner Production, 2024)

Highly sensitive optical approach towards Cu (II) ions detection in water sample using thioglycolic acid capped vanadium disulfide-based dichalcogenide quantum dots - Rahul Kumar; Tarun K. Dhiman; G.B.V.S. Lakshmi; Pratima R. Solanki; Kedar Singh (Journal of Environmental Chemical Engineering, 2024)

Sustainable basmati rice yield and quality enhancement through long-term organic nutrient management in the Indo-Gangetic Plains - Anita Kumawat; Dinesh Kumar; Y.S. Shivay; Devideen Yadav; Rahul Sadhukhan; Sandeep Gawdiya; Shakir Ali; M. Madhu; Kuldeep Kumar; I. Rashmi; R.A. Jat (Field Crops Research, 2024)

Crystallinity transformation engineering of hydrous cobalt nickel phosphate cathodes for hybrid supercapacitor devices: Extrinsic/battery to intercalation type pseudocapacitors - Vinod V. Patil; Nitish Kumar; Rahul R. Salunkhe; Jayavant L. Gunjakar; Chandrakant D. Lokhande; Mukund G. Mali; Vinayak G. Parale; Hyung-Ho Park; Dattakumar S. Mhamane; Umakant M. Patil (Chemical Engineering Journal, 2024)

Integrated use of ligand and structure-based virtual screening, molecular dynamics, free energy calculation and ADME prediction for the identification of potential PTP1B inhibitors - Bharti Devi; Sumukh Satyanarayana Vasishta; Bhanuranjan Das; Anurag T. K. Baidya; Rahul Salmon Rampa; Manoj Kumar Mahapatra; Rajnish Kumar (Molecular Diversity, 2024)

Effective-diode-based analysis of industrial solar photovoltaic panel by utilizing novel three-diode solar cell model against conventional single and double solar cell - Rahul Kumar; Amitesh Kumar (Environmental Science and Pollution Research, 2024)

Polystyrene microplastics induced disturbances in neuronal arborization and dendritic spine density in mice prefrontal cortex - Anjali Suman; Archisman Mahapatra; Priya Gupta; Shubhendu Shekhar Ray; Rahul Kumar Singh (Chemosphere, 2024)

Role of melatonin in the regulation of abiotic stress in plants - Muhammad Ahsan Altaf; Milan Kumar Lal; Rahul Kumar Tiwari (South African Journal of Botany, 2024)

Dominance of soil moisture over aridity in explaining vegetation greenness across global drylands - Indra Mani Tripathi; Shanti Shwarup Mahto; Anuj Prakash Kushwaha; Rahul Kumar; Amar Deep Tiwari; Bidhan Kumar Sahu; Vikrant Jain; Pranab Kumar Mohapatra (Science of The Total Environment, 2024)

Emergence of per- and poly-fluoroalkyl substances (PFAS) and advances in the remediation strategies - Bhim Sen Thapa; Soumya Pandit; Rahul Kumar Mishra; Sanket Joshi; Abubakr M. Idris; Tanmoy Roy Tusher (Science of The Total Environment, 2024)

Discovering the regulators of heat stress tolerance in Ziziphus nummularia (Burm.f) wight and walk.-arn - Kishor Prabhakar Panzade; Kishor U. Tribhuvan; Deepak V. Pawar; Rahul Singh Jasrotia; Kishor Gaikwad; Monika Dalal; Ranjeet Ranjan Kumar; Madan Pal Singh; Om Prakash Awasthi; Jasdeep Chatrath Padaria (Physiology and Molecular Biology of Plants, 2024)

Ionic Partitioning and Grain Mineral Contents in Quinoa Accessions in Response to High-SAR Saline Water Irrigation - Kailash Prajapat; Satish Kumar Sanwal; Parbodh Chander Sharma; Rahul Chandora (Journal of Soil Science and Plant Nutrition, 2024)

Comparative evaluation of management modules against Maydis leaf blight disease in maize (Zea mays) - Sumit Kumar Aggarwal; K. S. Hooda; Harleen Kaur; Robin Gogoi; Prashant Chauhan; P. K. Bagaria; Pardeep Kumar; Mukesh Choudhary; Rahul Kumar Tiwari; Milan Kumar Lal (European Journal of Plant Pathology, 2024)

Finding identical sequence repeats in multiple protein sequences: An algorithm - Vikas Kumar Maurya; Madhumathi Sanjeevi; Chandrasekar Narayanan Rahul; Ajitha Mohan; Dhanalakshmi Ramachandran; Rashmi Siddalingappa; Roshan Rauniyar; Sekar Kanagaraj (Journal of Biosciences, 2024)

Hypobaric hypoxia drives selection of altitude-associated adaptative alleles in the Himalayan population - Samantha Sharma; Remya Koshy; Rahul Kumar; Ghulam Mohammad; Tashi Thinlas; Brian B. Graham; Qadar Pasha (Science of The Total Environment, 2024)

Sewage treatment plant dust: An emerging concern for heavy metals-induced health risks in urban area - Rahul Tiwari; Vidisha Upadhyay; Sartaj Ahmad Bhat; Sunil Kumar (Science of The Total Environment, 2024)

Fusarium core rot disease affects physicochemical and pathophysiological attributes of apple (Malus × domestica Borkh.) fruit - Santosh Watpade; Milan Kumar Lal; Rahul Kumar Tiwari; Rishav Kumar; Kailash Chandra Naga; Ravinder Kumar; Kallol Kumar Pramanick; Hema Kumari; Esha Devi; Dharam Pal (Postharvest Biology and Technology, 2024)

Assessment of reservoir heterogeneities and hydrocarbon potential zones using wavelet-based fractal and multifractal analysis of geophysical logs of Cambay basin, India - Rahul Prajapati; Raj Kumar; Upendra K. Singh (Marine and Petroleum Geology, 2024)

Deciphering the potential of diverse barley genotypes for improving the malt quality - Heena Rani; Rachana D. Bhardwaj; Rahul Sen; Dinesh Kumar; Pankaj Bhardwaj; Simarjit Kaur; Satvir K. Grewal (Journal of Stored Products Research, 2024)

Exploring the current landscape of chitosan-based hybrid nanoplatforms as cancer theragnostic - Rahul Nair; Priti Paul; Indrani Maji; Ujala Gupta; Srushti Mahajan; Mayur Aalhate; Santosh Kumar Guru; Pankaj Kumar Singh (Carbohydrate Polymers, 2024)

Natural Snowmelt Timing Influences Community Structure and Phenological Patterns in Alpine Meadows, West Himalaya: A Case Study - Rahul Kumar; Bhupendra S. Adhikari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Transcriptional regulation of tomato fruit ripening - Priya Gambhir; Utkarsh Raghuvanshi; Rahul Kumar; Arun Kumar Sharma (Physiology and Molecular Biology of Plants, 2024)

MyeloDB: a multi-omics resource for multiple myeloma - Ambuj Kumar; Keerthana Vinod Kumar; Kavita Kundal; Avik Sengupta; Simran Sharma; Kunjulakshmi R; Rahul Kumar (Functional & Integrative Genomics, 2024)

Methodological Breakdown of Potato Peel’s Influence on Starch Digestibility, In Vitro Glycemic Response and Pasting Properties of Potato - Milan Kumar Lal; Rahul Kumar Tiwari; Awadhesh Kumar; Ravinder Kumar; Dharmendra Kumar; Arvind Jaiswal; Sushil Sudhakar Changan; Som Dutt; Jelena Popović-Djordjević; Brajesh Singh; Jesus Simal-Gandara (American Journal of Potato Research, 2024)
A Potato ( Solanum tuberosum L.) is a major staple food consumed worldwide. Potato peel is an important constituent that is generally discarded and considered agricultural waste before processing or cooking. The present investigation is an attempt to utilize different contents of potato peels (PP) with potato flesh (PF) of processing cultivar (Kufri Chipsona 3) and table cultivar (Kufri Jyoti), which affect starch nutritional profile, glycemic response, and pasting properties. The combination of PP at different concentrations of 5, 10, and 15%, respectively, to PF showed a significant reduction ( P

Evaluation of the Hyderabad network’s broadband seismic stations for characterizing ambient noise in the Eastern Dharwar Craton, southern India - Satish Saha; Rahul Biswas; Prantik Mandal; Pavan Kumar Vengala; M Saidixith; B N V Prasad (Journal of Earth System Science, 2024)

Fungi-assisted bio-flocculation of Picochlorum sp.: A novel bio-assisted treatment system for municipal wastewater - Rahul Kumar Goswami; Sanjeet Mehariya; Obulisamy Parthiba Karthikeyan; Pradeep Verma (Journal of Water Process Engineering, 2024)

Sonocatalytic induced dye degradation and antibacterial performance of SrTiO3 nanoparticles embedded cotton fabric - Amit Kumar; Moolchand Sharma; Abdelfattah Amari; Rahul Vaish (Environmental Research, 2024)

Imaging of Different Crustal and Mantle Discontinuities Below the Hyderabad Region on the Eastern Dharwar Craton - Prantik Mandal; Sandeep Gupta; K. Sivaram; Sanjay Kumar; Sudesh Kumar; Rahul Biswas; Raju Prathigadapa; B. N. V. Prasad; M. Saidixit (Pure and Applied Geophysics, 2024)

Examining effect of super-resolution on AVIRIS-NG data: A precursor to generation of large-scale urban material and natural cover maps - Kavach Mishra; Asfa Siddiqui; Vinay Kumar; Kamal Pandey; Rahul Dev Garg (Advances in Space Research, 2024)

Advances in phase change materials and nanomaterials for applications in thermal energy storage - Rahul Kumar; Amit Kumar Thakur; Lovi Raj Gupta; Anita Gehlot; Vineet Singh Sikarwar (Environmental Science and Pollution Research, 2023)

Determinants of farmers’ choice for agricultural output marketing channels of tomato (Solanum lycopersicum): an empirical evidence from north-western Himalayan region - Pankaj Thakur; Piyush Mehta; Amit Guleria; Divyanshu; Pardeep Singh; Prashant Sharma; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (Environment, Development and Sustainability, 2023)

Emission inventory of inorganic trace gases from solid residential fuels over the National Capital Territory of India - Rahul Arya; Sakshi Ahlawat; Lokesh Yadav; Martina Rani; Arnab Mondal; Ritu Jangirh; Garima Kotnala; Nikki Choudhary; Akansha Rai; Ummed Singh Saharan; Pooja Yadav; Rubiya Banoo; et al. (Environmental Science and Pollution Research, 2023)

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Valorisation of organic carbons and organo-solvents by mixotrophic cultivation of methylotrophic Tetraselmis indica for enhanced biomolecules production - Rahul Kumar Goswami; Sanjeet Mehariya; Obulisamy Parthiba Karthikeyan; Pradeep Verma (Sustainable Chemistry and Pharmacy, 2023)

Prevalence of pharmaceuticals and personal care products, microplastics and co-infecting microbes in the post-COVID-19 era and its implications on antimicrobial resistance and potential endocrine disruptive effects - Manish Kumar; Payal Mazumder; Rahul Silori; Suvendu Manna; Durga Prasad Panday; Nilotpal Das; Susanta Kumar Sethy; Keisuke Kuroda; Durga Madhab Mahapatra; Jürgen Mahlknecht; Vinay Kumar Tyagi; Rajesh Singh; et al. (Science of The Total Environment, 2023)

Particulates, unregulated and regulated emissions and catalytic converter efficiency evaluation of methanol (M15) fuelled BS-VI compliant light-duty spark-ignition engine - Ankur Kalwar; Rahul Kumar Singh; Ankit Gupta; Ranjeet Rajak; Gokul Gosakan; Avinash Kumar Agarwal (Science of The Total Environment, 2023)

A flexible and efficient knowledge-guided machine learning data assimilation (KGML-DA) framework for agroecosystem prediction in the US Midwest - Qi Yang; Licheng Liu; Junxiong Zhou; Rahul Ghosh; Bin Peng; Kaiyu Guan; Jinyun Tang; Wang Zhou; Vipin Kumar; Zhenong Jin (Remote Sensing of Environment, 2023)

Morphological changes and future projections of the Getz Ice shelf, western Antarctica—A statistical and geospatial approach - Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (Regional Studies in Marine Science, 2023)

Synthesis of graphene oxide from biomass waste: Characterization and volatile organic compounds removal - Rahul Mishra; Aman Kumar; Ekta Singh; Archana Kumari; Sunil Kumar (Process Safety and Environmental Protection, 2023)

International collaboration- An indispensable tool for Antarctic research: Status report of India's endeavours on the icy continent - Swati Nagar; Yogesh Ray; Rakesh Rao; Avinash Kumar; Rahul Mohan (Polar Science, 2023)

Mineral magnetic properties of surface soils from the Broknes and Grovnes Peninsula, Larsemann Hills, East Antarctica - G.S. Joju; Anish Kumar Warrier; Marcos A.E. Chaparro; B.S. Mahesh; Freddy Abraham Matthew; S. Anusree; Rahul Mohan (Polar Science, 2023)

Have COVID lockdowns really improved global air quality? –Hierarchical observations from the perspective of urban agglomerations using atmospheric reanalysis data - Rahul Deb Das; Subhajit Bandopadhyay; Subhasis Ghosh; Mridul Das; Mousumi Chowdhury; Alexander Cotrina-Sanchez; Chandan Kumar; Chandana Mitra (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Zinc oxide and selenium nanoparticles can improve semen quality and heat shock protein expression in cryopreserved goat (Capra hircus) spermatozoa - Sayed Nabil Abedin; Anubha Baruah; Kishore Kumar Baruah; Arundhati Bora; Devo Jyoti Dutta; Govindasamy Kadirvel; Rahul Katiyar; Sunil Doley; Samir Das; Gautam Khargharia; Biplab Sarkar; Sudip Sinha; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Microsatellite markers’ based molecular divergence among the breeding lines of aromatic marigold (Tagetes minuta L.) - Ajay Kumar; Hari Sharan; Diksha Dhiman; Rahul Dev Gautam; Ramesh Chauhan; Ashok Kumar; Satbeer Singh; Sanatsujat Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

A deep transfer learning framework for mapping high spatiotemporal resolution LAI - Junxiong Zhou; Qi Yang; Licheng Liu; Yanghui Kang; Xiaowei Jia; Min Chen; Rahul Ghosh; Shaomin Xu; Chongya Jiang; Kaiyu Guan; Vipin Kumar; Zhenong Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Sous vide processing for food quality enhancement: A review - Poornima Singh; Zainab Sultan; Vinay Kumar Pandey; Rahul Singh (Food and Humanity, 2023)

The Removal of Fluoride from the Water Using Epipremnum aureum (Money Plant) - Rahul Rahul; Ramesh Kumar; Suman Nagpal (Water Conservation Science and Engineering, 2023)

Ligand-based designing of DPP-4 inhibitors via hybridization; synthesis, docking, and biological evaluation of pyridazine-acetohydrazides - Manisha Nidhar; Vipin Kumar; Archisman Mahapatra; Priya Gupta; Brijesh Kumar Yadav; Rahul Kumar Singh; Ashish Kumar Tewari (Molecular Diversity, 2023)

Transcriptomic and Metabolomic Reprogramming to Explore the High-Altitude Adaptation of Medicinal Plants: A Review - Vinay Kumar; Pankaj Kumar; Bhavya Bhargava; Rohit Sharma; Mohammad Irfan; Rahul Chandora (Journal of Plant Growth Regulation, 2023)

Rhizospheric Trichoderma harzianum TBR-7 in combination with chitosan for eco-friendly management of crown rot disease in Egyptian clover (Trifolium alexandrinum L.) - Nitish Rattan Bhardwaj; Maneet Rana; Pushpendra Koli; Rahul Kaldate; Ajoy Kumar Roy; Amaresh Chandra (European Journal of Plant Pathology, 2023)

Microbial Waterborne Diseases in India: Status, Interventions, and Future Perspectives - Mamta D. Sharma; Puranjan Mishra; Aaliya Ali; Pradeep Kumar; Prachi Kapil; Rahul Grover; Rekha Verma; Anita Saini; Saurabh Kulshrestha (Current Microbiology, 2023)

Prediction of isotherm model for alum shale, Denmark by statistical modelling-case study - Sankari Hazarika; Rahul Kumar Singh (Arabian Journal of Geosciences, 2023)

A balancing act: Exploring the interplay between HSPs and osmoprotectants in temperature stress responses - Lopamudra Nayak; Milan Kumar Lal; Rahul Kumar Tiwari; Ravinder Kumar; Priyanka Lal; Ranjan Das; Biswaranjan Behera; Pankaj Thakur; Muhammad Ahsan Altaf; Awadhesh Kumar (South African Journal of Botany, 2023)

PFOS-induced dyslipidemia and impaired cholinergic neurotransmission in developing zebrafish: Insight into its mechanisms - Archisman Mahapatra; Priya Gupta; Anjali Suman; Shubhendu Shekhar Ray; Rahul Kumar Singh (Neurotoxicology and Teratology, 2023)

RETRACTED: Deep insights into kinetics, optimization and thermodynamic estimates of methylene blue adsorption from aqueous solution onto coffee husk (Coffee arabica) activated carbon - Prabu Deivasigamani; P. Senthil Kumar; Sathish Sundaraman; Michael Rahul Soosai; A. Annam Renita; Karthikeyan M; Nessipkhan Bektenov; Omirserik Baigenzhenov; Venkatesan D; Aravind Kumar J (Environmental Research, 2023)

End-use energy projections: Future regional disparity and energy poverty at the household level in rural and urban areas of India - Satish Kumar Yawale; Tatsuya Hanaoka; Manmohan Kapshe; Rahul Pandey (Energy Policy, 2023)

Sustainability issues of solar desalination hybrid systems integrated with heat exchangers for the production of drinking water: A review - Dhananjay Singh; Deepak Singh; Vinay Mishra; Jyoti Kushwaha; Rahul Dev; Suresh Kumar Patel; Ravi Shankar; Balendu Shekher Giri (Desalination, 2023)

Per-and polyfluoroalkyl substances (PFAS) as a health hazard: Current state of knowledge and strategies in environmental settings across Asia and future perspectives - Karuna Singh; Naresh Kumar; Asheesh Kumar Yadav; Rahul Singh; Kapil Kumar (Chemical Engineering Journal, 2023)

Adsorptive removal of ciprofloxacin and sulfamethoxazole from aqueous matrices using sawdust and plastic waste-derived biochar: A sustainable fight against antibiotic resistance - Rahul Silori; Jian Zang; Nirav P. Raval; Balendu Shekher Giri; Jürgen Mahlknecht; Abrahan Mora; Jaime Dueñas-Moreno; Syed Mohammad Tauseef; Manish Kumar (Bioresource Technology, 2023)

Profiling of conserved orthologs and miRNAs for understanding their role in salt tolerance mechanism of Sesuvium portulacastrum L. - Ganesh Chandrakant Nikalje; Ashish Kumar Srivastava; Rahul Mahadev Shelake; Ulhas Sopanrao Kadam; Jong Chan Hong; Jae-Yean Kim; T. D. Nikam; Penna Suprasanna (Molecular Biology Reports, 2023)

Fabrication of a New Coumarin Based Fluorescent “turn-on” Probe for Distinct and Sequential Recognition of Al3+ and F− Along With Its Application in Live Cell Imaging - Atanu Maji; Rahul Naskar; Debarpan Mitra; Saswati Gharami; Nabendu Murmu; Tapan Kumar Mondal (Journal of Fluorescence, 2023)

Comparative analysis of VMT genes/proteins in selected plant species with emphasis on bread wheat (Triticum aestivum L.) - Hemant Sharma; Shayaba; Rahul Kumar; Jitendra Kumar; Deepa Bhadana; Ritu Batra; Rakhi Singh; Sachin Kumar; Joy K Roy; Harindra S. Balyan; Pushpendra K. Gupta (Genes & Genomics, 2023)

Silica sources for arsenic mitigation in rice: machine learning-based predictive modeling and risk assessment - Rubina Khanam; Amaresh Kumar Nayak; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Rahul Tripathy; Pratap Bhattacharyya; Panneer Selvam; Sushmita Munda; Sivashankari Manickam; Manish Debnath; Raghavendra Goud Bandaru (Environmental Science and Pollution Research, 2023)

Snowmelt influence on phenological events of herbaceous plants in alpine region of West Himalaya - Rahul Kumar; Bhupendra S. Adhikari (Brazilian Journal of Botany, 2023)

Characteristics and application of animal byproduct-based films and coatings in the packaging of food products - Rahul Thakur; R. Santhosh; Yaghuvendra Kumar; Vedsagar Rajesh Suryavanshi; Harshi Singhi; D. Madhubabu; Suranga Wickramarachchi; Kunal Pal; Preetam Sarkar (Trends in Food Science & Technology, 2023)

The two faces of DJ-1D proteins - Priya Gambhir; Arun Kumar Sharma; Rahul Kumar (Trends in Plant Science, 2023)

Polystyrene microplastics disrupt female reproductive health and fertility via sirt1 modulation in zebrafish (Danio rerio) - Priya Gupta; Archisman Mahapatra; Anjali Suman; Shubhendu Shekhar Ray; Guilherme Malafaia; Rahul Kumar Singh (Journal of Hazardous Materials, 2023)

Consumer preference for nutrition front-of-pack-label formats in India: Evidence from a large-scale experimental survey - Ranjan Kumar Ghosh; Rahul Sanghvi; Arvind Sahay (Food Quality and Preference, 2023)

Prevalence of Endocrine Disrupting Chemicals in the urban wastewater treatment systems of Dehradun, India: Daunting presence of Estrone - Rahul Silori; Manish Kumar; Durga Madhab Mahapatra; Pinakshi Biswas; Bhanu Prakash Vellanki; Jürgen Mahlknecht; Syed Mohammad Tauseef; Damia Barcelo (Environmental Research, 2023)

An emerging expanse: Novel and eco-friendly-biogenic synthesis of E. cardamomum-wrapped TiO2 nanoparticles for environmental and biological applications - Harpreet Kaur; Sanjeev Kumar; Gaganpreet Kaur; Navjot Kaur; Rahul Badru; Rahul Saini (Environmental Research, 2023)

Bioenergy with carbon capture, storage and utilization: Potential technologies to mitigate climate change - Prabakaran Ganeshan; Vigneswaran V S; Sarath C. Gowd; Rahul Mishra; Ekta Singh; Aman Kumar; Sunil Kumar; Arivalagan Pugazhendhi; Karthik Rajendran (Biomass and Bioenergy, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

In Vitro and In Vivo Studies on the Efficacy of Zinc-Oxide and Selenium Nanoparticle in Cryopreserved Goat (Capra hircus) Spermatozoa - Sayed Nabil Abedin; Anubha Baruah; Kishore Kumar Baruah; Govindasamy Kadirvel; Rahul Katiyar; Gautam Khargharia; Arundhati Bora; Devo Jyoti Dutta; Sudip Sinha; Shantanu Tamuly; Arundhati Phookan; Sourabh Deori (Biological Trace Element Research, 2023)

Generative Adversarial Networks in Medicine: Important Considerations for this Emerging Innovation in Artificial Intelligence - Phani Srivatsav Paladugu; Joshua Ong; Nicolas Nelson; Sharif Amit Kamran; Ethan Waisberg; Nasif Zaman; Rahul Kumar; Roger Daglius Dias; Andrew Go Lee; Alireza Tavakkoli (Annals of Biomedical Engineering, 2023)

A critical review on sustainable hazardous waste management strategies: a step towards a circular economy - Ashutosh Kumar; Amit K. Thakur; Gajendra Kumar Gaurav; Jiří Jaromír Klemeš; Vishal Kumar Sandhwar; Kamal Kishore Pant; Rahul Kumar (Environmental Science and Pollution Research, 2023)
Globally, industrialisation and urbanisation have led to the generation of hazardous waste (HW). Sustainable hazardous waste management (HWM) is the need of the hour for a safe, clean, and eco-friendly environment and public health. The prominent waste management strategies should be aligned with circular economic models considering the economy, environment, and efficiency. This review critically discusses HW generation and sustainable management with the strategies of prevention, reduction, recycling, waste-to-energy, advanced treatment technology, and proper disposal. In this regard, the major HW policies, legislations, and international conventions related to HWM are summarised. The global generation and composition of hazardous industrial, household, and e-waste are analysed, along with their environmental and health impacts. The paper critically discusses recently adapted management strategies, waste-to-energy conversion techniques, treatment technologies, and their suitability, advantages, and limitations. A roadmap for future research focused on the components of the circular economy model is proposed, and the waste management challenges are discussed. This review stems to give a holistic and broader picture of global waste generation (from many sources), its effects on public health and the environment, and the need for a sustainable HWM approach towards the circular economy. The in-depth analysis presented in this work will help build cost-effective and eco-sustainable HWM projects.

One-pot biogenic synthesis of C. limon/TiO2 with dual applications as an advance photocatalyst and antimicrobial agent - Harpreet Kaur; Sanjeev Kumar; Rahul Saini; Prit Pal Singh; Arivalagan Pugazhendhi (Chemosphere, 2023)

Corrigendum to “Sphingomonas pokkalii sp. nov., a novel plant associated rhizobacterium isolated from a saline tolerant pokkali rice and its draft genome analysis” [Syst. Appl. Microbiol. 42(3) (2019) 334–342] - Rahul R. Menon; Sunitha Kumari; Pravin Kumar; Ashish Verma; Srinivasan Krishnamurthi; N. Rameshkumar (Systematic and Applied Microbiology, 2023)

Corrigendum to Ecological survey, population assessment and habitat distribution modelling for conserving Fritillaria roylei—A critically endangered Himalayan medicinal herb, South African Journal of Botany, Volume 160, September 2023, Pages 75-87 - Rahul Chandora; Shiv Paul; Kanishka RC; Pankaj Kumar; Badal Singh; Pradeep Kumar; Abhay Sharma; Amit Kumar; Dayal Singh; Narender Negi; Swaran Lata; Mohar Singh (South African Journal of Botany, 2023)

Harnessing unexplored medicinal values of the red listed South African weed Erigeron bonariensis: From ethnobotany to biomedicine - Vishal B. Mahanur; Rahul R. Rajge; Rashmi Saxena Pal; M.V.N.L. Chaitanya; Sukriti Vishwas; Saurabh Gupta; Gaurav Gupta; Deepak Kumar; Oluwafemi Omoniyi Oguntibeju; Zia ur Rehman; Faris F. Aba Alkhayl; Vinay Thakur; et al. (South African Journal of Botany, 2023)

Ecological survey, population assessment and habitat distribution modelling for conserving Fritillaria roylei—A critically endangered Himalayan medicinal herb - Rahul Chandora; Shiv Paul; Kanishka RC; Pankaj Kumar; Badal Singh; Pradeep Kumar; Abhay Sharma; Amit Kumar; Dayal Singh; Narender Negi; Swaran Lata; Mohar Singh (South African Journal of Botany, 2023)

Mapping smallholder cashew plantations to inform sustainable tree crop expansion in Benin - Leikun Yin; Rahul Ghosh; Chenxi Lin; David Hale; Christoph Weigl; James Obarowski; Junxiong Zhou; Jessica Till; Xiaowei Jia; Nanshan You; Troy Mao; Vipin Kumar; et al. (Remote Sensing of Environment, 2023)

Instant controlled pressure drop drying: A review on preservation of quality characteristics in fresh produce - Roji Waghmare; Paulo E.S. Munekata; Manoj Kumar; Sona R. Moharir; Rahul Yadav; Kuldeep Dhama; José M. Lorenzo (Food Chemistry, 2023)

Biostimulants and environmental stress mitigation in crops: A novel and emerging approach for agricultural sustainability under climate change - Sayanti Mandal; Uttpal Anand; José López-Bucio; Radha; Manoj Kumar; Milan Kumar Lal; Rahul Kumar Tiwari; Abhijit Dey (Environmental Research, 2023)

Polystyrene microplastics modulated bdnf expression triggering neurotoxicity via apoptotic pathway in zebrafish embryos - Anjali Suman; Archisman Mahapatra; Priya Gupta; Shubhendu Shekhar Ray; Rahul Kumar Singh (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Eco-friendly warm mix asphalt mixtures incorporating electric arc furnace steel slag as substitute to conventional aggregates - G. Shiva Kumar; M. S. Rahul; Suraj S. Jakati; M. Karthik; H. K. Ramaraju (Innovative Infrastructure Solutions, 2023)

RNA-seq analysis reveals an early defense response to tomato leaf curl New Delhi virus in potato cultivar Kufri Bahar - Arjunan Jeevalatha; Sundaresha Siddappa; Ravinder Kumar; Rahul Kumar Tiwari; Milan Kumar Lal; Sanjeev Sharma; Swarup Kumar Chakrabarti; Bir Pal Singh (Functional & Integrative Genomics, 2023)

Recent Insights on the Role of Various Food Processing Operations Towards the Development of Sustainable Food Systems - Vinay Kumar Pandey; Aamir Hussain Dar; Shubham Rohilla; Charu Lata Mahanta; Rafeeya Shams; Shafat Ahmad Khan; Rahul Singh (Circular Economy and Sustainability, 2023)

Valorization of the insect waste as a source of dietary protein in replacing the fishmeal protein for the cage reared Pangasianodon hypophthalmus: An approach to search the alternate non-conventional feed resource of animal origin - Rahul Das; Basanta Kumar Das; Md. Abul Hassan; Gopal Krishna; Narinder Kumar Chadha; Kiran Dube Rawat; Karmabeer Jena (Animal Feed Science and Technology, 2023)

First report of ‘Candidatus Phytoplasma australasia’ related strain associated with opium poppy phyllody and stunting in India - Sushil Kumar Singh; R. K. Mishra; M. Gurivi Reddy; S. N. Rahul; Carmine Marcone; Govind P. Rao (Australasian Plant Pathology, 2023)

Effect of sludge amelioration on yield, accumulation and translocation of heavy metals in soybean grown in acid and alkaline soils - Mahipal Choudhary; Siba Prasad Datta; Debasis Golui; Mahesh Chand Meena; Mahaveer Nogiya; Saubhagya Kumar Samal; Mohammed Basit Raza; Mohammad Mahmudur Rahman; Rahul Mishra (Environmental Science and Pollution Research, 2023)

Influence of topographic factors on community parameters in tropical deciduous forests of Eastern India - Rahul Kumar; Gajendra Kumar; Amit Kumar; Purabi Saikia (Vegetos, 2023)

Substantial utilization of food wastes for existence of nanocomposite polymers in sustainable development: a review - Anjali Tripathi; Shivangi Srivastava; Vinay Kumar Pandey; Rahul Singh; Parmjit S. Panesar; Aamir Hussain Dar; Sarvesh Rustagi; Rafeeya Shams; R. Pandiselvam (Environment, Development and Sustainability, 2023)

Unraveling the mechanisms of perfluorooctanesulfonic acid-induced dopaminergic neurotoxicity and microglial activation in developing zebrafish - Archisman Mahapatra; Priya Gupta; Anjali Suman; Shubhendu Shekhar Ray; Guilherme Malafaia; Rahul Kumar Singh (Science of The Total Environment, 2023)

Silencing of SlSPX1 and SlSPX2 promote growth and root mycorrhization in tomato (Solanum lycopersicum L.) seedlings - Naorem Ronald Reagan Singh; Abhishek Roychowdhury; Rajat Srivastava; Akash; Gayathri Areekkare Gaganan; Adwaita Prasad Parida; Rahul Kumar (Plant Science, 2023)

Pharmaceutical waste-water treatment via advanced oxidation based integrated processes: An engineering and economic perspective - Amit K. Thakur; Rahul Kumar; Ashutosh Kumar; Ravi Shankar; Nadeem A. Khan; Kaushal Naresh Gupta; Mahendra Ram; Raj Kumar Arya (Journal of Water Process Engineering, 2023)

Towards a sustainable future: Nexus between the sustainable development goals and waste management in the built environment - Sampriti Roy; Rahul Rautela; Sunil Kumar (Journal of Cleaner Production, 2023)

Association of microplastics with heavy metals and antibiotic resistance bacteria/genes in natural ecosystems - A perspective through science mapping approach - Payal Mazumder; Siddhant Dash; Manish Kumar; Rahul Silori; Ananda Tiwari; Meena Khwairakpam; Ajay S. Kalamdhad (Groundwater for Sustainable Development, 2023)

Non-dairy prebiotics: Conceptual relevance with nutrigenomics and mechanistic understanding of the effects on human health - Rajni Devi; Eshita Sharma; Richa Thakur; Priyanka Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Brajesh Singh; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (Food Research International, 2023)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

Antimicrobial resistance surge in the context of pollution, war, and pandemic - Rahul Silori; Vikalp Shrivastava; Payal Mazumder; Manish Kumar (Current Opinion in Environmental Science & Health, 2023)

Efficient Segmentation Algorithm for Estimation of Revised Reservoir Capacities in Google Earth Engine - Rahul Kumar Jaiswal; Gunja Dhruw; Sukant Jain; Ravi V. Galkate; Anil Kumar Lohani; Akhilesh Verma (Water Resources Management, 2023)

Mapping of QTLs associated with yield and related traits under reproductive stage drought stress in rice using SNP linkage map - Rahul Kaldate; Rahul Kumar Verma; Sanjay Kumar Chetia; Pradip Chandra Dey; Mayuri D. Mahalle; Sushil Kumar Singh; Akhil Ranjan Baruah; Mahendra Kumar Modi (Molecular Biology Reports, 2023)

Phytohormones Mediated Modulation of Abiotic Stress Tolerance and Potential Crosstalk in Horticultural Crops - Muhammad Ahsan Altaf; Rabia Shahid; Ravinder Kumar; Muhammad Mohsin Altaf; Awadhesh Kumar; Latif Ullah Khan; Muhammad Saqib; Muhammad Azher Nawaz; Bushra Saddiq; Saraj Bahadur; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Ingenious enactment of Halimeda macroloba-sourced calcium for the improved agro-active response of Arachis hypogea L. - B. Palani Kumar; V. Sowntharya; V. Muthulaxmi; Kahkashan Perveen; Rahul Datta; S. Yogalakshmi; Sakthivel Venkatesh; Mythili Ravichandran; R. Dineshkumar (Environment, Development and Sustainability, 2023)

Hazardous impacts of glyphosate on human and environment health: Occurrence and detection in food - Deeksha Rawat; Aarti Bains; Prince Chawla; Ravinder Kaushik; Rahul Yadav; Anil Kumar; Kandi Sridhar; Minaxi Sharma (Chemosphere, 2023)

A critical review and future perspective of plastic waste recycling - Rahul Tiwari; Numanuddin Azad; Deblina Dutta; Bholu Ram Yadav; Sunil Kumar (Science of The Total Environment, 2023)

OGF nanocomposite foam for enhanced recyclability and oil-recovery - Dharmveer Yadav; Rahul Kumar Das; Sumit Saxena; Shobha Shukla (Journal of Cleaner Production, 2023)

The prominence of carbon capture, utilization and storage technique, a special consideration on India - Atul Kumar Patidar; Rahul Kumar Singh; Tanupriya Choudhury (Gas Science and Engineering, 2023)

Progress and challenges in electrochemical energy storage devices: Fabrication, electrode material, and economic aspects - Rahul Sharma; Harish Kumar; Gaman Kumar; Saloni Sharma; Ranjan Aneja; Ashok K. Sharma; Ramesh Kumar; Parvin Kumar (Chemical Engineering Journal, 2023)

Traversing the diverse avenues of exopolysaccharides-based nanocarriers in the management of cancer - Priti Paul; Rahul Nair; Srushti Mahajan; Ujala Gupta; Mayur Aalhate; Indrani Maji; Pankaj Kumar Singh (Carbohydrate Polymers, 2023)

Salinity Stress Tolerance in Solanaceous Crops: Current Understanding and Its Prospects in Genome Editing - Muhammad Ahsan Altaf; Sayanti Mandal; Biswaranjan Behera; Vikas Mangal; Safina Naz; Ravinder Kumar; Awadhesh Kumar; Mimosa Ghorai; Brajesh Singh; Abhijit Dey; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

Fabrication, characterization and performance analysis of a two-step arsenic bio-filter column using Delftia spp. BAs29 and fired red mud pellets - Rimi Biswas; S. Rahul; Sumit Kumar Pal; Angana Sarkar (Environmental Geochemistry and Health, 2023)

Recent insights on electrostatic filtration and its potential applications in food industry - Shivangi Srivastava; Vinay Kumar Pandey; Rahul Singh; Aamir Hussain Dar; Iqra Bashir (Trends in Food Science & Technology, 2023)

Exogenous melatonin alleviates cadmium-induced inhibition of growth and photosynthesis through upregulating antioxidant defense system in strawberry - Muhammad Saqib; Umbreen Shahzad; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Safina Naz; Mohammad Shah Jahan; Zoia Arshad Awan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (South African Journal of Botany, 2023)

Deep eutectic solvents for extraction of functional components from plant-based products: A promising approach - Iqra Bashir; Aamir Hussain Dar; Kshirod Kumar Dash; Vinay Kumar Pandey; Ufaq Fayaz; Rafeeya Shams; Shivangi Srivastava; Rahul Singh (Sustainable Chemistry and Pharmacy, 2023)

Paleoclimatic reconstruction of northwest Himalaya since CE 475 using lake sediments from Tadag Taal, Kumaun, India - Arun Kaushik; Anil K. Gupta; Steven C. Clemens; Pankaj Kumar; Prasanta Sanyal; Priyantan Gupta; Manoj Kumar Jaiswal; Abhayanand S. Maurya; Sreya Sengupta; Rajveer Sharma; Rahul Pawar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Carbon and water footprints of major crop production in India - Amaresh Kumar NAYAK; Rahul TRIPATHI; Manish DEBNATH; Chinmaya Kumar SWAIN; Biswaranjan DHAL; Shanmugam VIJAYKUMAR; Anshuman Debasis NAYAK; Sangita MOHANTY; Mohammad SHAHID; Anjani KUMAR; Manoj RAJAK; Khitish Chandra MOHARANA; et al. (Pedosphere, 2023)

Browning of vegetation in efficient carbon sink regions of India during the past two decades is driven by climate change and anthropogenic intrusions - Rahul Kashyap; Jayanarayanan Kuttippurath; Pankaj Kumar (Journal of Environmental Management, 2023)

Screening of pharmaceutical and personal care products (PPCPs) along wastewater treatment system equipped with root zone treatment: A potential model for domestic waste leachate management - Manish Kumar; Rahul Silori; Payal Mazumder; Syed Mohammad Tauseef (Journal of Environmental Management, 2023)

Impact of acetamide, 1,2,4-triazole, and 1-dodecyl-2-pyrrolidinone on carbon dioxide hydrate growth: Application in carbon dioxide capture and sequestration - Rahul Sarkhel; Chandan Sahu; Rajnish Kumar; Jitendra S. Sangwai (Journal of Environmental Chemical Engineering, 2023)

Deciphering the melatonin-mediated response and signalling in the regulation of heavy metal stress in plants - Muhammad Ahsan Altaf; Nitin Sharma; Dipali Srivastava; Sayanti Mandal; Sandeep Adavi; Rupak Jena; Rakesh Kumar Bairwa; Abilash Valsala Gopalakrishnan; Awadhesh Kumar; Abhijit Dey; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Planta, 2023)

First report of powdery mildew of pomegranate (Punica granatum) caused by Erysiphe punicae in India - Santosh Watpade; Kailash Chandra Naga; Kallol Kumar Pramanick; Rahul Kumar Tiwari; Ravinder Kumar; Arun Kumar Shukla; Priyank Hanuman Mhatre; Milan Kumar Lal; Dharam Pal; N. Manjunatha (Journal of Plant Diseases and Protection, 2023)

Tungsten oxide nanostructures peculiarity and photocatalytic activity for the efficient elimination of the organic pollutant - Deepika Jamwal; Vishal Mutreja; Rahul; Surinder Kumar Mehta; Akash Katoch; Sang Sub Kim (Environmental Science and Pollution Research, 2023)

Effect of phosphorous acid on late blight disease mitigation and minimization of fungicide doses under field conditions - Sanjeev Sharma; S. Sundaresha; Rahul Kumar Tiwari; Vinay Sagar; Mehi Lal (Journal of Plant Pathology, 2023)

Delineation of thin and discrete sand reservoir facies from shale-dominated Kopili Formation (Middle to Late Eocene) using the post-stack seismic inversion and neural network algorithm: A case study from Assam Basin, India - Satya Narayan; Rahul Singh; Anand Mohan; Kumar Vivek; Paridhi Acharya; S K Pal (Journal of Earth System Science, 2023)

Highly customized porous TiO2-PANI nanoparticles with excellent photocatalytic efficiency for dye degradation - Harpreet Kaur; Sanjeev Kumar; Sandeep Kaushal; Rahul Badru; Prit Pal Singh; Arivalagan Pugazhendhi (Environmental Research, 2023)

Metabolic footprints in phosphate-starved plants - Abhishek Roychowdhury; Rajat Srivastava; Akash; Gyanesh Shukla; Grigor Zehirov; Kiril Mishev; Rahul Kumar (Physiology and Molecular Biology of Plants, 2023)

Cloning, expression, purification, and immunoblotting analysis of recombinant type III fibronectin domains of human oncostatin M receptor - Rahul Kumar Vempati (Molecular Biology Reports, 2023)

Delineation of agricultural fields in arid regions from Worldview-2 datasets based on image textural properties - Abhishek Adhikari; Rahul Dev Garg; Sunil Kumar Pundir; Anupam Singhal (Environmental Monitoring and Assessment, 2023)

CaCu3Ti4O12 nanoparticle-loaded cotton fabric for dual photocatalytic antibacterial and dye degradation applications - Amit Kumar; Moolchand Sharma; Rahul Vaish (Environmental Science and Pollution Research, 2023)

Metal nanocomposites-based electrochemical sensor for the detection of Vanillin (food additives): Experimental and theoretical approach - Rajni Kumari; Harish Kumar; Ankita Yadav; Rahul Sharma; Anita Kumari; Ashwani Kumar (Food Bioscience, 2023)

A comprehensive and conceptual overview of omics-based approaches for enhancing the resilience of vegetable crops against abiotic stresses - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Vijay Gahlaut; Ashish Bhatt; Ajay Kumar Thakur; Ravinder Kumar; Vinay Bhardwaj; Vinod Kumar; Brajesh Singh; et al. (Planta, 2023)

A holistic review on trend, occurrence, factors affecting pesticide concentration, and ecological risk assessment - Rajeev Pratap Singh; Monika Mahajan; Kavita Gandhi; Pankaj Kumar Gupta; Anita Singh; Prafull Singh; Rahul Kumar Singh; Mohd Kashif Kidwai (Environmental Monitoring and Assessment, 2023)

Particle preparation of pharmaceutical compounds using supercritical antisolvent process: current status and future perspectives - Rahul Kumar; Amit K. Thakur; Gergely Kali; Kancharlapalli Chinaraga Pitchaiah; Raj Kumar Arya; Anurag Kulabhi (Drug Delivery and Translational Research, 2023)

Impact of tillage cum crop establishment methods and nutrient management strategies on wet rice (Oryza sativa L): crop productivity, water footprint, soil health and profitability in typic Ustochrept soils under semi-arid sub-tropical environment - Mandapelli Sharath Chandra; R. K. Naresh; Rajan Bhatt; Manisha; Papita H. Gourkhede; Rahul Kumar; Praveen V. Kadam; Sandeep Gawdiya (Paddy and Water Environment, 2023)

X-linked hyper-immunoglobulin M syndrome harboring a novel CD40-ligand gene mutation: a case report - Rahul Ramachandran; Yamini Krishnan; Parminder Singh; Ashok Kumar; Abhishek Mohanty (Immunogenetics, 2023)

Spatiotemporal evolution of sea ice and its teleconnections with large-scale climate indices over Antarctica - M. Swathi; Avinash Kumar; Rahul Mohan (Marine Pollution Bulletin, 2023)

Late Holocene fire and precipitation history of the Kashmir Himalaya: Inferences from black carbon in lake sediments - Sangeeta Verma; Abdur Rahman; Rayees Ahmad Shah; Rahul Kumar Agrawal; M.G. Yadava; Sanjeev Kumar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Application of ultrasonication as pre-treatment for freeze drying: An innovative approach for the retention of nutraceutical quality in foods - Roji Waghmare; Manoj Kumar; Rahul Yadav; Priyank Mhatre; Sachin Sonawane; Swati Sharma; Yogesh Gat; Deepak Chandran; Radha; Muzaffar Hasan; Abhijit Dey; Tanmay Sarkar; et al. (Food Chemistry, 2023)

Understanding the underestimated: Occurrence, distribution, and interactions of microplastics in the sediment and soil of China, India, and Japan - Rahul Silori; Vikalp Shrivastava; Payal Mazumder; Chandrashekar Mootapally; Ashok Pandey; Manish Kumar (Environmental Pollution, 2023)

Boron fractions and its availability in soils of the Indo-Gangetic plains - Ruma Das; Rahul Kumar; Dibyendu Sarkar; Shrila Das; Amit Kumar Pradhan; Debarup Das; Manoj Srivastava; Abhas K. Sinha; Samaresh Sahoo; S.P. Datta; Biswapati Mandal (CATENA, 2023)

Geoheritage Assessment of a Hermit Cave System at Lakhamandal Valley, Upper Yamuna River Basin, NW Himalaya - Rahul Devrani; Rohit Kumar; Som Dutt; Rongsenzulu Jamir (Geoheritage, 2023)

A review on recovery processes of metals from E-waste: A green perspective - Deblina Dutta; Rahul Rautela; Lohit Kumar Srinivas Gujjala; Debajyoti Kundu; Pooja Sharma; Mamta Tembhare; Sunil Kumar (Science of The Total Environment, 2023)

Modelling extraction kinetics of betalains from freeze dried beetroot powder into aqueous ethanol solutions - Rahul Kumar; Maria Jose Oruna-Concha; Lisa Methven; Keshavan Niranjan (Journal of Food Engineering, 2023)

Enhancement of oxygen vacancy sites of La2-xMxCe2O7-δ (M = Ca, Ba, Sr) catalyst for the low temperature oxidative coupling of Methane: A combined DFT and experimental study - Rohan Singh Pal; Swati Rana; Sachin Kumar Sharma; Rubina Khatun; Deepak Khurana; Tuhin Suvra Khan; Mukesh Kumar Poddar; Rahul Sharma; Rajaram Bal (Chemical Engineering Journal, 2023)

4D nanoprinted sensor for facile organo-arsenic detection: A two-photon lithography-based approach - Sweta Rani; Rahul Kumar Das; Arun Jaiswal; Gaurav Pratap Singh; Ajinkya Palwe; Sumit Saxena; Shobha Shukla (Chemical Engineering Journal, 2023)

Influence of catalase encapsulation on Cobalt@Nanoporous carbon with multiwall shell for supercapacitor and polyurethane synthesis using carbon dioxide - Rahul Patil; Nitish Kumar; Sudip Bhattacharjee; Hsi-Yen Wu; Po-Chun Han; Babasaheb M. Matsagar; Kevin C.W. Wu; Rahul R. Salunkhe; Asim Bhaumik; Saikat Dutta (Chemical Engineering Journal, 2023)

The behavior of cloud base height over a hilly remote station of North-East India using ground-based remote sensing technique - Arundhati Kundu; Shyam S. Kundu; Som Kumar Sharma; Manasi Gogoi; Trisanu Banik; Arup Borgohain; Rahul Mahanta; Anjan Debnath (Atmospheric Research, 2023)

Molecular Insights into the Role of Reactive Oxygen, Nitrogen and Sulphur Species in Conferring Salinity Stress Tolerance in Plants - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Dharmendra Kumar; Vinay Bharadwaj; Brajesh Singh; Rajesh Kumar Singh; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Liquid antisolvent crystallization of pharmaceutical compounds: current status and future perspectives - Rahul Kumar; Amit K. Thakur; Nilanjana Banerjee; Ashutosh Kumar; Gajendra Kumar Gaurav; Raj Kumar Arya (Drug Delivery and Translational Research, 2023)

Development of reservoir module for a distributed conceptual hydrological model - Kallem Sushanth; Rahul Sojitra; Ashok Mishra; Manmohan Kumar Goel; Rajendra Singh (Acta Geophysica, 2023)

Integrated approach for the investigation of groundwater quality through hydrochemistry and water quality index (WQI) - Gopal Krishan; Mohit Kumar; M. Someshwar Rao; Rahul Garg; Brijesh Kumar Yadav; M.L. Kansal; Surjeet Singh; A. Bradley; Marian Muste; L.M. Sharma (Urban Climate, 2023)

Occurrence of Z-drugs, benzodiazepines, and ketamine in wastewater in the United States and Mexico during the Covid-19 pandemic - Sangeet Adhikari; Rahul Kumar; Erin M. Driver; Devin A. Bowes; Keng Tiong Ng; Juan Eduardo Sosa-Hernandez; Mariel Araceli Oyervides-Muñoz; Elda M. Melchor-Martínez; Manuel Martínez-Ruiz; Karina G. Coronado-Apodaca; Ted Smith; Aruni Bhatnagar; et al. (Science of The Total Environment, 2023)

Environmental and economic issues for renewable production of bio-jet fuel: A global prospective - Rahul Tiwari; Rahul Mishra; Akansha Choubey; Sunil Kumar; A.E. Atabani; Irfan Anjum Badruddin; T.M. Yunus Khan (Fuel, 2023)

Bio-hydrogen production through microbial electrolysis cell: Structural components and influencing factors - Rahul Gautam; Jagdeep K. Nayak; Neil V. Ress; Robert Steinberger-Wilckens; Uttam Kumar Ghosh (Chemical Engineering Journal, 2023)

Laboratory set-up for surface hoar layer growth over rounded grain snow - Chaman Chandel; Praveen K. Srivastava; Vinod Kumar; Prem Datt; Rahul Sheoran; P.K. Satayawali (Cold Regions Science and Technology, 2023)

Molecular mapping of drought-responsive QTLs during the reproductive stage of rice using a GBS (genotyping-by-sequencing) based SNP linkage map - Nabarun Roy; Rahul Kumar Verma; Sanjay Kumar Chetia; Vinay Sharma; Priyabrata Sen; Mahendra Kumar Modi (Molecular Biology Reports, 2023)

Applicability of confinement models for SCC jacketed reinforced concrete columns - Japneet Sidhu; Vinay Kumar; Pardeep Kumar; Rahul Dubey (Innovative Infrastructure Solutions, 2023)

Application of concatenated stepped solar still system (CS4) for RO-waste-water purification: an experimental study - Rahul Grewal; Mahesh Kumar (Environmental Science and Pollution Research, 2023)

Ex-situ Evaluation of Chironomid Larvae as a Potential Supplementary Food in Aquaculture - Susanta Nath; Shreya Samanta; Rahul Podder; Lennart Weltje; Biplob Kumar Modak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Identification and characterization of genes for drought tolerance in upland rice cultivar ‘Banglami’ of North East India - Rahul K. Verma; Sanjay K. Chetia; Vinay Sharma; Kamalakshi Devi; Amarendra Kumar; Mahendra K. Modi (Molecular Biology Reports, 2022)

Conservation importance of the strategic, centrally located snow leopard population in the western Himalayas, India: a genetic perspective - Sujeet Kumar Singh; Rahul De; Reeta Sharma; Aishwarya Maheshwari; Bheem Dutt Joshi; Diwakar Sharma; Sambandam Sathyakumar; Bilal Habib; Surendra Prakash Goyal (Mammalian Biology, 2022)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

Notes on Grewia tenax (Forssk.) Fiori: an underutilized multipurpose shrub of hot arid region of western Rajasthan - Anil Patidar; K. Venkatesan; J. P. Singh; Rahul Dev; Pavan Kumar Malav; Mahesh Kumar; S. C. Meena; Archana Sanyal; Mavji Patidar (Genetic Resources and Crop Evolution, 2022)

Land surface temperature distribution in Mahanadi delta: impact of land use land cover change - Rahul Tripathi; Khitish Chandra Moharana; Dibyendu Chatterjee; Manish Debnath; Sangita Mohanty; Anjani Kumar; Shanmugam Vijayakumar; Bhabani Shankar Satapathy; Bandaru Raghavendra Goud; Amaresh Kumar Nayak (Arabian Journal of Geosciences, 2022)

From source to sink: mechanistic insight of photoassimilates synthesis and partitioning under high temperature and elevated [CO2] - Milan Kumar Lal; Nitin Sharma; Sandeep B. Adavi; Eshita Sharma; Muhammad Ahsan Altaf; Rahul Kumar Tiwari; Ravinder Kumar; Awadhesh Kumar; Abhijit Dey; Vijay Paul; Brajesh Singh; Madan Pal Singh (Plant Molecular Biology, 2022)

Mitochondrial cytochrome b indicates the presence of two paraphyletic diverged lineages of the blue sheep Pseudois nayaur across the Indian Himalaya: conservation implications - Bheem Dutt Joshi; Vinay Kumar; Rahul De; Reeta Sharma; Ankita Bhattacharya; Stanzin Dolker; Ranjana Pal; Ved Prakash Kumar; Sambandam Sathyakumar; Bhupendra Singh Adhikari; Bilal Habib; Surendra Prakash Goyal (Molecular Biology Reports, 2022)

Activated Hollow and Solid Carbon Spheres for Enhanced Removal Efficiency of Pharmaceutical Pollutants and Heavy Metals in Water - Devika Laishram; Divya Kumar; Vishav Kant; Bhagirath Saini; Kiran P. Shejale; R. Krishnapriya; Vikash C. Janu; Rahul Singhal; Rakesh K. Sharma (Water, Air, & Soil Pollution, 2022)

Critical parameters for design and development of multivalent nanoconstructs: recent trends - Avijit Kumar Bakshi; Tanweer Haider; Rahul Tiwari; Vandana Soni (Drug Delivery and Translational Research, 2022)

Alterations in bone metabolites with age in C57BL/6 mice model - Dhara Patel; Tae Jin Lee; Sandeep Kumar; Sagar Vyavahare; Alison Worth; William D. Hill; Mark Hamrick; Carlos M. Isales; Rahul S. Shinde; Sadanand Fulzele (Biogerontology, 2022)

Use of activated Chromolaena odorata biomass for the removal of crystal violet from aqueous solution: kinetic, equilibrium, and thermodynamic study - Michael Rahul Soosai; Innasi Muthu Ganesh Moorthy; Perumal Varalakshmi; Asad Syed; Abdallah Mohamed Elgorban; Sean Patrick Rigby; Sivrajasekar Natesan; Sathaiah Gunaseelan; Yonas Camy Joshya; Rajoo Baskar; Rajaram Shyam Kumar; Sankar Karthikumar (Environmental Science and Pollution Research, 2022)

Forest composition regulates above-ground biomass in Sal forests of Ranchi, Eastern India - Rahul Kumar; Amit Kumar; Purabi Saikia (Environmental Sustainability, 2022)

Visible light assisted surface plasmon resonance triggered Ag/ZnO nanocomposites: synthesis and performance towards degradation of indigo carmine dye - Rahul Kumar; Shaileshkumar Y. Janbandhu; Gaurav K. Sukhadeve; Rupesh S. Gedam (Environmental Science and Pollution Research, 2022)

Rainfall partitioning in important multipurpose tree species of Himalayan foothills - Rahul Anand; S. Chaturvedi; Amit Kumar; Salil Tewari; V. K. Sah; V. C. Dhyani; R. Kaushal (Tropical Ecology, 2022)

Current perspective on wastewater treatment using photobioreactor for Tetraselmis sp.: an emerging and foreseeable sustainable approach - Rahul Kumar Goswami; Komal Agrawal; Sanjeet Mehariya; Pradeep Verma (Environmental Science and Pollution Research, 2022)

Free radical biology in neurological manifestations: mechanisms to therapeutics interventions - Rahul Tripathi; Rohan Gupta; Mehar Sahu; Devesh Srivastava; Ankita Das; Rashmi K Ambasta; Pravir Kumar (Environmental Science and Pollution Research, 2022)

Contrasting prevalence of Wolbachia infection across three key stored product beetles in India - Subramanian Sabtharishi; Sonai Rajan Thangaraj; Graham A. McCulloch; Rahul Kumar Chandel; Sonu Kumar Singh; Mohankumar Subbarayalu (International Journal of Tropical Insect Science, 2022)

Monitoring and assessment of anthropogenic impacts on water quality by estimating the BMWP and ASPT indices for a headwater stream in Doon Valley, India - Neetu Singh; Binod Kumar Choudhary; Sunil Singh; Rahul Kumar (Sustainable Water Resources Management, 2022)

Insight into melatonin-mediated response and signaling in the regulation of plant defense under biotic stress - Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar; Vikas Mangal; Muhammad Ahsan Altaf; Sanjeev Sharma; Brajesh Singh; Manoj Kumar (Plant Molecular Biology, 2022)

Impact of climate change on runoff regime of the Godavari River in India - Rahul Kumar Singh; Manoj Kumar Jain; Vivek Gupta (Sustainable Water Resources Management, 2022)

Molecular Insights into Therapeutic Potentials of Hybrid Compounds Targeting Alzheimer’s Disease - Ankit Jana; Arkadyuti Bhattacharjee; Sabya Sachi Das; Avani Srivastava; Akshpita Choudhury; Rahul Bhattacharjee; Swagata De; Asma Perveen; Danish Iqbal; Piyush Kumar Gupta; Saurabh Kumar Jha; Shreesh Ojha; et al. (Molecular Neurobiology, 2022)
Alzheimer’s disease (AD) is one of the most complex progressive neurological disorders involving degeneration of neuronal connections in brain cells leading to cell death. AD is predominantly detected among elder people (> 65 years), mostly diagnosed with the symptoms of memory loss and cognitive dysfunctions. The multifarious pathogenesis of AD comprises the accumulation of pathogenic proteins, decreased neurotransmission, oxidative stress, and neuroinflammation. The conventional therapeutic approaches are limited to symptomatic benefits and are ineffective against disease progression. In recent years, researchers have shown immense interest in the designing and fabrication of various novel therapeutics comprised of naturally isolated hybrid molecules. Hybrid therapeutic compounds are developed from the combination of pharmacophores isolated from bioactive moieties which specifically target and block various AD-associated pathogenic pathways. The method of designing hybrid molecules has numerous advantages over conventional multitarget drug development methods. In comparison to in silico high throughput screening, hybrid molecules generate quicker results and are also less expensive than fragment-based drug development. Designing hybrid-multitargeted therapeutic compounds is thus a prospective approach in developing an effective treatment for AD. Nevertheless, several issues must be addressed, and additional researches should be conducted to develop hybrid therapeutic compounds for clinical usage while keeping other off-target adverse effects in mind. In this review, we have summarized the recent progress on synthesis of hybrid compounds, their molecular mechanism, and therapeutic potential in AD. Using synoptic tables, figures, and schemes, the review presents therapeutic promise and potential for the development of many disease-modifying hybrids into next-generation medicines for AD.

Particle Size Reduction Techniques of Pharmaceutical Compounds for the Enhancement of Their Dissolution Rate and Bioavailability - Rahul Kumar; Amit K. Thakur; Pranava Chaudhari; Nilanjana Banerjee (Journal of Pharmaceutical Innovation, 2022)

Native parasitoid complex of the invasive fall armyworm, Spodoptera frugiperda (J. E. Smith) from Northern India - Doddachowdappa Sagar; Sachin S. Suroshe; M. C. Keerthi; J. Poorani; Ankita Gupta; Rahul Kumar Chandel (International Journal of Tropical Insect Science, 2022)

Association mapping, trait variation, interaction and population structure analysis in cucumber (Cucumis sativus L.) - Rahul Kumar; Anilabh Das Munshi; Tusar Kanti Behera; Gograj Singh Jat; Harshawardhan Choudhary; Akshay Talukdar; Prasanta Dash; Deepak Singh (Genetic Resources and Crop Evolution, 2022)

Management of solid waste marble powder: improving quality of sodium chloride obtained from sulphate-rich lake/subsoil brines with simultaneous recovery of high-purity gypsum and magnesium carbonate hydrate - Rahul J. Sanghavi; Sumesh C. Upadhyay; Arvind Kumar (Environmental Science and Pollution Research, 2022)

The alternative sigma factors, rpoN1 and rpoN2 are required for mycophagous activity of Burkholderia gladioli strain NGJ1 - Joyati Das; Rahul Kumar; Sunil Kumar Yadav; Gopaljee Jha (Environmental Microbiology, 2022)
Summary Bacteria utilize RpoN, an alternative sigma factor (σ54) to grow in diverse habitats, including nitrogen‐limiting conditions. Here, we report that a rice‐associated mycophagous bacterium Burkholderia gladioli strain NGJ1 encodes two paralogues of rpoN viz. rpoN1 and rpoN2 . Both of them are upregulated during 24 h of mycophagous interaction with Rhizoctonia solani , a polyphagous fungal pathogen. Disruption of either one of rpoNs renders the mutant NGJ1 bacterium defective in mycophagy, whereas ectopic expression of respective rpoN genes restores mycophagy in the complementing strains. NGJ1 requires rpoN1 and rpoN2 for efficient biocontrol to prevent R. solani to establish disease in rice and tomato. Further, we have identified 17 genes having RpoN regulatory motif in NGJ1, majority of them encode potential type III secretion system (T3SS) effectors, nitrogen assimilation, and cellular transport‐related functions. Several of these RpoN regulated genes as well as certain previously reported T3SS apparatus ( hrcC and hrcN ) and effector ( Bg_9562 and endo‐β‐1 , 3‐glucanase ) encoding genes are upregulated in NGJ1 but not in Δ rpoN1 or Δ rpoN2 mutant bacterium, during mycophagous interaction with R. solani . This highlights that RpoN1 and RpoN2 modulate T3SS, nitrogen assimilation as well as cellular transport systems in NGJ1 and thereby promote bacterial mycophagy.

Assessing Soil Degradation and Risk in Relation to Metal Pollution in Hindon River Water-Irrigated Soils of Western Uttar Pradesh of India - Debasis Golui; Manjunath Dali; Rajendra Singh; Siba Prasad Datta; Jajati Mandal; Prasenjit Ray; Vivek Kumar Trivedi; Anand Kumar Gupta; Rahul Kumar (Water, Air, & Soil Pollution, 2022)

Host SPX-PHR regulatory circuit: the molecular dynamo steering mycorrhization in plants - Rajat Srivastava; Abhishek Roychowdhury; Rahul Kumar (Plant Cell Reports, 2022)

Geospatial technology in agroforestry: status, prospects, and constraints - Prashant Sharma; Daulat Ram Bhardwaj; Manoj Kumar Singh; Rahul Nigam; Nazir A. Pala; Amit Kumar; Kamlesh Verma; Dhirender Kumar; Pankaj Thakur (Environmental Science and Pollution Research, 2022)

Scour depth forecast modeling caused by submerged vertical impinging circular jet: a comparative study between ANN and MNLR - Rahul Shakya; Manendra Singh; V. K. Sarda; Navsal Kumar (Sustainable Water Resources Management, 2022)

Molecular detection and genetic characterization of Coxiella-like endosymbionts in dogs and ticks infesting dogs in Northeast India - Gautam Patra; Subhamoy Ghosh; Shamik Polley; Priyanka; Sonjoy Kumar Borthakur; Om Prakash Choudhary; Rahul Singh Arya (Experimental and Applied Acarology, 2022)

Interpreting the COVID effect on atmospheric constituents over the Indian region during the lockdown: chemistry, meteorology, and seasonality - Rahul Kant; Avani Trivedi; Bibhutimaya Ghadai; Vinod Kumar; Chinmay Mallik (Environmental Monitoring and Assessment, 2022)

SARS-CoV-2-associated haemorrhagic encephalitis mimicking Herpes encephalitis - Rahul Handa; Satyan Nanda; Atul Prasad; Rajiv Anand; Man Mohan Mehndiratta; Dhruv Zutshi; Aarti Pahuja; Rajesh Kumar Pandey; Payal Mittal; Sachal Sharma; Sujata K Dass; Prabhjeet Kaur Bedi; et al. (Journal of NeuroVirology, 2022)

A report on tectonically sculptured unique glacier landform: a case study from the Tethys Kumaun Himalaya, India - Manish Mehta; Rahul Devrani; Khayingshing Luirei; Vinit Kumar (Geosciences Journal, 2022)

Modelling of Moment Tensors and Source Parameters of the 25 July 2021 Rare Lower Crustal Hyderabad (India) Earthquake of Mw 3.9 - Prantik Mandal; Satish Saha; Sudesh Kumar; Sandeep Gupta; Rahul Biswas; Sanjay Kumar; K. Sivaram; B. N. V. Prasad; M. Saidixit; Raju Prathigadapa; Bhoopender Singh; S. Madhusudan (Pure and Applied Geophysics, 2022)

Salinity responses and tolerance mechanisms in underground vegetable crops: an integrative review - Kumar Nishant Chourasia; Sanket Jijabrao More; Ashok Kumar; Dharmendra Kumar; Brajesh Singh; Vinay Bhardwaj; Awadhesh Kumar; Sourav Kumar Das; Rajesh Kumar Singh; Gaurav Zinta; Rahul Kumar Tiwari; Milan Kumar Lal (Planta, 2022)

Physiological and molecular insights on wheat responses to heat stress - Milan Kumar Lal; Rahul Kumar Tiwari; Vijay Gahlaut; Vikas Mangal; Awadhesh Kumar; Madan Pal Singh; Vijay Paul; Sudhir Kumar; Brajesh Singh; Gaurav Zinta (Plant Cell Reports, 2022)

Meta-QTLs, ortho-MetaQTLs and candidate genes for grain Fe and Zn contents in wheat (Triticum aestivum L.) - Rakhi Singh; Gautam Saripalli; Tinku Gautam; Anuj Kumar; Irfat Jan; Ritu Batra; Jitendra Kumar; Rahul Kumar; Harindra Singh Balyan; Shailendra Sharma; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2022)

Biogenic zinc oxide nanoparticles as an antibacterial, antifungal, and photocatalytic tool mediated via leaves of Girardinia diversifolia - Aayasha Negi; Reena Gangwar; Rahul Kumar Vishwakarma; Devendra Singh Negi (Nanotechnology for Environmental Engineering, 2022)

Utilization of nano-sized waste lime sludge particles in harvesting marine microalgae for biodiesel feedstock production - Amit; Navneet Kumar; Swati Verma; Jinsub Park; Amit K. Jaiswal; Uttam Kumar Ghosh; Rahul Gautam (Nanotechnology for Environmental Engineering, 2022)

A molecular insight of inflammatory cascades in rheumatoid arthritis and anti-arthritic potential of phytoconstituents - Vaibhav Patidar; Shruti Shah; Rahul Kumar; Pankaj Kumar Singh; Shashi Bala Singh; Dharmendra Kumar Khatri (Molecular Biology Reports, 2022)

Melatonin Mitigates Cadmium Toxicity by Promoting Root Architecture and Mineral Homeostasis of Tomato Genotypes - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Safina Naz; Muhammad Mohsin Altaf; Latif Ullah Khan; Milan Kumar Lal; Rahul Kumar Tiwari; Awais Shakoor (Journal of Soil Science and Plant Nutrition, 2022)

An Insight into Microbes Mediated Heavy Metal Detoxification in Plants: a Review - Rajni Devi; Biswaranjan Behera; Md Basit Raza; Vikas Mangal; Muhammad Ahsan Altaf; Ravinder Kumar; Awadhesh Kumar; Rahul Kumar Tiwari; Milan Kumar Lal; Brajesh Singh (Journal of Soil Science and Plant Nutrition, 2022)

Mapping of hydrocarbon-bearing reservoirs using frequency-dependent amplitude vs. offset (FAVO) - Shubham Tiwari; Dibakar Ghosal; Rahul Kumar Singh; Subbarao Yelisetti (Journal of Earth System Science, 2022)

Gridded distribution of total suspended particulate matter (TSP) and their chemical characterization over Delhi during winter - Ritu Jangirh; Sakshi Ahlawat; Rahul Arya; Arnab Mondal; Lokesh Yadav; Garima Kotnala; Pooja Yadav; Nikki Choudhary; Martina Rani; Rubiya Banoo; Akansha Rai; Ummed Singh Saharan; et al. (Environmental Science and Pollution Research, 2022)

Calcium-channel-blockers exhibit divergent regulation of cancer extravasation through the mechanical properties of cancer cells and underlying vascular endothelial cells - S. R. Vaibavi; Manoj Sivasubramaniapandian; Rahul Vaippully; Privita Edwina; Basudev Roy; Saumendra Kumar Bajpai (Cell Biochemistry and Biophysics, 2022)

Modelling suspended sediment concentration and discharge relationship using neural network and adaptive neuro-fuzzy inference system - Atul Kumar Rahul; Nikita Shivhare; Sujeet Kumar; Shyam Bihari Dwivedi; Prabhat Kumar Singh Dikshit (Arabian Journal of Geosciences, 2022)

Yield performance & economic evaluation of mustard varieties under mango based Agri-horticulture practice in semi-arid tropics - Ajay Kumar Shah; Anil Kumar Kori; Kailash Kumar; Rahul Dongre (Agroforestry Systems, 2022)

Amorphous systems for delivery of nutraceuticals: challenges opportunities - Devendrasingh Tomar; Pankaj K. Singh; Sajidul Hoque; Sheela Modani; Anitha Sriram; Rahul Kumar; Jitender Madan; Dharmendra Khatri; Kamal Dua (Critical Reviews in Food Science and Nutrition, 2022)

Rapid determination and optimisation of berberine from Himalayan Berberis lycium by soxhlet apparatus using CCD-RSM and its quality control as a potential candidate for COVID-19 - Anil Kumar Katare; Bikarma Singh; Pooja Shukla; Sandeep Gupta; Bishander Singh; Kavya Yalamanchili; Nitin Kulshrestha; Rajendra Bhanwaria; Ashok Kumar Sharma; Sarita Sharma; Sneha; Durga Prasad Mindala; et al. (Natural Product Research, 2022)

First report of dry rot of potato caused by Fusarium proliferatum in India - Rahul Kumar Tiwari; Bishnu Maya Bashyal; V. Shanmugam; Milan Kumar Lal; Ravinder Kumar; Sanjeev Sharma; Kailash Chandra Naga; Kumar Nishant Chourasia; Rashmi Aggarwal (Journal of Plant Diseases and Protection, 2022)

Impact of Land Use and Land Cover Change on Ecosystem Services in Eastern Coast of India - Rahul Tripathi; Khitish Chandra Moharana; Sangita Mohanty; Suchismita Pattnaik; Dibyendu Chatterjee; Chinmaya Kumar Swain; Anjani Kumar; Prafulla Kumar Nayak; Bipin Bihari Panda; Debarti Bhaduri; Sushmita Munda; Rubina Khanam; et al. (International Journal of Environmental Research, 2022)

Influence of silica fume and ground granulated blast furnace slag on the engineering properties of ultra-high-performance concrete - Shubhum Prakash; Sanjay Kumar; Rahul Biswas; Baboo Rai (Innovative Infrastructure Solutions, 2022)

Evaluation of pavement quality concrete prepared with locally available supplementary cementitious materials - Rahul Kumar; Ranja Bandyopadhyaya; Hillol Chakravarty (Innovative Infrastructure Solutions, 2022)

New report of Citrus indica Yu. Tanaka, a wild progenitor species of citrus from Dailong Forest, Manipur, and recommendation for its conservation - Elangbam Julia Devi; Rajendra Kumar Labala; Rakesh Sanabam; Nandeibam Samarjit Singh; Rahul Modak; Huidrom Sunitibala Devi (Genetic Resources and Crop Evolution, 2022)

Asserting the Depleting Groundwater Condition in Coastal Region and Its Relation to River System by Using Remote Sensing and GIS: A Case Study of Rushikulya River Basin, Odisha, India - Nirasindhu Desinayak; Gyan Prakash Satyam; Suren Nayak; Rahul Kumar Singh; Sridevi Jadav; Girija Shankar Behera (Journal of the Indian Society of Remote Sensing, 2022)

Study of fertility restoration and genetic diversity of drought-tolerant breeding lines for hybrid rice (Oryza sativa L.) development - Vijayata Singh; Rahul Priyadarshi; Akhilesh Kumar Singh; Abhinav Jain (Journal of Crop Science and Biotechnology, 2022)

Identification of genomic locations associated with grain micronutrients (iron and zinc) in rice (Oryza sativa L.) - Amit Pippal; Nabin Bhusal; Rahul Kumar Meena; Mahavir Bishnoi; Pratik Istari Bhoyar; Rajinder K. Jain (Genetic Resources and Crop Evolution, 2022)

Calcareous peloids in the north-western Arabian Sea: implications of late Quaternary marine sedimentation and paleoclimate - Vikas Dev; Vishwesh Kumar Pathak; Rahul Dey; Madhurima Mazumder; Ajai Kumar Rai; Siddhartha Sankar Das (Arabian Journal of Geosciences, 2022)

AI-based diagnosis of COVID-19 patients using X-ray scans with stochastic ensemble of CNNs - Ridhi Arora; Vipul Bansal; Himanshu Buckchash; Rahul Kumar; Vinodh J. Sahayasheela; Narayanan Narayanan; Ganesh N. Pandian; Balasubramanian Raman (Physical and Engineering Sciences in Medicine, 2021)

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Phosphorus starvation response dynamics and management in plants for sustainable agriculture - Rajat Srivastava; Suvajit Basu; Rahul Kumar (Journal of Plant Biochemistry and Biotechnology, 2021)

Photocatalytic TiO2/CdS/ZnS nanocomposite induces Bacillus subtilis cell death by disrupting its metabolism and membrane integrity - Naveen Kumar; Anuj Mittal; Monika Yadav; Shankar Sharma; Tarun Kumar; Rahul Chakraborty; Shantanu Sengupta; Nar Singh Chauhan (Indian Journal of Microbiology, 2021)

Complexity analyses of Godavari and Krishna river streamflow using the concept of entropy - Rahul Kumar Singh; Manoj Kumar Jain (Acta Geophysica, 2021)

Infectious spleen and kidney necrosis virus‐associated large‐scale mortality in farmed giant gourami, Osphronemus goramy, in India - Thangaraj Raja Swaminathan; Nithianantham Sundar Raj; Prasannan Geetha Preena; Pravata Kumar Pradhan; Neeraj Sood; Rahul Girish Kumar; Arun Sudhagar; Naresh Kumar Sood (Journal of Fish Diseases, 2021)
Megalocytivirus cause diseases that have serious economic impacts on aquaculture, mainly in East and South‐East Asia. Five primary genotypes are known: infectious spleen and kidney necrosis virus (ISKNV), red sea bream iridovirus (RSIV), turbot reddish body iridovirus (TRBIV), threespine stickleback iridovirus (TSIV) and scale drop disease virus (SDDV). ISKNV‐mediated infectious spleen and kidney necrosis disease (ISKND) is a major viral disease in both freshwater and marine fish species. In this study, we report the isolation of ISKNV from diseased giant gourami, Osphronemus goramy, in India. Transmission electron microscopy of ultrathin sections of kidney and spleen revealed the presence of numerous polygonal naked viral particles having an outer nucleocapsid layer within the cytoplasm of enlarged cells (115–125 nm). Molecular and phylogenetic analyses confirmed the presence of ISKNV and the major capsid protein (MCP) (1,362 bp) gene in the infected fish had a high similarity to the other ISKNV‐I isolates. Moreover, ISKNV was propagated in the Astronotus ocellatus fin (AOF) cell line and further confirmed genotypically. A high mortality rate (60%) was observed in gourami fish injected with ISKNV‐positive tissue homogenate through challenge studies. Considering the lethal nature of ISKNV, the present study spotlights the implementation of stringent biosecurity practices for the proper control of the disease in the country.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Budding Multi-matrix Technology—a Retrospective Approach, Deep Insights, and Future Perspectives - Anitha Sriram; Suma Tangirala; Srividya Atmakuri; Sajid Hoque; Sheela Modani; Saurabh Srivastava; Srushti Mahajan; Indrani Maji; Rahul Kumar; Dharmendra Khatri; Jitender Madan; Pankaj Kumar Singh (AAPS PharmSciTech, 2021)

Glyceraldehyde-3-Phosphate Dehydrogenase Facilitates Macroautophagic Degradation of Mutant Huntingtin Protein Aggregates - Surbhi Chaudhary; Asmita Dhiman; Rahul Dilawari; Gaurav Kumar Chaubey; Sharmila Talukdar; Radheshyam Modanwal; Anil Patidar; Himanshu Malhotra; Chaaya Iyengar Raje; Manoj Raje (Molecular Neurobiology, 2021)

Correction to: WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Synthesis of styryl-linked fused dihydropyridines by catalyst-free multicomponent reactions - Rahul Yadav; Tasneem Parvin; Anoop Kumar Panday; Lokman H. Choudhury (Molecular Diversity, 2021)

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

Transcription factor stoichiometry in cell fate determination - Rahul Kumar; Ajay Kumar Sharma (Journal of Genetics, 2021)

WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Molecular mapping of popping volume QTL in popcorn (Zea maize L.) - Shivani Thakur; Rahul Kumar; Yogesh Vikal; Pritesh Vyas; Imran Sheikh; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2021)

Apatite and zircon fission-track thermochronology constraining the interplay between tectonics, topography and exhumation, Arunachal Himalaya - James Pebam; Vikas Adlakha; A K Jain; R C Patel; Nand Lal; S Singh; Rajeev Kumar; Rahul Devrani (Journal of Earth System Science, 2021)

Correction to: Biomethanol Production from Methane by Immobilized Co-cultures of Methanotrophs - Sanjay K. S. Patel; Rahul K. Gupta; Virendra Kumar; Sanath Kondaveeti; Anurag Kumar; Devashish Das; Vipin Chandra Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2021)

Bromelain and Olea europaea (L.) leaf extract mediated alleviation of benzo(a)pyrene induced lung cancer through Nrf2 and NFκB pathway - Debabrata Majumder; Rahul Debnath; Priyatosh Nath; K. V. Libin Kumar; Mousumi Debnath; Prosun Tribedi; Debasish Maiti (Environmental Science and Pollution Research, 2021)

The enhanced phosphorus use efficiency in phosphate-deficient and mycorrhiza-inoculated barley seedlings involves activation of different sets of PHT1 transporters in roots - Rajat Srivastava; Parul Sirohi; Harsh Chauhan; Rahul Kumar (Planta, 2021)

Structural based screening of potential inhibitors of SMAD4: a step towards personalized medicine for gall bladder and other associated cancers - Rakesh Kumar; Rahul Kumar; Pranay Tanwar (Molecular Diversity, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Potato apical leaf curl disease: current status and perspectives on a disease caused by tomato leaf curl New Delhi virus - Ravinder Kumar; Rahul Kumar Tiwari; Arjunan Jeevalatha; Sundaresha Siddappa; Mohd. Abas Shah; Sanjeev Sharma; Vinay Sagar; Manoj Kumar; Swarup Kumar Chakrabarti (Journal of Plant Diseases and Protection, 2021)

Application of remote sensing for assessment of change in vegetation cover and the subsequent impact on climatic variables - Rahul Mishra; Ekta Singh; Aman Kumar; Sunil Kumar (Environmental Science and Pollution Research, 2021)

Carbon stock potential in Pinus roxburghii forests of Indian Himalayan regions - Munesh Kumar; Amit Kumar; Rahul Kumar; Bobbymoore Konsam; Nazir A. Pala; Jahangeer A. Bhat (Environment, Development and Sustainability, 2021)

First Insights Into the Horizontal Movements of Whale Sharks (Rhincodon typus) in the Northern Arabian Sea - Lucy M. Arrowsmith; Charan Kumar Paidi; Farukhkha Husenkha Bloch; Sajan John; Binod Chandra Choudhury; Rahul Kaul; Ana M. M. Sequeira; Charitha B. Pattiaratchi; Mark G. Meekan (Frontiers in Marine Science, 2021)
Whale sharks off the western coast of India have suffered high levels of fishing pressure in the past, and today continue to be caught in small-scale fisheries as by-catch. Additionally, coastlines in this region host very large and growing human populations that are undergoing rapid development. This exacerbates ongoing anthropogenic threats to this species such as pollution, habitat loss, and ship traffic. For these reasons, there is an urgent need for data on movement patterns of whale sharks in this region of the Indian Ocean. Here, we address this issue by providing the first data on the horizontal movements of whale sharks tagged in the northern Arabian Sea off the western coast of the Indian state of Gujarat. From 2011 to 2017, eight individuals, ranging from 5.4 to 8 m were tagged and monitored using satellite telemetry. Tag retention varied from 1 to 137 days, with the sharks traveling distances of 34 – ∼2,230 km. Six of the eight individuals remained close to their tagging locations, although two sharks displayed wide ranging movements into the Arabian Sea, following frontal zones between water masses of different sea surface temperatures. We explore the relationship between the movement patterns of these whale sharks and the physical and biological processes of the region.

Remediation of noxious pollutants using nano-titania-based photocatalytic construction materials: a review - Lok Pratap Singh; Rahul Kumar Dhaka; Dilshad Ali; Inderjeet Tyagi; Usha Sharma; Srinivasrao Naik Banavath (Environmental Science and Pollution Research, 2021)

Performance analysis of multi-gap V-roughness with staggered elements of solar air heater based on artificial neural network and experimental investigations - Piyush Kumar Jain; Atul Lanjewar; Rahul Jain; Kunj Bihari Rana (Environmental Science and Pollution Research, 2021)

Plant viral vectors: expanding the possibilities of precise gene editing in plant genomes - Stuti Kujur; Muthappa Senthil-Kumar; Rahul Kumar (Plant Cell Reports, 2021)

Cross-amplification of ungulate microsatellite markers in the endemic Indian antelope or blackbuck (Antilope cervicapra) for population monitoring and conservation genetics studies in south Asia - Rahul De; Vinay Kumar; Kumar Ankit; Khursid Alam Khan; Himanshu Kumar; Nirmal Kumar; Bilal Habib; Surendra Prakash Goyal (Molecular Biology Reports, 2021)

Genetics of lodging resistance in chickpea (Cicer arietinum L) - Rahul Raiya; Venkatraman Hegde; Veda Krishnan; Chellapilla Bharadwaj; Shailesh Tripathi; Pradeep Kumar Jain (Euphytica, 2021)

Endophytic Microbial Diversity: A New Hope for the Production of Novel Anti-tumor and Anti-HIV Agents as Future Therapeutics - Aditya Banyal; Vikram Thakur; Rahul Thakur; Pradeep Kumar (Current Microbiology, 2021)

Larger floods of Himalayan foothill rivers sustained flows in the Ghaggar–Hakra channel during Harappan age - Ajit Singh; Vikrant Jain; Michel Danino; Naveen Chauhan; Rahul Kumar Kaushal; Shantamoy Guha; V. N. Prabhakar (Journal of Quaternary Science, 2021)
The human–landform interaction in the region of the Ghaggar–Hakra palaeochannel in the northwest Indo‐Gangetic plains during the Bronze Age Indus/Harappan civilisation (~4.6–3.9 thousand years before the present, ka bp ) remains an enigmatic case due to a paucity of evidence regarding the hydrology of the then existing river. Here, we estimated the palaeohydrology of the foothill Markanda River in the sub‐Himalayan catchment of the Ghaggar–Hakra (G–H) palaeochannel. Our morphology and chronology results show aggradation of a fan (57.7 ka) during the Late Pleistocene and T–1 to T–5 fluvial terraces (13.1 to 6.0 ka) during the terminal Pleistocene to Holocene, and deposition of palaeoflood sediments (3.9–3.8 ka) over the T–3 terraces during the Late Holocene. Considering the known uplift rates along the Himalayan frontal thrust, and our estimated aggradation rates, we derived channel palaeogeometry and calculated peak discharge at the site of palaeoflood deposits. We conclude that the Markanda River's peak discharge was several orders of magnitude higher during the Late Holocene than the modern‐day peak discharge of 100‐year return period. The palaeoflood deposits represent larger flooding of the foothill rivers that sustained flows in the downstream reaches of the Ghaggar–Hakra palaeochannel during the Late Harappan civilisation.

Transfer learning–based ensemble support vector machine model for automated COVID-19 detection using lung computerized tomography scan data - Mukul Singh; Shrey Bansal; Sakshi Ahuja; Rahul Kumar Dubey; Bijaya Ketan Panigrahi; Nilanjan Dey (Medical & Biological Engineering & Computing, 2021)

Normalized Antecedent Precipitation Index Based Model for Prediction of Runoff from Un-Gauged Catchments - Narayan C. Ghosh; Rahul Kumar Jaiswal; Shakir Ali (Water Resources Management, 2021)

Population structure and regeneration status of Shorea robusta and associated trees in Sal forests of Ranchi, Eastern India - Rahul Kumar; Purabi Saikia (Tropical Ecology, 2021)

Correction to: Preparation of high-purity magnesium-ammonium-phosphate fertilizer using sea bittern and industrial waste streams - Rahul J. Sanghavi; Rakesh Dobariya; Sameer Bhatti; Arvind Kumar (Environmental Science and Pollution Research, 2021)

Magnetic properties of surface sediments in Schirmacher Oasis, East Antarctica: spatial distribution and controlling factors - Anish Kumar Warrier; Joju George Sebastian; K. Amrutha; A. S. Yamuna Sali; B. S. Mahesh; Rahul Mohan (Journal of Soils and Sediments, 2021)
Purpose We investigated the magnetic properties (abundance, grain size, and mineralogy) of iron oxides present in Lake L-55 sediments, Schirmacher Oasis, East Antarctica, with an aim to understand their spatial distribution and the underlying mechanisms that control their formation and distribution. Methods Twenty-five surficial sediments retrieved from different parts of Lake L-55 were subjected to the entire range of environmental magnetic (magnetic susceptibility, anhysteretic remanent magnetization (ARM), isothermal remanent magnetization (IRM)) measurements (at different field strengths). Inter-parametric ratios ( χ ARM /SIRM, χ ARM / χ lf , χ ARM / χ fd , IRM 20 mT /SIRM, IRM 20 mT /ARM, S -ratio, L -ratio) provided insights into the magnetic properties (abundance, grain size, and mineralogy of iron oxides). Scanning electron microscopic-energy dispersive X-ray spectroscopic (SEM-EDS) analysis was performed on magnetic extracts from a few sediments. Besides, organic matter (%) was also calculated for the sediment samples. Principal component analysis was performed to gain information on the presence of different components and their relative dominance. Results The iron oxides are strongly magnetic (high values of concentration-dependent parameters). The principal iron oxide is magnetite ( S -ratio > 0.90) which is coarse-grained (multi-domain (MD) and stable single-domain (SSD) grains), and there is no influence of authigenic greigite, bacterial magnetite, and anthropogenic magnetite. The mineralogy is confirmed by SEM-EDS data. The iron oxides are of different grain sizes, and their contribution is in the order of MD > SSD > SP as shown by the principal component analysis. Pedogenic iron oxide minerals seem to be present in the samples whose formation is due to the oxidation of magnetite into hematite. However, they are of SSD size and not SP, suggesting that the intensity of pedogenesis is not sufficient to form SP grains. Conclusion The iron oxide minerals are mainly terrigenous, and the biogenic activity within the lake is not sufficient to modify the ferrimagnetic minerals. Spatial distribution patterns suggest the non-uniform distribution of magnetite/titanomagnetite of varying sizes in the lake basin which is transported by both melt water streams and winds.

A simplified approach for the evaluation of groundwater flow in stream–aquifer interaction - Mamta Saxena; Rahul Kumar Singh (Acta Geophysica, 2021)

Catfishes of the genus Sperata (Pisces:Bagridae) in India - Rahul Girish Kumar; Ravi Charan; Nadumury Pradeep Krishnaprasoon; Valaparambil Saidumohammad Basheer (Journal of Fish Biology, 2021)
DNA barcode data of the South Asian bagrid catfish genus Sperata indicate the presence of at least five species in the Indian subcontinent. Those results, which are supported by morphological data, show a marked increase in species diversity from the recent taxonomic and fishery literature, although each of the five species had been previously named. Two species are restricted to rivers of peninsular India south of the Godavari: Sperata aorides from the Cauvery river basin and S. seenghala from the Krishna river basin. Most literature records of S. seenghala from the Ganges‐Brahmaputra‐Meghna river basins likely refer to S. lamarrii , a species which appears to also be present in the Indus river basin. Some genetic data reported as S. seenghala from the Ganges‐Brahmaputra‐Meghna river basins refer to S. aorella . S. aor is widespread in the Ganges‐Brahmaputra‐Surma river basins in India and Bangladesh, extending southwards to the Godavari river.

Spatio-temporal soil nutrient dynamics and plant species diversity in selected Sal forests of Ranchi, Eastern India - Rahul Kumar; Purabi Saikia (Vegetos, 2021)

Biofortification and bioavailability of Zn, Fe and Se in wheat: present status and future prospects - P. K. Gupta; H. S. Balyan; Shailendra Sharma; Rahul Kumar (Theoretical and Applied Genetics, 2021)

Overexpression of ICE1 gene in mungbean (Vigna radiata L.) for cold tolerance - Gyana Ranjan Rout; Anuradha Bansal; Dhaneswar Swain; Kundansigh Rajpalsingh Jadhao; Rahul G. Shelke; Sanjib Kumar Panda (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Fusarium-nematode wilt disease complexes, etiology and mechanism of development - Mujeebur Rahman Khan; Rahul Kumar Sharma (Indian Phytopathology, 2020)

Phytoplankton diversity in relation to physicochemical attributes and water quality of Mandakini River, Garhwal Himalaya - Rahul Kumar; Rama Kumari; Chandi Prasad; Vijayta Tiwari; Neetu Singh; Swati Mohapatra; Ramchander Merugu; Stanzin Namtak; Akash Deep (Environmental Monitoring and Assessment, 2020)

Review of existing heavy metal contamination indices and development of an entropy-based improved indexing approach - Kunwar Raghvendra Singh; Rahul Dutta; Ajay S. Kalamdhad; Bimlesh Kumar (Environment, Development and Sustainability, 2020)

Review of scientific technology-based solutions for vehicular pollution control - Sunil Gulia; Rahul Tiwari; Saurabh Mendiratta; Satinder Kaur; S. K. Goyal; Rakesh Kumar (Clean Technologies and Environmental Policy, 2020)

Development of transcriptome-wide SSR markers for genetic diversity and structure analysis in Macrotyloma uniflorum (Lam.) Verdc. - Rahul Kumar; Sumeet Parkash Kaundal; Vikas Sharma; Ashutosh Sharma; Gagandeep Singh; Ram Kumar Sharma; Rakesh Kumar Chahota; Tilak Raj Sharma (Physiology and Molecular Biology of Plants, 2020)

Carbon Mineralization and Inorganic Nitrogen Pools under Terminalia chebula Retz.-Based Agroforestry System in Himalayan Foothills, India - Amit Kumar; Gopal Krishna Dwivedi; Salil Tewari; Jai Paul; Rahul Anand; Narendra Kumar; Parmanand Kumar; Hukum Singh; Rajesh Kaushal (Forest Science, 2020)
Soil organic matter is major terrestrial pool for soil organic carbon (C) and nitrogen (N), and their decomposition is sensitive to vegetation and climate change. Integrated nutrient management (INM) deals with the combined application of chemical fertilizers and organic manures for nutritional requirement of crops and avoid the adverse effect of long-term application of chemical fertilizer on crop production and their sustainability. The present study was carried out to investigate the influence of different nutrient sources on soil C mineralization and inorganic N pools in a Terminalia chebula Retz, based on a agroforestry system. The results showed that the highest CO2 evolution was recorded in 100 percent INM and minimum in farmyard manure treatment after 120 days of incubation. Inorganic N was higher under the agroforestry system than under the open system. Among the different nutrient sources, the highest inorganic N was recorded in a 100 percent INM nutrient source and minimal in wheat straw treatment. The yield of turmeric was higher under the T. chebula-based agroforestry system (20.87 t ha–1) than under the open system (19.27 t ha–1). Results suggest that agroforestry systems using the INM approach can enhance C mineralization and inorganic N concentration with improved crop productivity in the Himalayan foothills. Study Implications: Fertilizer has been used since ancient times, and if well managed it can be an asset, promoting sustainable agriculture and increasing crop production, particularly for smallholder farmers in the Himalayan region of India. We compared fertilizer application practices under an agroforestry system in a representative Himalayan region of India. The majority of farmers in the region of the Himalayan foothills having marginal land and they are not able to produce optimum food grains for their requirement. However, their demands are increasing day by day, so to fulfill their demand, they have to adopt agroforestry. Agroforestry may be fulfilling their demand in terms of food, fuel, fodder, and other intangible benefits. Moreover, to increase the production under agroforestry, we have to apply organic and inorganic fertilizer in the soil either as the sole application or as a combination of these fertilizers. The application of these fertilizers will improve the productivity and fertility of land, especially carbon mineralization and inorganic nitrogen. These two soil properties are important to study because these are limiting to land productivity. In addition, efforts to improve integrated nutrient management in the Himalayan region of India would strengthen farmers’ incomes by strengthening land fertility and productivity. The rapid increase in human population over the last century is putting a massive pressure on existing resources, namely soil and water, resulting in environmental degradation in some regions around the world. As productive land becomes scarce, marginalized farmers are pushed into fragile croplands and forest lands unsuitable for modern agriculture which, in turn, is vulnerable, to degradation. If the present trend in population growth persists, pasture and forest lands will be further reduced (Satterthwaite et al. 2010). At this stage, the value of growing trees becomes more significant, and participation in tree planting schemes should be encouraged. However, this option is most feasible when combined with agriculture. As a result, agroforestry is an important management strategy that not only helps to meet the world food requirements but also helps to protect soil from degradation (Ram et al. 2017) and can enhance soil organic matter levels by adding the quantity of above- and below-ground organic matter inputs to soils (Nair et al. 2009, Marone et al. 2017).

Application of WQI for water quality assessment of high-altitude snow-fed sacred Lake Hemkund, Garhwal Himalaya - Akash Deep; Vidhu Gupta; Lalita Bisht; Rahul Kumar (Sustainable Water Resources Management, 2020)

Detection of New Delhi Metallo-β-lactamase 1 and Cephalosporin Resistance Genes Among Carbapenem-Resistant Enterobacteriaceae in Water Bodies Adjacent to Hospitals in India - Sneha Girijan Kalasseril; Rahul Krishnan; Rejish Kumar Vattiringal; Robin Paul; Philip Mathew; Devika Pillai (Current Microbiology, 2020)

Partitioning of eddy covariance-measured net ecosystem exchange of CO2 in tropical lowland paddy - Sumanta Chatterjee; Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Pratap Bhattacharyya; Smruthi Sagarika Mahapatra; Manish Debnath; Rahul Tripathi; Prabhat Kumar Guru; Biswaranjan Dhal (Paddy and Water Environment, 2020)

Autophagy-Inducing Inhalable Co-crystal Formulation of Niclosamide-Nicotinamide for Lung Cancer Therapy - Eupa Ray; Kalpesh Vaghasiya; Ankur Sharma; Rahul Shukla; Rehan Khan; Anil Kumar; Rahul Kumar Verma (AAPS PharmSciTech, 2020)

Dramatic decline of Arctic sea ice linked to global warming - Juhi Yadav; Avinash Kumar; Rahul Mohan (Natural Hazards, 2020)

Introgression of powdery mildew resistance from Aegilops triuncialis into wheat through induced homeologous pairing - Robinsh Kamboj; Sushma Sharma; Rahul Kumar; Prachi Sharma; Vikas Kumar Ravat; Parveen Chhuneja; Pritesh Vyas; Imran Sheikh; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Two-Photon-Induced Fluorescence Study of Rhodamine-6G Dye in Different Sets of Binary Solvents - Rahul Kumar Gupta; Surya Kant; Ashwini Kumar Rawat; Debabrata Goswami (Journal of Fluorescence, 2020)

Biomethanol Production from Methane by Immobilized Co-cultures of Methanotrophs - Sanjay K. S. Patel; Rahul K. Gupta; Virendra Kumar; Sanath Kondaveeti; Anurag Kumar; Devashish Das; Vipin Chandra Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2020)

Protein Kinase Inhibitors Arrested the In-Vitro Growth of Theileria equi - Jyotika Yadav; Praveen Goel; Kruti Debnath Mandal; Rahul Yadav; Naveen Kumar; Rajender Kumar; B. N. Tripathi; Sanjay Kumar (Acta Parasitologica, 2020)

Bardoxolone Methyl Ameliorates Hyperglycemia Induced Mitochondrial Dysfunction by Activating the keap1-Nrf2-ARE Pathway in Experimental Diabetic Neuropathy - Anil Kumar Kalvala; Rahul Kumar; Bhoomika Sherkhane; Chayanika Gundu; Vijay Kumar Arruri; Ashutosh Kumar (Molecular Neurobiology, 2020)

Impact of rainfall variability on the ecophysiology of Hyptis suaveolens: a study in the constructed tropical grassland - Talat Afreen; Vartika Singh; Vinod Kumar Yadav; Rahul Prasad Singh; Hema Singh (Environmental Monitoring and Assessment, 2020)

Aquatic plant diversity and physicochemical characteristics of headwater stream Bal Ganga, Garhwal Himalaya - Rahul Kumar; Chandi Prasad; Stanzin Namtak; Vishav Kirti; Rifat Azam; Anushka Sharma (Environment, Development and Sustainability, 2020)

Genetics of yield, abiotic stress tolerance and biofortification in wheat (Triticum aestivum L.) - Pushpendra Kumar Gupta; Harindra Singh Balyan; Shailendra Sharma; Rahul Kumar (Theoretical and Applied Genetics, 2020)

Understanding the Oral Absorption of Irbesartan Using Biorelevant Dissolution Testing and PBPK Modeling - Navpreet Kaur; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2020)

An Approach to Measure the Biomass of Bloodworms (Diptera: Chironomidae) in Different Nutrients - Rahul Podder; Susanta Nath; Biplob Kumar Modak (Proceedings of the Zoological Society, 2020)

The Potato Tuber Moth, Phthorimaea operculella (Zeller), in India: Biology, Ecology, and Control - R. S. Chandel; Sumit Vashisth; Saurbh Soni; Rahul Kumar; Vinod Kumar (Potato Research, 2020)

Preparation of high-purity magnesium-ammonium-phosphate fertilizer using sea bittern and industrial waste streams - Rahul J. Sanghavi; Rakesh Dobariya; Sameer Bhatti; Arvind Kumar (Environmental Science and Pollution Research, 2020)

Water balance modeling of Tandula (India) reservoir catchment using SWAT - Rahul Kumar Jaiswal; Ram Narayan Yadav; Anil Kumar Lohani; Hari Lal Tiwari; Shalini Yadav (Arabian Journal of Geosciences, 2020)

Trend analysis of river flow and groundwater level for Shipra river basin in India - Ravi Venkatrao Galkate; Shalini Yadav; Rahul Kumar Jaiswal; Ram Narayan Yadava (Arabian Journal of Geosciences, 2020)

Estimation of behavioral change of SSC of bed profile in the river using ADCP - Atul Kumar Rahul; Nikita Shivhare; Shyam Bihari Dwivedi; Prabhat Kumar Singh Dikshit (Arabian Journal of Geosciences, 2020)

Most Variable Genes and Transcription Factors in Acute Lymphoblastic Leukemia Patients - Anil Kumar Tomar; Rahul Agarwal; Bishwajit Kundu (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Concurrent overexpression of rice G-protein β and γ subunits provide enhanced tolerance to sheath blight disease and abiotic stress in rice - Durga Madhab Swain; Ranjan Kumar Sahoo; Ravindra Kumar Chandan; Srayan Ghosh; Rahul Kumar; Gopaljee Jha; Narendra Tuteja (Planta, 2019)

Genome-wide identification and expression analysis of Hsp70, Hsp90, and Hsp100 heat shock protein genes in barley under stress conditions and reproductive development - Reeku Chaudhary; Vinay K Baranwal; Rahul Kumar; Debabrata Sircar; Harsh Chauhan (Functional & Integrative Genomics, 2019)

Application of WQI for assessment of water quality of high altitude lake Dodi Tal, Garhwal Himalaya, India - Rahul Kumar; Sushma Singh; Ramesh C. Sharma (Sustainable Water Resources Management, 2019)

Influence of Metal Ions on the Immobilization of β-Glucosidase Through Protein-Inorganic Hybrids - Sanjay K. S. Patel; Rahul K. Gupta; Virendra Kumar; Primata Mardina; Rowina Lestari; Vipin C. Kalia; Myung-Seok Choi; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Alginate Microspheres Elicit Innate M1-Inflammatory Response in Macrophages Leading to Bacillary Killing - Kalpesh Vaghasiya; Aisha Eram; Ankur Sharma; Eupa Ray; Suneera Adlakha; Rahul Kumar Verma (AAPS PharmSciTech, 2019)

Assessment of Biopharmaceutical Performance of Supersaturating Formulations of Carbamazepine in Rats Using Physiologically Based Pharmacokinetic Modeling - Samarth D. Thakore; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Ajit S. Narang; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2019)

Insecticidal fern protein Tma12 is possibly a lytic polysaccharide monooxygenase - Sunil K. Yadav; Archana; Rahul Singh; Pradhyumna Kumar Singh; Prema G. Vasudev (Planta, 2019)

Reliability Analysis of Slope Safety Factor by Using GPR and GP - Pijush Samui; Rahul Kumar; Uttam Yadav; Sunita Kumari; Dieu Tien Bui (Geotechnical and Geological Engineering, 2019)

Characterization of land surface energy fluxes in a tropical lowland rice paddy - Dibyendu Chatterjee; Rahul Tripathi; Sumanta Chatterjee; Manish Debnath; Mohammad Shahid; Pratap Bhattacharyya; Chinmaya Kumar Swain; Rojalin Tripathy; Bimal K. Bhattacharya; Amaresh Kumar Nayak (Theoretical and Applied Climatology, 2019)

Expression of an endo α-1, 3-Glucanase gene from Trichoderma harzianum in rice induces resistance against sheath blight - Rahul Kumar; Kumkum Kumari; Krushna C. Hembram; Laxman Kandha; Birendra Kumar Bindhani (Journal of Plant Biochemistry and Biotechnology, 2019)

Evaluation and correlation of oxidative stress and haemato-biochemical observations in horses with natural patent and latent trypanosomosis in Punjab state of India - Rahul Parashar; Lachhman Das Singla; Mayank Gupta; Suresh Kumar Sharma (Acta Parasitologica, 2018)
The haemato-biochemical indices and oxidative stress markers in horses naturally infected with Trypanosoma evansi were evaluated by analyzing the level of these parameters between T. evansi infected (microscopically positive patent group and PCR positive latent group) and infection free horses. To compare the hemato-biochemical indices and oxidative stress indicators, horses were divided into three categories based on diagnostic test employed and positive results obtained. These included Romanowsky stained slide positive group (Group I; n = 6), PCR positive group (group II; n = 28) and negative control group (group III, n = 30), revealing parasitologically positive patent, molecular positive latent and disease free status of horses. A significant reductions in total erythrocytes count (TEC, P = 0.01), haemoglobin (Hb, P = 0.01) and packed cell volume (PCV, P = 0.04) was noticed both in group I and group II while significant neutrophilia and lymphocytopenia was observed in group I when compared to negative control group. Substantial increase in creatinine (CRTN, P = 0.032) and gamma glutamyl transferase (GGT, P = 0.012) in group I while significant decrease in glucose (GLU, P = 0.04) and iron (Fe, P = 0.01) were noticed in both group I and group II in comparison to group III. A significant difference in lipid peroxides (LPO, P = 0.01) with highest level in patent group I (15.33 ± 0.53) followed by PCR positive latent group (14.09 ± 1.66) indicates higher lipid peroxidation in erythrocytes and oxidative stress in decreasing order when compared with infection free control horses (9.83 ± 0.97). Catalase (CAT, P = 0.01) was significantly lower in parasitological (0.82 ± 0.14) and molecular positive cases (1.27 ± 0.35) in comparison to control group (3.43 ± 0.96). The levels of superoxide dismutase (SOD, P = 0.01), reduced glutathione (GSH, P = 0.01) and ferric reducing antioxidant power (FRAP, P = 0.01) were significantly lower in parasito-molecular positive cases as compared to infection free control horses. An inverse correlation of RBC count with LPO and GSH and a direct correlation with catalase, SOD and FRAP was revealed. Overall, the observed substantial decreases in the oxidative parameters like catalase CAT, SOD, GSH and FRAP activities with remarkably elevated levels of LPO indicate high exposure of erythrocytes to oxidative damage in T.evansi infected horses.

Genome-wide analysis of genes encoding MBD domain-containing proteins from tomato suggest their role in fruit development and abiotic stress responses - Adwaita Prasad Parida; Utkarsh Raghuvanshi; Amit Pareek; Vijendra Singh; Rahul Kumar; Arun Kumar Sharma (Molecular Biology Reports, 2018)

Polybrominated diphenyl ethers (PBDEs) in core sediments from creek ecosystem: occurrence, geochronology, and source contribution - Mahesh Tiwari; Sanjay Kumar Sahu; Rahul C. Bhangare; P. Y. Ajmal; Gauri Girish Pandit (Environmental Geochemistry and Health, 2018)

A ripening-induced SlGH3-2 gene regulates fruit ripening via adjusting auxin-ethylene levels in tomato (Solanum lycopersicum L.) - Thula Sravankumar; Akash; NandKiran Naik; Rahul Kumar (Plant Molecular Biology, 2018)

Using multi-source data and decision tree classification in mapping vegetation diversity - Gaurav Shukla; Rahul Dev Garg; Pradeep Kumar; Hari Shanker Srivastava; Pradeep Kumar Garg (Spatial Information Research, 2018)

Orcinol Glucoside Loaded Polymer - Lipid Hybrid Nanostructured Lipid Carriers: Potential Cytotoxic Agents against Gastric, Colon and Hepatoma Carcinoma Cell Lines - Prasant Nahak; Rahul L. Gajbhiye; Gourab Karmakar; Pritam Guha; Biplab Roy; Shila Elizabeth Besra; Alexey G. Bikov; Alexander V. Akentiev; Boris A. Noskov; Kaushik Nag; Parasuraman Jaisankar; Amiya Kumar Panda (Pharmaceutical Research, 2018)

Sugarcane ratoon discrimination using LANDSAT NDVI temporal data - Sandeep Kumar Singla; Rahul Dev Garg; Om Prakash Dubey (Spatial Information Research, 2018)

Boron application improves yield of rice cultivars under high temperature stress during vegetative and reproductive stages - Mohammad Shahid; Amaresh Kumar Nayak; Rahul Tripathi; Jawahar Lal Katara; Priyanka Bihari; Banwari Lal; Priyanka Gautam (International Journal of Biometeorology, 2018)

Greenhouse gas emissions and energy exchange in wet and dry season rice: eddy covariance-based approach - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Pratap Bhattacharyya; Dibyendu Chatterjee; Sumanta Chatterjee; Rahul Tripathi; Nihar Ranjan Singh; B. Dhal (Environmental Monitoring and Assessment, 2018)

Distribution, movements, and survival of the critically endangered Bengal Florican Houbaropsis bengalensis in India and Nepal - Rohit R. S. Jha; Jyotendra Jyu Thakuri; Asad R. Rahmani; Maheshwar Dhakal; Ngulkholal Khongsai; Narendra Man Babu Pradhan; Nikhil Shinde; Bridesh Kumar Chauhan; Rahul K. Talegaonkar; Ian P. Barber; Graeme M. Buchanan; Toby H. Galligan; et al. (Journal of Ornithology, 2018)

Impact of Shewanella oneidensis on heavy metals remobilization under reductive conditions in soil of Guilan Province, Iran - Nasrin Ghorbanzadeh; Rahul Kumar; Sang-hun Lee; Hyun-Sung Park; Byong-Hun Jeon (Geosciences Journal, 2018)

Measuring potassium fractions is not sufficient to assess the long-term impact of fertilization and manuring on soil’s potassium supplying capacity - Debarup Das; Amaresh Kumar Nayak; V. K. Thilagam; Dibyendu Chatterjee; M. Shahid; Rahul Tripathi; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; B. B. Panda; S. S. Biswas (Journal of Soils and Sediments, 2018)

An effective implementation and assessment of a random forest classifier as a soil spatial predictive model - Gaurav Shukla; Rahul Dev Garg; Hari Shanker Srivastava; Pradeep Kumar Garg (International Journal of Remote Sensing, 2018)

5-LOX in Alzheimer’s Disease: Potential Serum Marker and In Vitro Evidences for Rescue of Neurotoxicity by Its Inhibitor YWCS - Shashank Shekhar; Saroj Kumar Yadav; Nitish Rai; Rahul Kumar; Yudhishthir Yadav; Manjari Tripathi; Aparajit B. Dey; Sharmistha Dey (Molecular Neurobiology, 2018)

Evaluation of end use quality and root traits in wheat cultivars associated with 1RS.1BL translocation - Ambika Sharma; Imran Sheikh; Rahul Kumar; Krishan Kumar; Pritesh Vyas; H. S. Dhaliwal (Euphytica, 2018)

Development of transcriptome based web genomic resources of yellow mosaic disease in Vigna mungo - Rahul Singh Jasrotia; Mir Asif Iquebal; Pramod Kumar Yadav; Neeraj Kumar; Sarika Jaiswal; U. B. Angadi; Anil Rai; Dinesh Kumar (Physiology and Molecular Biology of Plants, 2017)

Molecular stacking of wide compatibility gene, S5 n and elongated uppermost internode (eui) gene into IR 58025B, an elite maintainer line of rice - Rahul Priyadarshi; Hari Prasad Subramanyam Arremsetty; Akhilesh Kumar Singh; Durga Khandekar; Kandasamy Ulaganathan; Vinay Shenoy (Journal of Plant Biochemistry and Biotechnology, 2017)

Response of Sandy Lake in Schirmacher Oasis, East Antarctica to the glacial-interglacial climate shift - Badanal Siddaiah Mahesh; Anish Kumar Warrier; Rahul Mohan; Manish Tiwari; Rajdeep Roy; Rajesh Asthana; Rasik Ravindra (Journal of Paleolimnology, 2017)

Stability of Coatings on Sulfide Minerals in Acidic and Low-Temperature Environments - Chan-Ung Kang; Byong-Hun Jeon; Rahul Kumar; Seong-Sook Park; Hyun-Sung Park; Sun-Joon Kim (Mine Water and the Environment, 2017)

Satellite-based technique for nowcasting of thunderstorms over Indian region - Suman Goyal; Ashish Kumar; M Mohapatra; L S Rathore; S K Dube; Rahul Saxena; R K Giri (Journal of Earth System Science, 2017)

Uptake, distribution, and remobilization of iron and zinc among various tissues of wheat–Aegilops substitution lines at different growth stages - Prachi Sharma; Imran Sheikh; Dharmendra Singh; Satish Kumar; Shailender Kumar Verma; Rahul Kumar; Pritesh Vyas; Harcharan Singh Dhaliwal (Acta Physiologiae Plantarum, 2017)

Seasonal Trend of Body Protein and Growth of Chironomid Larvae - Susanta Nath; Rahul Podder; Biplob Kumar Modak (Proceedings of the Zoological Society, 2017)

PCV: An Alignment Free Method for Finding Homologous Nucleotide Sequences and its Application in Phylogenetic Study - Rajnish Kumar; Bharat Kumar Mishra; Tapobrata Lahiri; Gautam Kumar; Nilesh Kumar; Rahul Gupta; Manoj Kumar Pal (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Reliability Analysis of Infinite Slope Using Metamodels - Rahul Kumar; Pijush Samui; Sunita Kumari (Geotechnical and Geological Engineering, 2017)

Assessment of Cr, Ni and Pb Pollution in Rural Agricultural Soils of Tonalite–Trondjhemite Series in Central India - Kriti Shukla; Bijendra Kumar; Rahul Agrawal; Kumari Priyanka; Madavi Venkatesh; Anshumali (Bulletin of Environmental Contamination and Toxicology, 2017)

Persistence of acetamiprid in paddy and soil under West Bengal agro-climatic conditions - Soumen Saha; Rahul Mondal; Subhadeep Mukherjee; Mitali Sarkar; Ramen Kumar Kole (Environmental Monitoring and Assessment, 2017)

Experimental investigation of impact of diesel particulate filter on smoke and NOx emissions of a Euro-I compression ignition engine with active and off-board regeneration - Pradeep Kumar Gupta; Dilip Sharma; Shyam Lal Soni; Rahul Goyal; Dheeraj Kishor Johar (Clean Technologies and Environmental Policy, 2017)

Fruit preferential activity of the tomato RIP1 gene promoter in transgenic tomato and Arabidopsis - Priyanka Agarwal; Rahul Kumar; Amit Pareek; Arun K. Sharma (Molecular Genetics and Genomics, 2017)

Recombinant pharmaceutical protein production in plants: unraveling the therapeutic potential of molecular pharming - Vijaya R. Dirisala; Rahul R. Nair; Krupanidhi Srirama; Prakash Narayana Reddy; K. R. S. Sambasiva Rao; N. Satya Sampath Kumar; Giridhar Parvatam (Acta Physiologiae Plantarum, 2017)

Development of real-time reference evapotranspiration at the regional scale using satellite-based observations - Swapnil S. Vyas; Rahul Nigam; Bimal K. Bhattacharya; Prashant Kumar (International Journal of Remote Sensing, 2016)

Identification and expression profiling of DNA methyltransferases during development and stress conditions in Solanaceae - Rahul Kumar; Pankaj Kumar Chauhan; Ashima Khurana (Functional & Integrative Genomics, 2016)

Determination of Optimum Tool for Efficient Rock Cutting - Pijush Samui; Rahul Kumar; Pradeep Kurup (Geotechnical and Geological Engineering, 2016)

Micronutrient Fractionation in Coal Mine-Affected Agricultural Soils, India - Rahul Agrawal; Bijendra Kumar; Kumari Priyanka; Chandravir Narayan; Kriti Shukla; Jhuma Sarkar; Anshumali (Bulletin of Environmental Contamination and Toxicology, 2016)

A review on synthesis, characterization, and applications of nano zero valent iron (nZVI) for environmental remediation - Ritika Mukherjee; Rahul Kumar; Alok Sinha; Yangdup Lama; Amal Krishna Saha (Critical Reviews in Environmental Science and Technology, 2016)

Micronutrients (Fe, Mn, Zn and Cu) balance under long-term application of fertilizer and manure in a tropical rice-rice system - Mohammad Shahid; Arvind Kumar Shukla; Pratap Bhattacharyya; Rahul Tripathi; Sangita Mohanty; Anjani Kumar; Banwari Lal; Priyanka Gautam; Rajagounder Raja; Bipin Bihari Panda; Brundaban Das; Amaresh Kumar Nayak (Journal of Soils and Sediments, 2016)

Defense Transcriptome Analysis of Sugarcane and Colletotrichum falcatum Interaction Using Host Suspension Cells and Pathogen Elicitor - P. R. Rahul; V. Ganesh Kumar; R. Viswanathan; A. Ramesh Sundar; P. Malathi; C. Naveen Prasanth; P. T. Pratima (Sugar Tech, 2016)

Streptomyces lonarensis sp. nov., isolated from Lonar Lake, a meteorite salt water lake in India - Trupti K. Sharma; Rahul Mawlankar; Vidya V. Sonalkar; Vidhya K. Shinde; Jing Zhan; Wen-Jun Li; Meenakshi V. Rele; Syed G. Dastager; Lalitha Sunil Kumar (Antonie van Leeuwenhoek, 2016)

Animal models of hepatotoxicity - Ganesh Singh Bhakuni; Onkar Bedi; Jitender Bariwal; Rahul Deshmukh; Puneet Kumar (Inflammation Research, 2016)

Floristic assessment of the important least concern plant species with taxonomic descriptions along the National Highway - Jitin Rahul; Manish Kumar Jain (Brazilian Journal of Botany, 2015)

Characterizing spatial variability of soil properties in salt affected coastal India using geostatistics and kriging - Rahul Tripathi; A. K. Nayak; Mohammad Shahid; R. Raja; B. B. Panda; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; R. N. Sahoo (Arabian Journal of Geosciences, 2015)

Genomic Survey, Gene Expression, and Interaction Analysis Suggest Diverse Roles of ARF and Aux/IAA Proteins in Solanaceae - Rahul Kumar; Priyanka Agarwal; Amit Pareek; Akhilesh K. Tyagi; Arun K. Sharma (Plant Molecular Biology Reporter, 2015)

Changes in vasotocin levels in relation to ovarian development in the catfish Heteropneustes fossilis exposed to altered photoperiod and temperature - Radha Chaube; Rahul Kumar Singh; Keerikattil P. Joy (Fish Physiology and Biochemistry, 2015)

Insights from the Molecular Docking of Hydrolytic Products of Methyl Isocyanate (MIC) to Inhibition of Human Immune Proteins - Manish Kumar Tripathi; Mohammad Yasir; Vikram Singh Gurjar; Protiti Bose; Amit Dubey; Rahul Shrivastava (Interdisciplinary Sciences: Computational Life Sciences, 2015)

First molecular evidence of the transplacental transmission of Theileria annulata - Vikrant Sudan; Shanker Kumar Singh; Amit Kumar Jaiswal; Rahul Parashar; Daya Shanker (Tropical Animal Health and Production, 2015)

Identification and cross-species amplification of microsatellite markers derived from expressed sequence data of rose species - Ram Kumar Sharma; Anil Chaudhary; Himanshu Sharma; Pankaj Bhardwaj; Vikas Sharma; Rahul Kumar; Paramvir Singh Ahuja (Journal of Plant Biochemistry and Biotechnology, 2015)

The Role of 25-Hydroxy Vitamin D Deficiency in Iron Deficient Children of North India - Shikha Sharma; Rahul Jain; Pradeep Kumar Dabla (Indian Journal of Clinical Biochemistry, 2015)

A duplex PCR-based assay for simultaneous detection of Trypanosoma evansi and Theileria annulata infections in water buffaloes - Vikrant Sudan; Amit Kumar Jaiswal; Rahul Parashar; Daya Shanker (Tropical Animal Health and Production, 2015)

Effect of zinc supplements in the attenuated cardioprotective effect of ischemic preconditioning in hyperlipidemic rat heart - Sunil Kumar Kansal; Uma Jyoti; Samridhi Sharma; Arun Kaura; Rahul Deshmukh; Sandeep Goyal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

An Overview of Ultraviolet B Radiation-Induced Skin Cancer Chemoprevention by Silibinin - Rahul Kumar; Gagan Deep; Rajesh Agarwal (Current Pharmacology Reports, 2015)

Three-Dimensional Blood Vessel Segmentation and Centerline Extraction based on Two-Dimensional Cross-Section Analysis - Rahul Prasanna Kumar; Fritz Albregtsen; Martin Reimers; Bjørn Edwin; Thomas Langø; Ole Jakob Elle (Annals of Biomedical Engineering, 2015)

Effect of Licofelone—A Dual COX/5-LOX Inhibitor in Intracerebroventricular Streptozotocin-Induced Behavioral and Biochemical Abnormalities in Rats - Ashok Kumar; Sorabh Sharma; Ashwani Prashar; Rahul Deshmukh (Journal of Molecular Neuroscience, 2015)

Capsaicin inhibits collagen fibril formation and increases the stability of collagen fibers - Sathiamurthi Perumal; Kriti Dubey; Rahul Badhwar; Kodimattan Joseph George; Rakesh Kumar Sharma; Ganesh Bagler; Balaraman Madhan; Karunakar Kar (European Biophysics Journal, 2015)

Insights from the molecular docking of hydrolytic products of methyl iso cyanate (MIC) to inhibition of human immune proteins - Manish Kumar Tripathi; Mohammad Yasir; Vikram Singh Gurjar; Protiti Bose; Amit Dubey; Rahul Shrivastava (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Characterization and 3D structure prediction of chitinase induced in sugarcane during pathogenesis of Colletotrichum falcatum - P. R. Rahul; V. Ganesh Kumar; M. Sathyabhama; R. Viswanathan; A. Ramesh Sundar; P. Malathi (Journal of Plant Biochemistry and Biotechnology, 2015)

Identification and molecular characterization of a novel splice variant of human 5- lipoxygenase gene - Abhay Kumar Singh; Rahul Kumar; Abhay Anand Shukla; Gururao Hariprasad; Shyam Sunder Chauhan; Sharmistha Dey (Molecular Biology Reports, 2014)

Functional genomics of tomato: Opportunities and challenges in post-genome NGS era - Rahul Kumar; Ashima Khurana (Journal of Biosciences, 2014)

Nitric oxide is involved in salicylic acid-induced flowering of Lemna aequinoctialis Welw. - Ashima Khurana; Rahul Kumar; Shashi B. Babbar (Acta Physiologiae Plantarum, 2014)

9, 10-Bis(8-Quinolinoxymethyl)Anthracene—A Fluorescent Sensor for Nanomolar Detection of Cu2+ with Unusual Acid Stability of Cu2+-Complex - Prabhpreet Singh; Rahul Kumar; Subodh Kumar (Journal of Fluorescence, 2014)

Fly Ash Addition Affects Microbial Biomass and Carbon Mineralization in Agricultural Soils - A. K. Nayak; Anjani Kumar; R. Raja; K. S. Rao; Sangita Mohanty; Mohammad Shahid; Rahul Tripathy; B. B. Panda; P. Bhattacharyya (Bulletin of Environmental Contamination and Toxicology, 2014)

Synthesis and comparative bioefficacy of N-(1-phenethyl-4-piperidinyl)propionanilide (fentanyl) and its 1-substituted analogs in Swiss albino mice - Pradeep Kumar Gupta; Shiv Kumar Yadav; Yangchen Doma Bhutia; Poonam Singh; Pooja Rao; Niranjan Laxman Gujar; Kumaran Ganesan; Rahul Bhattacharya (Medicinal Chemistry Research, 2013)

Characterization and gene mapping of a brittle culm mutant of diploid wheat (Triticum monococcum L.) with irregular xylem vessels development - Mohammad Javed Ansari; Ahmad Al-Ghamdi; Salma Usmani; Rahul Kumar; Adgaba Nuru; Kuldeep Singh; Harcharan Singh Dhaliwal (Acta Physiologiae Plantarum, 2013)

Vortices Formed on the Mitral Valve Tips Aid Normal Left Ventricular Filling - John J. Charonko; Rahul Kumar; Kelley Stewart; William C. Little; Pavlos P. Vlachos (Annals of Biomedical Engineering, 2013)

Angular Circulation Speed of Tablets in a Vibratory Tablet Coating Pan - Rahul Kumar; Carl Wassgren (AAPS PharmSciTech, 2013)

Effect of Counterions on Physicochemical Properties of Prazosin Salts - Lokesh Kumar; Chhuttan Lal Meena; Yogesh B. Pawar; Banrida Wahlang; Kulbhushan Tikoo; Rahul Jain; Arvind K. Bansal (AAPS PharmSciTech, 2013)

Subtle structural differences crucial for function in similarly engineered ADP-glucose pyrophosphorylase larger subunit in rice and maize - Rahul Kaushik; Monica Vashist; Sunita Jain; V. K. Sikka; Sudhir Kumar (Journal of Plant Biochemistry and Biotechnology, 2012)

Characterization and molecular mapping of EMS-induced brittle culm mutants of diploid wheat (Triticum monococcum L.) - Mohd. Javed Ansari; Rahul Kumar; Kuldeep Singh; Harcharan S. Dhaliwal (Euphytica, 2012)

Identification and validation of sex-linked SCAR markers in dioecious Hippophae rhamnoides L. (Elaeagnaceae) - Girish Korekar; Ram Kumar Sharma; Rahul Kumar; Meenu; Naveen C. Bisht; Ravi B. Srivastava; Paramvir Singh Ahuja; Tsering Stobdan (Biotechnology Letters, 2012)

Microbial Biomass and Carbon Mineralization in Agricultural Soils as Affected by Pesticide Addition - Anjani Kumar; A. K. Nayak; Arvind K. Shukla; B. B. Panda; R. Raja; Mohammad Shahid; Rahul Tripathi; Sangita Mohanty; P. C. Rath (Bulletin of Environmental Contamination and Toxicology, 2012)

Genome-wide investigation and expression analysis suggest diverse roles of auxin-responsive GH3 genes during development and response to different stimuli in tomato (Solanum lycopersicum) - Rahul Kumar; Priyanka Agarwal; Akhilesh K. Tyagi; Arun K. Sharma (Molecular Genetics and Genomics, 2012)

Transcriptome analysis of rin mutant fruit and in silico analysis of promoters of differentially regulated genes provides insight into LeMADS-RIN-regulated ethylene-dependent as well as ethylene-independent aspects of ripening in tomato - Rahul Kumar; Manoj K. Sharma; Sanjay Kapoor; Akhilesh K. Tyagi; Arun K. Sharma (Molecular Genetics and Genomics, 2012)

Formulation of Time Series Vegetation Index from Indian Geostationary Satellite and Comparison with Global Product - Rahul Nigam; Bimal Kumar Bhattacharya; Keshav R. Gunjal; N. Padmanabhan; N. K. Patel (Journal of the Indian Society of Remote Sensing, 2012)

Solubility-Modulated Asymmetric Membrane Tablets of Triprolidine Hydrochloride: Statistical Optimization and Evaluation - Rahul Dev; Anil Kumar; Kamla Pathak (AAPS PharmSciTech, 2012)

Erratum to: DNA damage in the presence of chemical genotoxic agents induce acetylation of H3K56 and H4K16 but not H3K9 in mammalian cells - Rahul Kumar Vempati; Devyani Haldar (Molecular Biology Reports, 2012)

DNA damage in the presence of chemical genotoxic agents induce acetylation of H3K56 and H4K16 but not H3K9 in mammalian cells - Rahul Kumar Vempati (Molecular Biology Reports, 2012)

Genome-wide analysis of auxin response factor (ARF) gene family from tomato and analysis of their role in flower and fruit development - Rahul Kumar; Akhilesh K. Tyagi; Arun K. Sharma (Molecular Genetics and Genomics, 2011)

Pyramiding of two bacterial blight resistance and a semidwarfing gene in Type 3 Basmati using marker-assisted selection - Deepak Rajpurohit; Rahul Kumar; Mankesh Kumar; Priyanka Paul; Anjali Awasthi; P. Osman Basha; Anju Puri; Tripta Jhang; Kuldeep Singh; Harcharan Singh Dhaliwal (Euphytica, 2011)

Identification, phylogeny, and transcript profiling of ERF family genes during development and abiotic stress treatments in tomato - Manoj K. Sharma; Rahul Kumar; Amolkumar U. Solanke; Rita Sharma; Akhilesh K. Tyagi; Arun K. Sharma (Molecular Genetics and Genomics, 2010)

Sustainable bioenergy production strategies for rural India - Rahul B. Hiremath; Bimlesh Kumar; P. Balachandra; N. H. Ravindranath (Mitigation and Adaptation Strategies for Global Change, 2010)

Development of a New Comprehensive Ocean Atlas for Indian Ocean utilizing ARGO Data - B. Prasad Kumar; Rahul Barman; S. K. Dube; P. C. Pandey; M. Ravichandran; Shailesh Nayak (International Journal of Climatology, 2010)
The World Ocean Atlas (WOA), also termed ‘Levitus Climatology’, is a global ocean climatology containing monthly, seasonal and annual means of temperature (T) and salinity (S) fields at standard ocean depths. The monthly climatology for T and S is available for standard depths up to 1000 m. The database used in the preparation of this climatology (WOA) are historical records of Conductivity, Temperature and Depth (CTD) casts and other available marine observations collected in the past. The methodology used in preparation of this WOA is objective analysis which is essentially non‐synoptic and widely scattered in the space domain. We understand that ARGO data has so far not been blended with WOA, nor has its impact for improving WOA climatology been attempted. Presently, with the wealth of marine data from ARGO profilers in the Indian Ocean, we propose a new approach to reconstruct T and S fields optimally utilizing the ARGO data. Here we develop a new model using Delaunay Tessellation with QHull algorithm delivering three‐dimensional T and S fields from a non‐uniform scattered database up to a depth of 1000 m. For gaps in a data‐sparse region, we use all available quality‐checked Ocean Station Data (OSD) and Profiling Float Data (PFL) information on T and S, in addition to the existing ARGO data. The initiative here was to replace WOA data points with realistic information from ARGO and in situ data, thereby producing a new climatology atlas. We demonstrate the robustness of our approach, and the final climatology on T and S is better compared with the existing state‐of‐the‐art WOA. The advantage of the proposed methodology is the scope of improving the ocean atlas with the addition of more ARGO data in the near future. The clustered approach in modelling enables ocean parameter retrieval in geometrically disconnected regions with an option for hot restart. We believe that the new climatology will benefit the research community immensely. Copyright © 2009 Royal Meteorological Society

Guanidine hydrochloride and urea-induced unfolding of Brugia malayi hexokinase - Alok Ranjan Singh; Shweta Joshi; Rahul Arya; Arvind Mohan Kayastha; Jitendra Kumar Saxena (European Biophysics Journal, 2010)

A partner monoclonal antibody to Moab 730 kills 100% of DU145 and PC3 androgen-independent cancer cells - Hemant Kumar Vyas; Rahul Pal; Nirmal K. Lohiya; G. P. Talwar (Journal of Biosciences, 2009)

Influence of nitrogen on the expression of TaDof1 transcription factor in wheat and its relationship with photo synthetic and ammonium assimilating efficiency - Rahul Kumar; Ravindra Taware; Vikram S. Gaur; S. K. Guru; Anil Kumar (Molecular Biology Reports, 2009)

Relative Microalgal Concentration in Prydz Bay, East Antarctica during Late Austral Summer, 2006 - Rahul Mohan; Sunil Kumar Shukla; N. Anilkumar; M. Sudhakar; Satya Prakash; R. Ramesh (Algae, 2009)

Identification and cross-species amplification of EST derived SSR markers in different bamboo species - Vikas Sharma; Pankaj Bhardwaj; Rahul Kumar; Ram Kumar Sharma; Anil Sood; Paramvir Singh Ahuja (Conservation Genetics, 2009)

Interaction between sugarcane and Colletotrichum falcatum causing red rot: Understanding disease resistance at transcription level - R. Viswanathan; A. Ramesh Sundar; P. Malathi; P. R. Rahul; V. Ganesh Kumar; R. Banumathy; P. T. Prathima; M. Raveendran; K. K. Kumar; P. Balasubramanian (Sugar Tech, 2009)

Regulation of native GABAA receptors by PKC and protein phosphatase activity - Sandeep Kumar; Rahul T. Khisti; A. Leslie Morrow (Psychopharmacology, 2005)

Protective efficacy and immunogenicity of Escherichia coli K13 diphtheria toxoid conjugate against experimental ascending pyelonephritis - Varinder Kumar; NK Ganguly; Kusum Joshi; Rahul Mittal; Kusum Harjai; Sanjay Chhibber; Saroj Sharma (Medical Microbiology and Immunology, 2005)

Genetic control of banded leaf and sheath blight (Rhizoctonia solani f. sp. sasakii) in maize (Zea mays L.) - Rahul Kumar; I. S. Singh (Cereal Research Communications, 2004)

Biosensor based on Langmuir–Blodgett films of poly(3-hexyl thiophene) for detection of galactose in human blood - Sandeep K. Sharma; Rahul Singhal; B.D. Malhotra; Neeta Sehgal; Ashok Kumar (Biotechnology Letters, 2004)

Enzymatic synthesis of multi-component copolymers and their structural characterization - Rajesh Kumar; Rahul Tyagi; Virinder S. Parmar; Lynne A. Samuelson; Jayant Kumar; Arthur C. Watterson (Molecular Diversity, 2003)